Muslim Diasporas and the Politics of Belonging: Ibadi and Ismaili Pasts and Presents in East Africa - Wortmann, Kimberly T. (Religion Compass, 2025)
ABSTRACT This article examines the Ibadi and Ismaili Muslim communities in East Africa—particularly in Uganda, Kenya, and Tanzania (including Zanzibar)—and their distinct religious, social, and economic roles. Even as minorities within predominantly Sunni contexts, both groups have shaped the region through migration, commerce, and international networks. Often overlooked in studies of postcolonial Islam, they are frequently (mis)identified by ethnic labels (“waarabu” for Ibadis, “wahindi” for Ismailis), which obscure their complex identities. By offering an overview of their religious traditions, migration histories, and institutional presence, the article highlights how these communities challenge dominant frameworks within both regional histories and the academic study of Islam. In doing so, it contributes to broader discussions in religious studies around pluralism, identity, and the intersections of race, religion, and belonging in postcolonial contexts—key concerns for scholars of religion today.

Afterlives of Revolution: Everyday Counterhistories in Southern Oman Alice Wilson (Stanford, CA: Stanford University Press, 2023). Pp. 336. $30.00 paper. ISBN: 9781503635784 - Lori, Noora (International Journal of Middle East Studies, 2025)
Keywords: Recension

المخطوط الفقهي العماني: مظانه ونهج التعامل معه في دراسة سير الفقهاء ونتاجهم العلمي من خلال كتاب: إتحاف الأعيان للمؤرخ البطاشي - البطاشي, هلال بن خلفان (مجلة الشهاب, 2025)

الأصول ألمازيغيّة لبعض تراكيب ألدّارجة التّونسيّة (Revue de l'Institut des Belles Lettres Arabes, 2025)
‫يختلف‬‫ الناس‬ ‫في‬ ‫كون‬ ‫ما‬ ‫يتكلّم‬ ‫به‬ ‫التّونسيون‬ ‫لغة‬ ‫أو‬ ‫لھجة‬ ‫‪.‬‬‫وقد‬‫تح‬‫ّم‬‫س ‬‫الكثير‬ ‫من‬ ‫األكاديميين‬ ‫‪‬‬‫منذ‬ ‫أوائل‬ ‫سبعينيات‬ ‫القرن‬ ‫الماضي‬ ‫إلى‬‫كونھا ‬‫لغة‬ ‫وعملوا‬ ‫على‬ ‫استجالء‬ ‫قواعدھا‬ ‫كما‬ ‫اعتمدھا‬ ‫الكثير‬ ‫من‬‫الكتّاب ‬‬‫في‬ ‫كتاباتھم‪،‬‬ ‫غير‬ ‫أنّھم‬ ‫لم‬ ‫يختلفوا‬ ‫جميعا‬ ‫على‬ ‫ثراء‬ ‫ھذه‬ ‫اللّغة‬ ‫‪/‬‬‫اللّھجة‬‫وعلى‬ ‫حضور‬ ‫مؤ‬‫ثرات‬‫ و موروثات‬ ‫لغوية‬ ‫عديدة‬ ‫فيھا‬ .
Keywords: Linguistique -- Djerba

Rive orientale de l'Arabie: hommes et espaces au début de l'islam / Moez Dridi. Éd. l'Harmattan, 2025 - Lochon, Christian (Mondes et Cultures : comptes rendus trimestriels des séances de l’Académie des sciences d’outre-mer, 2025)
Keywords: Recension

La necropoli dell’Antica Età del Bronzo di Halban (Governatorato di Al-Batinah Sud), Sultanato dell’Oman - Bortolini, Eugenio; Seghi, Francesca; Facciani, Sara; Bianchi, Vittoria; Brener, Elisa; Bernardini, Sara; Silvestrini, Sara; Frenez, Dennys; Urcia, Alberto; Vazzana, Antonino; Benazzi, Stefano (Ocnus, 2025)
The site of Halban, located 35 km to the west of the capital city Muscat (Sultanate of Oman), was first mentioned in 1998. The site comprises 33 well-preserved monumental stone funerary structures situated on a limestone terrace between the Al-Batinah coastal plain and the Al-Hajar Al-Gharbi mountains. Most of these tombs date back to the 3rd millennium BCE and are characterized by their substantial diameter, considerable remaining height, and noticeable variability in construction techniques and external polishing. This contribu- tion presents the preliminary results of the excavations carried out in 2023 and 2024, which reveal a complex palimpsest of continuity and reuse at a strategic location. This position enabled the connection of inland oases with coastal communities and allowed for the interception of major short- and long-distance trade routes during the 3rd millennium BCE.

Relieved or Deceived? The Reception of the Egyptian Invasion of 1875–1876 in the Sultanate of Zanzibar and Its Subsequent Interpretations - PaweŁczak, Marek (Journal of World History, 2025)
This article examines the East African experience of the 1875–1876 Egyptian invasion of part of the Sultanate of Zanzibar and its interpretation as preserved in written sources. The key part of this article's argument addresses important questions posed by global history, namely: what was the image of the modernizing world from its peripheries? How was the information upon which it was built spread, hierarchized, and interpreted?, The author analyzes the traces of the invasion left in Zanzibar's later historical memory, which he compares with the known facts concerning the course and reception of the Egyptian actions. The article strives to embed the conclusions thus reached in its diachronic analysis. It also uses explanatory models (referred to as conspiracy theories) to understand the population's political mood and its access to information about the international situation. The initial premise for creating conspiracy theories, the author argues, was the contradiction between the image of Egypt as a strong Muslim state and a potential anti-imperial ally, rooted in the minds of the Sultan of Zanzibar's Muslim subjects and in the practices of the occupying forces.

القوة البحرية العُمانية في عهد الإمام سيف بن سلطان اليعربي (1692–1711م) " دراسة في السياسة الخارجية وبناء النفوذ الإقليمي" - الهادي, حبيب بن مرهون بن سعيد (حوليات آداب عين شمس, 2025)
At the dawn of the modern era, the Islamic world faced an overwhelming wave of colonial expansion, as European powers sought to dominate vital maritime routes and commercial hubs across the East, aiming to control global trade and natural resources. The western Indian Ocean—comprising the coasts of the Arabian Gulf, the Arabian Peninsula, western India, and eastern Africa—became a major theatre of this imperial contest, as vast areas fell under Portuguese domination for more than a century. Yet, divine providence granted this region enlightened leadership embodied in the Imams of Oman from the Yaʿrubi dynasty, who confronted the colonial advance with a comprehensive liberation project that reshaped the geopolitical balance in the western Indian Ocean and inaugurated a new era of regional stability, prosperity, and sovereignty. This study examines Oman’s foreign policy during the reign of Imam Saif bin Sultan al-Yaʿrubi (1692–1711 CE) as a distinguished model of Islamic leadership that successfully employed naval and diplomatic power to achieve regional peace and security while consolidating Oman’s independence in the face of European expansionism. The research adopts a descriptive-analytical methodology, drawing upon historical documents, maps, and primary and secondary sources to uncover the intellectual and strategic foundations of Omani foreign policy during this pivotal period and to assess its political, military, and economic outcomes across the broader Indian Ocean region. The first section explores Imam Saif bin Sultan’s policy of consolidating security and promoting peace throughout the western Indian Ocean through a comprehensive strategic vision grounded in the unification of the Omani interior and the enhancement of the state’s maritime and commercial capabilities. The second section analyzes the outcomes of this policy, which combined firmness and pragmatism in confronting colonial powers, as the Imam pursued a systematic offensive strategy aimed at liberating Portuguese strongholds and securing international navigation and free trade. The study concludes that the era of Imam Saif bin Sultan marked a strategic turning point in Omani foreign policy, transforming the state from a defensive actor into a proactive regional power. His leadership institutionalized the principles of maritime sovereignty, preventive diplomacy, and regional balance in an era marked by intense global competition. Furthermore, this Omani experience provides valuable insights into the enduring concept of peace through strength and exemplifies an early form of ethical realism in Arab-Islamic political thought and practice. Keywords: Imam Saif bin Sultan al-Yaʿrubi, foreign policy, the Portuguese, western Indian Ocean, Omani naval power.

Incensi omaniti - Mion, Giuliano (Rivista degli studi orientali, 2025)

Contribution à l’etude des modes d’usage des parcours de la région de Ghardaïa (Sahara septentrional algerien) - Senoussi, Abdelhakim; Bensemaoune, Youcef; Bouagga, Abdelhamid; Faradji, Khalil (Revue des bio ressources, 2025)

دوافع الفخر النرجسي وتجلياته في شعر سليمان النبهاني - الحوقاني, عيسى بن سعيد بن عيسى (مجلة الأندلس للعلوم الإنسانية والاجتماعية, 2025)
تتناول هذه الدراسة ظاهرة الفخر النرجسي في شعر سليمان بن سليمان بن مظفر النبهاني للوقوف على دوافعها وأسبابها، والكشف عن تجلياتها المختلفة، وإسهامها في توجيه إبداعه الشعري، وسعت الدراسة إلى استنطاق النصوص الشعرية وتتبع العوامل الخارجية التي أسهمت في إنتاجها، وتنبثق أهمية هذه الدراسة من كونها تتناول ظاهرة نفسية لم تسبق دراستها في شعر سليمان النبهاني بل لم تدرس. س- حسب اطلاعنا- في الشعر العماني عامة، ومما يزيد الموضوع جدة وطرافة أن هذا الشاعر أحد ملوك الدولة النبهانية التي حكمت عمان قرونا من الزمن، وخاض ملوكها صراعات كبيرة ضد خصومهم لتثبيت ملكهم. ولنا أن نتساءل عن دوافع الفخر النرجسي عند النبهاني، وعن تجلياته في نتاجه الشعري وللإجابة عن ذلك لجأت الدراسة إلى تتبع الفخر في شعره، واتكأت على تحليل النصوص الشعرية واستنطاقها، والوقوف على العوامل الخارجية المحيطة بالشاعر لحظة إبداعه الشعري، وتوسلت الدراسة المنهج النفسي مع الإفادة من نظريتي التلقي والتأويل. وقد اقتضت حيثيات الدراسة قسمتها إلى مقدمة وأربعة محاور: المحور الأول: دوافع الفخر النرجسي في شعر سليمان النبهاني المحور الثاني: نرجسية الفخر بأصالة العرق ووراثة الملك. المحور الثالث: نرجسية الفخر بتفخيم الذات واحتقار الآخر. المحور الرابع: نرجسية الفخر بادعاء التفرد. وقد خلصت الدراسة إلى أن أبرز دوافع الفخر النرجسي عند النبهاني تتمثل في اجتماع عراقة النسب ووراثة الملك، وكثرة المنازعين له في ملكه، بالإضافة إلى نشأته الملكية، وأسهمت قدراته الشعرية والسياسية والقتالية في تكريس النرجسية في شخصيته، وقد تجلى الفخر النرجسي في شعر النبهاني في مظاهر ثلاثة: أولها نرجسية الفخر بأصالة العرق ووراثة الملك، وثانيها الفخر بتفخيم الذات واحتقار الآخر، وآخرها الفخر بإدعاء التفرد.

موقف الإباضية من رؤية الله تعالى في الآخرة عرض ونقد - إبراهيم, محمد رشدي (مجلة كلية البنات الأزهرية بالعاشر من رمضان, 2025)

رسالتا الإمامِ راشد بن سعيد اليَحْمُديِّ العمانيِّ (445 هـ) في السِّياسة الشَّرْعية- دراسة نصية تداولية - لقم, أحمد علي (حولية کلية اللغة العربية بجرجا, 2025)
الملخصتتناول هذه الدراسةُ رسالتين في السياسة الشرعية للإمام راشد بن سعيد اليحمدي، أحد أعلام الفكر العُمَاني من منظورٍ لغويٍّ وتداوليٍّ وسيميائيٍّ؛ للكشف عن البنية اللغوية العميقة للخطاب، وتنبعُ أهميةُ البحث من سعيه إلى إحياء النصوص التراثية من داخل بنائها اللغوي، وإبرازِ ما تمتازُ به من تماسكٍ نصيٍّ، واتساقٍ دلاليٍّ، وقوّةٍ حجاجيّةٍ تستمدّ سلطانها من البناء اللغوي، والبرهان العقليِّ.وجاءت حدودُ البحث محصورةً في تحليل الجوانب اللغوية والأسلوبية للرسالتين دون التوسّع في الجانب التاريخي أو الفقهي، واقتضى موضوع البحث أن يقع في تمهيد، وثلاثة مباحث، وخاتمة:-المبحث الأول: التحليل التداولي للرسالتين.   المبحث الثاني: الإطار النظري لسيميائية العلامة الإعرابية.المبحث الثالث: سيميائية العلامة الإعرابية في الرسالتين.   ثم خاتمة البحث، وفيها أهم النتائج والتوصيات.وقد اعتمدت الدراسةُ منهجًا تحليليًّا مركّبًا يجمعُ بين ثلاثةِ محاورَ متكاملةٍ: التحليل النصيّ لبيانِ علاقات التماسك والانسجام، والتحليل التداوليّ للكشف عن المقاصد الخطابية ووظائفها الإنجازية، والتحليل السيميائيّ لرصدِ العلامات الإعرابية والرمزية في سياقها المقصديّ.وقد أفضت النتائجُ إلى أنّ الخطابَ السياسيَّ عند الإمامِ راشدٍ يتّسمُ بتركيبٍ لغويٍّ رصينٍ يستندُ إلى التلاحمِ النحويِّ والدلالةِ المقصديّة، مما أضفى على النصّ قوّةً بيانيةً وسلطةً شرعيةً حملت المخاطبَ على الامتثال والإذعان، كما كشفت الدراسةُ عن إسهام العلاماتِ الإعرابيةَ في توليدِ دلالاتٍ تداوليّةٍ وسياقيةٍ تتجاوزُ الوظيفةَ النحويةَ الظاهرة.وتوصي الدراسةُ بضرورةِ الإفادةِ من المناهجِ اللسانيةِ الحديثةِ في قراءةِ النصوصِ التراثيةِ قراءةً علميةً تُبرزُ ثراءها الدلاليَّ والبيانيَّ، وتُعيدُ وصلَ التراثِ بآفاقِ الدرسِ اللغويِّ المعاصر.

مسلك الشراء عند الإباضيَّة وأثره في الجماعات الإسلاميَّة المعاصرة عرض ودراسة - السحيمي, سليمان بن سالم (مجلة کلية الدراسات الإسلامية للبنين بأسوان, 2025)
اشتمل البحث على تعريف الإباضية وأهم عقائدها بإيجاز، والمراد بمسالك الدين؛ وهي الطرق التي يتوصل بها لإنفاذ الأحكام الشرعية والإمامة عند الإباضية، وهي أربعة: الظهور، والدفاع، والشراء، والكتمان، مع بيان المراد بمسلك الشراء ومنزلته وشروطه وأهدافه ومهامه وحقيقته المتمثلة في الثورة على الحاكم؛ لمواجهة الانحراف، ونقد الفساد، والأمر بالمعروف والنهي عن المنكر بالقوة والعنف، فوجدت الجماعات الإسلامية المعاصرة مندوحة في الشراء؛ إذ الثورة والعنف منهجًا وسلوكًا لها، وكان الجامع بينهما التضحية والفداء ووحدة الهدف، وقد تجلى ذلك في المشابهة من حيث وجود: عدد، وبيعة، وأهداف، كما سوغ الشراء للبعض بالقيام بالعمليات الفدائية لسوء الفهم والخلل في الاستدلال. وختم البحث بمناقشة أدلة الشراء، ومسلك الجماعات وبيان مناقضته لما جاءت به الشريعة من وجوب الصبر على جور الأئمة، وترك قتالهم والخروج عليهم، وما يترتب على ذلك من مفاسد وفتن.

İbâdiyye’nin Hz. Ali Dönemi Olaylarına Dair Eleştiri ve Görüşleri - Yoldaş, Mehmet Hanifi; Kubat, Mehmet (Genç Mütefekkirler Dergisi, 2025)
İbâdiyye, İslam tarihi içerisinde erken sayılabilecek bir dönemde teşekkül eden ilk İslam mezheplerindendir. Hz. Ali dönemi siyasî olayları sonucu ortaya çıkan Muhakkime-i Ulâ’nın devamı olarak kendilerini nitelendiren İbâdîler, Basra şehrinin politize olmuş ortamında mezhepleşme sürecini devam ettirmişlerdir. Dönemin siyasi olayları ve bu olaylarla nedeniyle tartışılan dini konular İslam toplumunun öncelikli gündem maddelerini başında gelmektedir. İbâdî toplumu da Basra şehrini ve içinde yaşadıkları toplumun siyasi ve dini atmosferi gereği birçok konu hakkında görüş ve eleştiriler ortaya koymuştur. Bu konuların başında Hz. Ali dönemi olayları ve bu olaylar nedeniyle tartışılan dinî meseleler gelmektedir. İbâdiyye, Ehl-i sünnet’e göre Hz. Ali dönemi olaylarını farklı zaviyeden değerlendirmekte ve bazı olaylarda Hz. Ali’nin haklı bazı olaylarda ise haksız olduğunu dile getirmektedir. İslam tarihinde yaşanmış ve kendisinden sonra tarihin akışına yön vermiş olan Hz. Ali dönemi olaylarına dair İbâdîlerin görüş ve eleştirilerini incelemek İbâdiyye mezhebini tanıma ve anlama adına önem kesp etmektedir.

İbâdî Usûlcülere Göre Râvi Sayısı Bakımından Hadisler -Vercelânî Örneği- - Kaya, Mehmed Sıddık; Agitoğlu, Nurullah (Bitlis İlahiyat Dergisi, 2025)
Hz. Peygamber’in vefatından sonra, ilk iki halife dönemi ve Hz. Osman’ın halifeliğinin ilk döneminde birlik ve beraberlik içinde yaşayan Müslümanlar, müteakip dönemlerde yaşanan olaylar neticesinde fırkalara bölünmüşlerdir. Bunlardan dikkat çeken önemli bir fırka da Hâricîlerdir. Zaman içinde farklı gruplara bölünen Hâricîler, sahip oldukları aşırı ve sert tutumlarından dolayı tarih sahnesinden silinmişler, sadece haklarında makâlât kitaplarından bizlere aktarılan bilgiler kalmıştır. Diğer Hâricî gruplara nazaran daha ılımlı bir çizgiyi benimseyen İbâdîler ise bu fırkadan günümüze ulaşabilmiş tek gruptur. Hz. Ali döneminden sonra ortaya çıkan karışıklarla beraber hadis uydurma faaliyetlerinin görülmeye başlamasıyla sahih hadisleri zayıf ve uydurma olanlarından ayırmak için hadis usûlü ortaya çıkmaya başlamıştır. Genelde hadis usûlü çalışmalarında birlik sağlanmış olmasına rağmen yer yer mezhebî farklılıkların da ortaya çıktığı görülmektedir. Bu makalede haklarında yeteri kadar çalışma yapılmamış olduğundan dolayı yeterince tanınmayan veya yanlış tanıtılmış olan İbâdiyye mezhebinin bu konudaki görüşlerine değinilmeye çalışılacaktır. Aynı zamanda konunun daha iyi anlaşılması için yer yer İbâdî âlimlerin râvi sayısına göre hadislere bakışı, Sünnî âlimlerin bu konudaki görüşleriyle karşılaştırılması yapılacaktır. Makalede İbâdiyye mezhebinin önemli bir âlimi olup mezhepte söz sahibi olmasından konu Vercelânî özelinden ele alınacaktır. Burada Vercelânî’nin hadislere verdiği değer, mütevâtir ve âhâd habere bakışı ile bunların dinde hüccet olup olmadığı konularına değinilecektir.

الحراك العلمي في بايلك الشرق والصحراء الجزائرية خلال العهد العثماني: قراءة في المظاهر والأعلام - Djekaba, Nadji (Burdur İlahiyat Dergisi, 2025)
يهدف هذا البحث إلى دراسة الحراك العلمي في بايلك الشرق والصحراء الكبرى خلال العهد العثماني، مع التركيز على الحواضر العلمية البارزة مثل قسنطينة وعنابة وتوات وورقلة وميزاب. تُبرز الدراسة الدور المحوري لهذه الحواضر في إثراء الحياة العلمية والثقافية بالجزائر بفضل تنوعها الجغرافي والمذهبي وتفاعلها مع الحواضر المجاورة. كانت قسنطينة مركزًا علميًا وإداريًا بارزًا بفضل دعم البايات العثمانيين وإنشاء مؤسسات تعليمية مثل المدرسة الكتانية، بينما شهدت عنابة حضورًا علميًا مميزًا لأسر مثل البوني. أما في الصحراء الكبرى، فبرزت حواضر مثل توات وورقلة وميزاب كمراكز علمية ذات أهمية خاصة، حيث ازدهرت العلوم الشرعية والعقلية بفضل موقعها الاستراتيجي على طرق التجارة الصحراوية الذي سهل انتقال العلماء والكتب. يشير البحث إلى التنوع المذهبي بين المالكية والإباضية في هذه الحواضر، مما أضفى ثراءً على الحياة العلمية، مع الإشارة إلى غياب جامعة مركزية كالزيتونة أو الأزهر بسبب التوازن العلمي بين الحواضر المختلفة. وتسعى الدراسة إلى تسليط الضوء على المظاهر المختلفة لهذا الحراك العلمي وأعلامه الذين كان لهم دور محوري في تشكيل المشهد الثقافي والفكري للجزائر خلال تلك الفترة. كما تهدف إلى استعراض الإسهامات العلمية لهذه الحواضر من خلال المؤسسات التعليمية، الزوايا، والمدارس، بالإضافة إلى الأسر العلمية التي لعبت دورًا رياديًا في نشر العلم وتعزيز الحياة الثقافية. يختتم البحث بتوصيات لتعزيز دراسة الأرشيفات وتوثيق التراث العلمي الجزائري وإجراء دراسات مقارنة بين الحواضر العلمية، مؤكداً على أهمية هذا الإرث في فهم الهوية الثقافية والعلمية للجزائر ودورها في إثراء التراث الإسلامي.

Kendi Kaynakları Işığında İbâdiyye’nin Rü’yetullah Konusundaki Görüşleri - Yoldaş, Mehmet Hanifi (Düzce İlahiyat Dergisi, 2025)
İbâdiyye, İslâm tarihinde ortaya çıkan ilk mezheplerden olan Hâricîlerin alt fırkalarından biri olarak kabul edilmektedir. İbâdîler; mezheplerinin (kendi ifadeleriyle) teşekkül ettiği İslâm tarihinin erken dönemlerinden itibaren imamlarının, liderlerinin ve İbâdî cemaatinin İslâm’ı doğru anlamak ve yaşamak için büyük gayret sarf ettiklerini ve dönemin siyasi atmosferinden ötürü büyük bedeller ödediklerini kendi kaynaklarında anlatmaktadırlar. Bununla birlikte ilmî faaliyetlerden ve telif çalışmalarından geri kalmadıkları; insanlara İslâm’ı anlatma, tebliğ ve davet faaliyetlerine büyük önem verdikleri de dile getirdikleri hususlardandır. İbâdîler, İslâm’ın usûlu’d-dîn konuları başta olmak üzere birçok meselede ciddi bir ilmî birikim ortaya koymuşlardır. İbâdî âlimler, tarihsel süreç içerisinde ilmî faaliyetler çerçevesinde birçok telif ve kitap kaleme alarak görüşlerinin sistematik hale gelmesini ve nesilden nesile aktarımını sağlamışlardır. Bu fırka müntesipleri, yaşadıkları dönemde münazara ortamlarında konuşulan ve tartışılan meseleler hakkında düşüncelerini ve görüşlerini ifade etmekten geri durmamışlardır. İbâdî âlimlerin ilmî faaliyetlerini incelediğimizde hatırı sayılır bir İbâdî literatürüyle karşılaşmaktayız. Onların fikir beyan ettikleri konulardan biri de rü’yetullah meselesidir. Bu mesele, kelâmî bir konu olarak hicrî ikinci yüzyılda İslâm toplumunun gündemini meşgul etmeye başlamıştır. Rü’yetullah konusu, İbâdî ilim erbaplarınca, sahip oldukları tevhid ve sıfatlar konusundaki düşünceleri bağlamında ele alınmış ve konu hakkındaki ayetlerle Hz. Peygamber’den nakledilen hadisleri de görüşlerini doğrulatma adına yoruma tabi tutmuşlardır. Ayetlerden anlam çıkarma adına Arapça dil kurallarını da göz önünde tutmuşlardır. Çalışmamızda bu hususları dikkate alarak İbâdiyye’nin konuyu ele alma yöntemini, kullandıkları metodu ve yaptıkları değerlendirmeleri inceleyeceğiz. İbâdiyye’nin rü’yetullah konusundaki görüşlerini İbâdî müelliflerin ve âlimlerinin eserleri ekseninde ortaya koymaya çalışacağız. Çalışmamızın sınırlarını dikkate alarak konu hakkında diğer mezheplerin fikirlerine yer vermeyeceğiz.

İbâdî Düşüncede Emir bi’l-Ma‘rûf Nehiy ani’l-Münker İlkesinin Kullanım Alanı ve Bu İlkenin Pratiklerine Dair Bir İnceleme - Yoldaş, Mehmet Hanifi (Kader, 2025)
İslâm, kişinin Allah Teâlâ’nın rızasına uygun bir hayat yaşaması için hem bireysel hem de toplumsal yaşamda uyması gereken çeşitli emir ve yasaklar koymuştur. Bu emir ve yasakların varlık sebebi insanoğlunun dünya hayatında kimseye zarar vermeden ve kimseden zarar görmeden bir ömür sürmesi içindir. Bu durumu teminat altına alan ilke ise insanların maslahatı için farz kılınmış olan emir bi’l-ma‘rûf nehiy ani’l-münker esasıdır. Bu ilkenin gayesi; İslâm toplumunun Kur’an ve sünnetin ahkâmına uygun erdemli, barış ve sükûn içinde hayatını sürdüren bir ümmet olmasını sağlamaktır. Hicrî birinci yüzyılın sonuna doğru başlayan Müslümanlar arasındaki gruplaşmaların zamanla fırkalaşma hareketine dönmesiyle birçok itikadî ve siyasî mezhep teşekkül etti. Bu mezheplerden biri olan İbâdiyye; İslam ümmeti içerisinde varlığını günümüze kadar devam ettiren itikadî oluşumlardan biridir. İbâdîler, Hâricîlerin günümüzdeki devamı olarak kabul edilmekte ve itidalli fikirlere sahip olmakla nitelendirilmektedirler. İbâdiyye; ilk dönem kurucu liderlerinin imametleri zamanından itibaren fikirlerinin ekolleşmesi ve farklı beldelerde mezhebî görüşlerinin yayılması için davet çalışmalarını sistematik şekilde sürdürdü. İbâdîler, mezhebi görüşleri doğrultusunda bir İslâm toplumu meydana getirme ve devletleşme çalışmalarının istenilen neticeyi getirmesi için tarihsel süreçte çeşitli kurumlar ve nizamlar/sistemler teşekkül ettirdiler. Tüm bu çalışmaların nihaî gayesi insanların yaşamlarında ma‘rûfun artması ve münkerin kademeli olarak azalması ile asr-ı saadet dönemine benzer bir İslâm toplumunu vücuda getirme ülküsüdür. Bireyin değişiminin beraberinde toplumsal dönüşümü getireceği gerçeğini dikkate alan İbâdîler, toplum hayatını tanzim edecek ilkelerin en önemlisi olarak adalet esasını öne çıkardılar. Onlara göre adalet ilkesinin temelini ise emir bi’l-ma‘rûf nehiy ani’l-münker esası oluşturmaktadır. İbâdiyye, tarihi süreç içerisinde toplum hayatını tanzim etmede İslam’ın en önemli ilkesi olarak kabul edilen emir bi’l-ma‘rûf nehiy ani’l-münker esasının tatbiki için birçok uygulama geliştirdi ve çeşitli pratikler ortaya koydu. Emir bi’l-ma‘rûf nehiy ani’l-münker ilkesinin her bir Müslümana gücü oranında farz olduğu düşüncesine sahip olan İbâdîlerin bu ilkeyi uygulama adına yaptıkları çalışmalar ve pratikler dindar bir toplum ve dindar bir nesil inşa etmede önemli kilometre taşları olarak kabul edilir. Makalemizde İslâm dünyasının farklı bir coğrafyasında varlığını devam ettiren İbâdî Müslümanların kendi mezhebi görüşlerini yaymada, toplumsal hayatı tanzim etmede ve İslâm’ın hayata hâkim olmasında bu ilkenin pratiğe aktarılması adına yapılan uygulamaları ve işlevlerini ortaya koymaya gayret edeceğiz. Araştırmamızda İbâdî müellif ve âlimlerin eserleri başvuracağımız öncelikli kaynaklarımızdır.

İbâzîlere Göre Sahâbî Kavlinin Hücciyeti - Kağanarslan, Yusuf (Mesned İlahiyat Araştırmaları Dergisi, 2025)
Bu çalışma, İslâm hukukunun tali delilleri arasında yer alan sahâbî kavlinin İbâzî mezhebi açısından hücciyetini incelemektedir. Sahâbî kavli, İslâm dünyasında özellikle usûl-i fıkıh bağlamında delil olma niteliği tartışılan bir meseledir. Sünnî mezheplerin sahâbî görüşüne dair yaklaşımı bilinse de Hicrî 1. asırda ortaya çıkan ve Haricî kökenli olduğu ileri sürülen İbâzî mezhebinin bu konudaki görüşleri yeterince tanınmamaktadır. Çalışma, İbâzîlerin sahâbî kavline yaklaşımı yanında, sahâbeye karşı genel tutumları ve sahâbenin adaleti hakkındaki görüşlerini de ele almakta, özellikle sahâbe hakkındaki olumsuz yaklaşımlarına dair iddiaların doğruluğunu kendi kaynakları ışığında ortaya koymayı amaçlamaktadır. İbâzî mezhebi, Abdullah b. İbâz’a nispet edilmekle birlikte, mezhebin esas kurucusu olarak Câbir b. Zeyd kabul edilmektedir. İbâzîler, sahâbeye yönelik yaklaşımlarında velâ (dostluk) ve berâ (buğz) ilkelerini esas alır. Bu ilkeler çerçevesinde, sahâbenin davranışlarını zâhirî amellerine göre değerlendirirler; sahâbeden hak üzere olanlara velâ, yanlış davranış sergileyenlere ise berâ uygularlar. Özellikle fitne olarak adlandırılan Cemel, Sıffîn ve Nehrevân savaşlarında hata ettiklerine inandıkları bazı sahâbîlerden teberri etmişlerdir. Ancak bu tutumları, sahâbenin genel faziletini inkâr ettikleri anlamına gelmemektedir. İbâzîler, sahâbenin adaletini fitne öncesi ve sonrası olmak üzere iki dönem üzerinden değerlendirmişlerdir. Fitne öncesi dönemde fıskı açıkça bilinenler dışındaki sahâbenin âdil olduğunu kabul ederlerken fitne sonrası dönemde ise adaletleri bilinenler hariç tüm sahâbîlerin adaletinin araştırılması gerektiğini savunmuşlardır. Bu bakımdan Ehl-i Sünnet’ten ayrılırlar; çünkü Sünnî anlayış sahâbenin tamamını adil kabul eder. Sahâbî kavlinin hücciyeti konusunda da İbâzîlerin yaklaşımı dikkat çekicidir. Mezhebin ilk imamı Câbir b. Zeyd, fetva verirken Kur’ân, sünnet, icmâ ve sahâbî görüşüne başvurmuş; hocası İbn Abbas’ın görüşlerine özel bir önem atfetmiştir. Ancak onun sahâbî görüşünü kesin bağlayıcı bir delil olarak kabul etmediği, kendi görüşünü de ifade ettiği görülmektedir. Mezhebin ikinci imamı Ebû Ubeyde’nin ise sahâbî kavline yaklaşımı daha kritiktir. Ona göre, sahâbî görüşü doğru bulunursa kabul edilir; aksi takdirde amel edilmez. İbâzî kaynaklarında da bu yaklaşımın izleri görülür. Özellikle sahâbe arasında ihtilaf bulunan meselelerde, sahâbî kavli bağlayıcı bir delil sayılmamış; sahâbî görüşleri kendi içinde değerlendirilmiştir. İbâzîler, sahâbî görüşünün mutlak olarak hüccet olmadığını, sahâbenin masum olmadığını ve hata yapabileceklerini savunmuşlardır. Onlara göre sahâbî kavli, diğer müctehidlerin görüşlerinden farksızdır ve bağlayıcılığı yoktur. Sahâbe döneminde sahâbîlerin dahi birbirlerine muhalefet ettikleri gerçeğinden hareketle sahâbî kavlinin sonraki nesiller için de bağlayıcı olmadığı sonucuna varmışlardır. Ayrıca İbâzîler, kendi mezheplerine atfedilen sahâbenin tekfirine dair iddiaları reddederler. Onlara göre, küfür kelimesi şirk anlamında kullanılmaz; daha çok nimet küfrü (nankörlük) anlamında kullanılır. Bu sebeple ehl-i kıbleyi dinden çıkarma anlamında tekfir etmediklerini özellikle belirtirler. İbâzîlerin sahâbeye yönelik genel tutumu, fitne sonrası olaylara bakışları ve sahâbî kavlinin hücciyeti konusundaki değerlendirmeleri, onların Şîa ve Ehl-i Sünnet’ten özgün bir yaklaşıma sahip olduklarını göstermektedir. Onlar; Hz. Peygamber, Hz. Ebubekir ve Hz. Ömer dönemini ideal dönem olarak görüp o döneme dönüş çağrısında bulunmuşlardır. Fitne sonrası dönemde ise velâ ve berâ ilkeleri doğrultusunda sahâbe değerlendirilmiş, hatalı bulunanlardan teberri edilmiş, sahih görülen görüşler benimsenmiştir. Sonuç olarak İbâzîler, sahâbî kavlinin bağlayıcı bir delil olmadığını, sahâbînin ictihadî görüşlerinin diğer müctehidlerin görüşleriyle aynı statüde değerlendirileceğini savunmuşlardır. Sahâbenin adaletine dair tutumları ve sahâbe kavline yaklaşımları, tarihsel ve itikadî bağlamda özgün bir çizgi ortaya koymaktadır.

Avtebî (ö. 511/1118), el-İbâne’si ve Arap Diline Katkıları - Özbey, Lütfi (Ordu İlahiyat, 2025)
Bu çalışma Ebü’l-Münzir el-Avtebî’nin hayatı, el-İbâne adlı eseri ve bu eser aracılığıyla Arap diline katkılarını ele almaktadır. Avtebî, Umman’ın önemli şehirlerinden biri kabul edilen Suhâr kentinin Avteb kasabasında doğmuştur. Müellifin yaşadığı dönemde Umman ve çevresi çeşitli siyasî karışıklıklara sahne olduğundan birçok kitap ve kütüphane tahrip edilmiş, bu nedenle o döneme ait çoğu bilgi ve belge kaybolmuştur. Avtebî’nin de tam olarak ne zaman dünyaya geldiği hususu tarih bilimciler arasında tartışmalı bir konu olmuştur. Çocukluğu, ders aldığı hocaları, yetiştirdiği talebeleri gibi konularda yeterli bilgi bulunmayan Avtebî, İbâzî fıkhı ve Arap soy bilimi gibi bilim dallarında önemli eserler telif etmiştir. Özellikle İbâzî fıkhı alanında kaleme aldığı yirmi üç ciltlik eseri, bu mezhebin ana kaynaklarından biri olarak kabul edilmiştir. Bu ilimlerin yanı sıra Avtebî, kısıtlı imkanlarına rağmen Arap dil bilimi alanında da yaşadığı dönemin en önemli ilmi şahsiyetlerinden biri olmayı başarmıştır. Avtebî’nin el-İbâne adlı eseri, hicrî beşinci asırda Arap dili alanında kaleme alınmış içeriğinin zenginliği ve eserin hacmi bakımından en önde gelen eserlerden biridir. Eser; ses bilimi, sözcük bilimi, cümle bilimi belagat, darb-ı mesel, şiir gibi konuların yanı sıra tefsir, hadis ve kıraat gibi alanları da ihtiva etmektedir. Avtebî, el-İbâne’de dil konularını farklı âlimlerin görüşlerini zikrederek detaylı bir şekilde ele almaktadır. Anlamını tespit sadedinde zikretmiş olduğu kelimeleri, farklı Arap şiirleri ile de desteklemektedir. Avtebî el-İbâne’de, öncelikle Kur’an ve hadisle istişhâd etmenin yanı sıra Arap şiirleri ve mesellerden de yararlanmaktadır. Eserini alfabetik sıraya göre kaleme almak sureti ile okuyucuya o günün şartlarında ciddi bir kullanım kolaylığı sağlamıştır. Sözcükler ele alınırken yerine göre ses bilim, sözcük bilim, cümle bilim, kıraat farklılıkları ve belagat incelikleri tespit edilerek bu hususlara dikkat çekilmiştir. Avtebî, son derece açık ve açıklayıcı olma vasfına istinaden eserini el-İbâne şeklinde isimlendirmiştir. Eserde kelimelerin harf sırasına göre ele alınıp incelenmesi, el-İbâne’nin ansiklopedi tarzında bir eser mi yoksa sözlük amacı ile hazırlanmış bir eser mi olduğu sorusunu meydana getirmiş ve bu husus araştırmacılar tarafından tartışılagelmiştir. Avtebî’nin Arap dili alanında el-İbâne dışında yalnızca adının tespit edilebildiği birkaç eseri daha vardır. Bu eserlerin birçoğu, müellifin mevcut eserlerinde isimlerini zikretmesi sebebi ile yalnızca adları tespit edilmiş ancak bu eserlerin yazmalarına henüz ulaşılamamıştır. Arap dili alanında kaleme aldığı eserlerin arasında günümüzde yalnızca el-İbâne adlı eseri elimize ulaştığından Avtebî’nin Arap dili alanına yaptığı katkılar yalnızca bu eser özelinde incelenmiştir. Avtebî ve el-İbâne’si hakkında başta Umman olmak üzere çeşitli Arap ülkelerinde çeşitli çalışmalar yapılmıştır. Ancak Türkiye’de bizim çalışmamız dışında herhangi bir bilimsel çalışma yapılmamış olması bu çalışmayı alana katkısı anlamında daha önemli hale getirmektedir. Bu Avtebî’nin hem el-İbâne adlı eseri hem de diğer çalışmaları ile kendi el yazısıyla notlar düşerek üzerinde çalıştığı eserlerin kodikolojik açıdan yeterince incelenmemiş olması, onun yaşadığı dönemin kesin olarak tespit edilmesini zorlaştırmakta ve bu husustaki belirsizliği sürdürmektedir. Bu bağlamda, Avtebî’nin döneminin daha sağlıklı şekilde tayin edilebilmesi için Avtebî’ye ait yazma eserler üzerinde kodikolojik inceleme yapılmasını elzem kılmaktadır.

Kalhâtî’nin el-Keşf ve’l-Beyân Adlı Eseri Bağlamında İmâmet Eleştirisi - Kalyoncu, Zübeyde (Âsâr Akademik Dinî Araştırmalar Dergisi, 2025)
Bir ilim dalında gerçekleştirilecek araştırmalar ilk aşamada o disiplin ile ilgili temel klasik kaynakları üzerinden yürütülür. Mezhepler tarihi literatüründe, çoğunlukla muhaliflerinin görüşlerini çürütmek gayesiyle telif edilen Ehl-i sünnet kaynakların yanında diğer fırka mensuplarının eserleri de büyük öneme haizdir. Çünkü mezhep tasnifi ve değerlendirmelerini tek yönlü okumak objektif yorumlama için yeterli olmamaktadır. Muhaliflerine yönelik şiddeti ön planda tutan ve hiç düşünmeden kan döken Hâricî anlayışın bir alt kolu olarak kabul edilen İbâzıyye fırkası ile ilgili ana kaynaklarda yapılan tespitler araştırma konusudur ve tartışmaya açıktır. Çünkü kendilerini Hâricî olarak kabul etmeyen, ılımlı görüş ve davet yöntemleri ile varlıklarını günümüze kadar sürdüren İbâzıyye doktrininin ilk olarak kendi kaynaklarından okunması gerekmektedir. Aynı zamanda İbâzî fırak eserlerinde yer verilen başta Hâricîler ve Şîa olmak üzere diğer bid‘at ehli fırkalara yönelik bakış açısının değerlendirilmesi de yapılmalıdır. Fırkalara yönelik, farklı teolojik yaklaşımların ve durum tespitlerinin nasıl olduğunun bilinmesi klasik kaynaklardaki bilgilerin kritiğini yapma hususunda katkı sağlayacaktır. Bu bağlamda makalemizin amacı, Umanlı İbâzî müellif olan Ebû Abdillâh Muhammed b. Saîd el-Ezdî el-Kalhâtî’nin (VI./XII. yüzyıl [?]) eseri “el-Keşf ve’l-beyân” üzerinden, Şîa mezhebine yaklaşımını tespit etmeye çalışmaktır. İbâzıyye ve Şîa fırkaları ortaya çıktıkları ilk evrede Hz. Ali’nin taraftarı olmaları hasebiyle aynı safta iken zamanla siyasî, ekonomik ve sosyal sâiklerin etkisiyle birbirine muhalif iki fırka olmuşlardır. Aralarında temel ihtilaf başlığı ise ilk olarak imâmet bahsidir denilebilir. Kalhâtî’nin eseri el-Keşf üzerinden Şîa'ya yaptığı eleştiriler mezhep taassubunun izlerini taşıyor olsa da büyük oranda Ehl-i sünnet kaynaklarında yer alan bilgiler ile benzerlik göstermesi dikkat çekicidir. Kalhâtî, imâmet merkezli olarak yaptığı eleştirilerini hem aklî hem de naklî deliller ile temellendirmeye çalışmış ancak hadis nakli konusunda çoğunlukla fırkasının rivayet zincirini kullanmıştır. Haricî zihniyetin en ılımlı kolu olarak kabul edilen İbâziyye mezhebinin mensubu olan Kalhâtî’nin eseri, Şîa’ya yöneltilen eleştiriler temelinde İslam mezhepleri tarihi açısından alana katkı sağlayacak bilgiler ve yaklaşımlar içermektedir. Öne Çıkanlar • Bu çalışmada İbâzıyye fırkasının bir mensubu olan Kalhâtî’nin Şîa’ya dair görüşleri incelenmektedir. • Bid‘at ehli bir fırkanın diğer bir bid‘at ehli fırkaya yönelik eleştirilerinde sünnî kaynaklar ile benzerlik söz konusu olabilmektedir. • İki fırka arasında temel eleştiri başlığı imâmet konusunda yoğunlaşmaktadır. • Kalhâtî, Şîa’nın ilk iki halifeye yönelik eleştirilerini red etmektedir. • Kalhâtî, Hz. Ali’nin vesayet yoluyla imâmetinin doğru olmadığını beyan etmektedir. Atıf Bilgisi Kalyoncu, Zübeyde. “Kalhâtî’nin el-Keşf ve’l-Beyân Adlı Eseri Bağlamında İmâmet Eleştirisi”. ÂSÂR Akademik Dinî Araştırmalar Dergisi 1/5 (Ekim 2025), 32-63. https://doi.org/10.5281/zenodo.17276501

İbazî el-Kindî en-Nizvânî ve el-Cevheru’l-muktasar Adlı Eseri Üzerine - Yildiz, Metin (Van İlahiyat Dergisi, 2025)
İslâm düşüncesinde kronolojik olarak teşekkül eden ilk kelâm ekolleri arasında yer alan Hariciliğin İbâziyye kolu birçok konuyu diğer Haricî fırkalardan farklı ve daha ılımlı bir şekilde yorumlayarak günümüze kadar varlığını koruyabilmiş tek fırkadır. İbâziyye’nin ismini kendisinden aldığı Abdullah b. İbâz’dan itibaren birçok kelâm âliminin eserleri günümüze kadar gelmiştir. Bu çalışmada araştırma konusu edindiğimiz el-Kindî en-Nizvânî (ö. 557/1162) günümüz Uman sınırları içerisinde yer alan Nizvâ şehrinde doğmuş ve yaşamış İbâzî bir âlimdir. Erken yaşta ilim hayatına başlayan el-Kindî en-Nizvânî daha yirmi beş yaşlarındayken hocasına reddiye yazacak seviyeye ulaşmıştır. İlim hayatına etkin bir şekilde katıldığı gibi dönemin siyasî ortamında da bilfiil yer almıştır. Eserleri günümüze kadar ulaşan erken dönem İbâzî kelâmcıları arasında yer alan el-Kindî en-Nizvânî, fıkıh, usûlü’l-fıkh, tarih ve fırak gibi alanlarda mâhir olduğu gibi dakîku’l-kelâm ve celîlu’l-kelâm alanlarında da velûd ve mâhir bir âlimdir. Onun el-Cevheru’l-muktasar ‘ı İbâziyye’de kelâmın dakîk konularını sistematik bir şekilde içeren ve günümüze kadar gelen erken dönem özgün eserlerden birisidir. el-Kindî en-Nizvânî bu eserinde âlem, âlemin unsurları olan cevher, araz ve cisim gibi dakîku’l-kelâm konularını detaylı bir şekilde ele almıştır. Yine bu eserinde iman, İslâm, şirk, küfür, tekfir, tevhid, dinin esasları, Kur’an’ın mu’cizevî özelliği, insan fiilleri, nübüvvet, Şiâ’nın imâmet teorisine yönelik eleştiriler, Nehrevân ehlinin durumu, kime Ehl-i sünnet isminin verileceği, İbâziyye’nin din anlayışını takip edenlerin ahiretteki durumları vb. celîlü’l-kelâm konularına da değinmektedir. Çalışmamızda erken dönem İbâzî kelâmcılarından el-Kindî en-Nizvânî ve onun el-Cevheru’l-muktasar adlı eserinin İbâziyye’deki yeri ve bilhassa Kelâm ilmindeki önemi ele alınacaktır. Bu çalışmadaki amacımız İslâm’ın erken döneminde yaşamış ve genişçe bir müellefatı günümüze ulaşmış el-Kindî en-Nizvânînn İbâziyye’deki konumunu ve onun el-Cevheru’l-muktasar adlı eserinin başta dakîku’l-kelâm olmak üzere celîlu’l-kelâm’daki yerini ortaya koymaktır. İbâziyye’nin çağdaş araştırmalarda Mu’tezile, Eş’ariyye, Mâtüridiyye ve Şia ekollerine nazaran yeterli derecede çalışılmadığını söylemek mümkündür. Bu araştırmada el-Kindî en-Nizvânî ve onun el-Cevheru’l-muktasar adlı eserinin önemini ortaya koyularak bu alana bir katkıda bulunulmaya çalışılacaktır. Bu yönüyle bu çalışmanın İbâziyye ve bilhassa el-Kindî en-Nizvânî ve onun el-Cevheru’l-muktasar adlı eseri hakkında yeni çalışmaların yapılmasına katkı sunması umulmaktadır.

İbâdîliğin Kuzey Afrika’ya Yayılışı: Tarihsel Süreç ve Belirleyici Faktörler - Borsbuğa, Coşkun; Ekinci, Mustafa (Ondokuz Mayıs Üniversitesi İlahiyat Fakültesi Dergisi, 2025)
Bu araştırma makalesi, İbâdîliğin Kuzey Afrika’ya (Mağrib) yayılma sürecini tarihsel, sosyo-politik ve mezhepsel dinamikler çerçevesinde incelemektedir. Çalışmanın temel amacı, İbâdîliğin Mağrib coğrafyasında hangi tarihsel şartlar altında benimsendiğini ve nasıl kalıcı bir yapı hâline geldiğini ortaya koymaktır. Bu bağlamda, İslam mezhepleri tarihi ilmi perspektifi dikkate alınarak İbâdî ve İbâdî olmayan kaynaklar karşılaştırmalı bir yöntemle analiz edilmiştir. Emevî yönetiminin bölgede uyguladığı baskıcı politikalar, Arap olmayan unsurlara karşı ayrımcı tutumu ve merkezi otoritenin toplumsal adaletsizlikleri artıran uygulamaları, Berberî kabileleri arasında ciddi huzursuzluklara yol açmıştır. Aynı dönemde bölgede etkili olan Hâricî Sufrî hareketinin aşırı ve şiddet yanlısı tutumu, Berberîlerin Sufrîlere nazaran daha mutedil bir dini anlayışa yönelmelerine zemin hazırlamıştır. Bu şartlar altında İbâdîlik, özellikle barışçıl yaklaşımı, ahlakî bütünlüğü önceleyen söylemi ve toplumsal düzeni gözeten siyasal söylemi bölgedeki Berberî kabileler nezdinde önemli bir karşılık bulmuştur. İbâdîliğin Mağrib’de yayılmasında etkili olan bir diğer önemli unsur ise Ebû Ubeyde Müslim öncülüğünde Hameletü’l-ilm teşkilatının örgütlü ve sistematik çalışmalarıdır. Bu yapı, mezhebin öğretilerini hem sözlü hem yazılı yollarla taşraya ulaştırmada ve çeşitli kabilelerle mezhebin ilkelerini buluşturmada etkili bir aracı rolü üstlenmiştir. Ayrıca, İbâdîler arasında yaygın olan gizlilik esasına dayalı eğitim ve öğretim yöntemleri, hac dönemlerinde hacılara yönelik ilmî faaliyetleri ve İslam coğrafyasının birçok yerindeki ticarî faaliyetleri mezhebin baskı dönemlerinde varlığını sürdürmesini sağlamıştır.

İbâdî Gelenekte Hadis Şerhçiliği ve Yorum - Özdemir, Ahmet (Mesned İlahiyat Araştırmaları Dergisi, 2025)
Hâricîler, hicri birinci asırda özellikle iman ve küfür gibi daha çok itikâd ile ilgili tartışmalar neticesinde birçok farklı kola ayrılmış ve zaman içerisinde İbâdiyye hariç söz konusu gruplar dağılıp yok olmuşlardır. İbâdiyye, Hâricîlerin özellikle diğer Müslümanlar hakkındaki sert görüşlerine katılmayarak onlardan ayrılmış ve Abdullâh b. İbâd (öl. 86/705) liderliğinde teşkilatlanmış mutedil bir fırkadır. Erken dönemde teşekkülünü tamamlayan İbâdiyye, Emevî ve Abbasîlerle mücadeleleri neticesinde kendi devletleri olan Rüstemîler’i kurmuş ve günümüzde ‘Umân Sultanlığı’nın yanı sıra Kuzey Afrika’daki birçok ülkede çok sayıda müntesibi bulunan bir mezheptir. İbâdiyye, Hâriciyye’nin diğer kollarının aksine eserleri günümüze ulaşan tek fırkadır. Mezhebin önemli temsilcilerinden olan Câbir b. Zeyd (öl. 93/711-12), Ebû Ubeyde (öl. 145/762) ve Rabî‘ b. Habîb (öl. 175/791) gibi muhaddisler, hicri birinci ve ikinci asırda hadis tedvin ve tasnif faaliyetine katkıda bulunmuşlar ve söz konusu ilmî faaliyetler neticesinde hadis edebiyatının ilk ürünleri ortaya çıkmıştır. İlk hadis musannefâtından biri Rabî‘ b. Habîb’in el-Câmiu’s-Sahîh adlı eseri, günümüze kadar ulaşmıştır. İmam Mâlik (öl. 179/795) ile çağdaş olan Rabî‘ b. Habîb’in el-Câmiu’s-Sahîh veya Müs-nedu’r-Rabî‘ olarak da bilinen eseri, İbâdiyye nezdinde Kur’ân’dan sonra en muteber dinî kitap olarak kabul edilmiş ve günümüzde birçok baskısı yapılmıştır. Hadis şerhi bakımından İbâdî kaynakların son derece sınırlı olduğunu belirtmek gerekir. İbâdiyye’nin ana hadis kaynağı olan Rabî‘ b. Habîb’in el-Câmiu’s-Sahîh’i üzerine iki önemli şerh yazılmıştır. Birincisi Ebû Sitte diğeri ise Nureddîn es-Sâlimî tarafından kaleme alınmıştır. Şu an elimizde matbu olan İbâdî ilk hadis şerh çalışması, hicri 1087’de vefat eden Ebû Sitte’nin Rabî‘in el-Câmiu’s-Sahîh’i üzerine yazdığı şerhtir. Diğer bir şerh ise 1913’te vefat eden Nureddîn es-Sâlimî’nin yine aynı eser üzerine yazmış olduğu çalışmadır. Bunun dışında İbâdî âlimlerce hadis alanında yazılmış başka şerh çalışması varsa da ya kütüphanelerde gün yüzüne çıkarılmayı bekleyen yazma halindedir ya da yukarıda söz ettiğimiz iki şerhin muhtasarıdır. Dolayısıyla İbâdî âlimler tarafından yazılmış olan hadis şerh çalışmaları hem sınırlı hem de geç dönemlere aittir. Biz de çalışmamızı bu iki hadis şerhi bağlamında gerçekleştirdik. İki şerhten hareketle İbâdiyye mezhebinin hadis şerh metodolojisini tespit etmeye çalışacağız. Yapılacak çalışma neticesinde şu soruların cevaplarını bulacağımızı ümit ediyoruz: İbâdiyye, hadis şerhi alanında ne tür kaynaklara sahiptir ve söz konusu eserlerin özellikleri nelerdir? Hadis şerhlerinde ne tür kaynaklara müracaat etmişlerdir? Şerhlerinde Sünnî kaynaklardan ne derece yararlanmışlardır? Hadisleri anlama ve yorumlamada ne tür bir usul geliştirmişlerdir? Hadis şerhlerinde mezhepsel bakışın tesiri ne orandadır? Özellikle İbâdiyye fırkasının temel ilkeleriyle alakalı konularda söz konusu rivayetlere ne şekilde yaklaşılmıştır? İbâdî ile Sünnî şârihlerin yöntemleri ne derece benzeşmektedir? Çalışmanın neticesinde aslında İbâdî şerh geleneğinin, Sünnî gelenekten pek farklı olmadığı görülmüştür. Elbette şerh anlayışlarına kendi bakış açılarını yansıtmışlardır. Ancak bunun doğal karşılanması gerektiği açıktır. Zira bugün Sünnî gelenek içerisinde dahi Hanefî, Malikî, Şâfiî, Hanbelî, Zâhirî gibi farklı renklere sahip şerh anlayışları görmek mümkündür. Zaman içerisinde mezheplerin birbirinden etkilendiklerini ve İbâdî şârihlerin özellikle Sünnî gelenekten ciddi anlamda etkilendiğini söylemek gerekir. Günümüzde hadis ve sünnetin anlaşılması ve bu alanda oluşturulan usul ve metodoloji noktasında özellikle Sünnî geleneğin tesirinde kalındığı bilinen bir husustur. Kanaatimizce Sünnî geleneğin tesirinde olan usule, İbâdî geleneği de eklemek gerekmektedir. Böylece hadis ve sünnete bakış açımız daha da zenginleşmiş olacaktır. Ayrıca mezheplerinin Kur’ân ve sünnet merkezli olduğunu belirten, Kütüb-i Sitte başta olmak üzere Ehl-i Sünnet’e ait önemli hadis kaynaklarına müracaat eden ve gerektiğinde Sünnî dört fıkhî mezhebin görüşlerine de başvuran bir mezhep de ötekileştirilmemiş olacaktır. Zira ümmetin ihtilaflarda kaybolmaya değil genel ilke ve prensipler etrafında birlik olmaya daha fazla ihtiyacı vardır.

Bi̇r Tâbi̇î'ni̇n Si̇yasi̇ Konumu: İkri̇me El-Berberî Ve Hâri̇cîli̇kle İli̇şki̇si̇ - Vuran, Hasan (Kilis 7 Aralık Üniversitesi İlahiyat Fakültesi Dergisi, 2025)
İslam tarihinin erken dönemleri, siyasi otorite, dinî meşruiyet ve ümmet birliği meselelerinin iç içe geçtiği karmaşık bir süreç olarak dikkati çeker. Hz. Osmân’ın şehadetiyle başlayan ve Hz. Alî döneminde derinleşerek Cemel ile Sıffîn gibi büyük iç çatışmalara dönüşen siyasi krizler, sadece bir iktidar mücadelesi değil aynı zamanda İslam toplumunun siyasi düşüncesini derinden etkileyen hadiselerdir. Bu hadiseler siyasi meşruiyet, imamet anlayışı ve dinî birlik arayışı açısından da kalıcı etkiler bırakmıştır. Hz. Peygamber’in (s.a.s.) vefatından sonraki süreçte sahabe ve onlardan sonraki nesil olan tâbiîn, yeni karşılaştıkları sorunlara ürettikleri çözümlerde yahut gerçekleşen sosyal ve siyasi olayları değerlendirmede çeşitli içtihatlar yaparak farklı sonuçlara varmışlardır. İçtihatlardaki çeşitlenme kimi zaman itikatla ya da muamelatla alakalı olmuş kimi zaman da siyasetle ilişkili meselelerde tezahür etmiştir. Siyaset anlayışındaki ayrışmalarda sahabe ve tâbiînden bazıları iktidarın yanında yer alırken bazıları da muhalif grupların içerisinde bulunmuş bazen de bu gruplara liderlik etmişlerdir. Bu bağlamda, İkrime el-Berberî gibi şahsiyetler, hem ilmî faaliyetleri hem de siyasi duruşlarıyla dikkat çeken figürler arasında yer almıştır. Tefsir, hadis ve meğâzî alanlarında derin bilgiye sahip olan İkrime, aynı zamanda Hâricî hareketle ilişkilendirilmiş olması sebebiyle tarihsel kaynaklarda tartışmalı bir konuma sahiptir. Hâricîliğin yayılmasında bazı âlim ve davetçilerin etkili olduğu, bazı isimlerin bu hareketle doğrudan ya da dolaylı irtibat kurduğu yönünde rivayetler de tarih literatüründe yer almaktadır. Bu isimlerden biri olan İkrime el-Berberî, tâbiîn neslinin önde gelen âlimlerinden biri olarak kabul edilmekle birlikte, hakkında Hâricî olduğuna dair çeşitli iddialar ileri sürülmüştür. İbn Abbâs’ın mevlası ve önde gelen talebesi olarak tanınan İkrime, özellikle tefsir, hadis ve meğâzî alanlarında büyük bir birikime sahip olmuş ve bu yönüyle İslami ilimlerin gelişiminde önemli bir yer edinmiştir. Ancak onun siyasi tavırları ve itikadi duruşuna dair klasik rical ve tarih literatüründe farklı görüşlerin yer alması, İkrime’yi tartışmalı bir şahsiyet hâline getirmiştir. Bu çalışma, İkrime el-Berberî’nin ilmî kişiliği ile ona nispet edilen siyasi aidiyet arasındaki ilişkiyi erken dönem İslam tarihinin şartları içinde yeniden değerlendirmeyi amaçlamaktadır. Çalışmanın çıkış noktası, İkrime’nin yalnızca bir hadis ve tefsir âlimi olarak değil, aynı zamanda dönemin siyasi gerilimleriyle temas hâlinde bir şahsiyet olarak anlaşılabileceği varsayımıdır. Bu amaçla, başta İbn Sâd, Taberî, Zehebî ve İbn Hacer gibi klasik kaynaklar ile modern araştırmalar birlikte incelenmiştir. Ayrıca karşılaştırmalı okuma için Ebû Zekeriyâ el-Vercelânî ve Dercînî gibi İbâzî müelliflerin eserlerine de müracaat edilmiştir. Tarihsel bağlam analizi ve karşılaştırmalı biyografi yöntemleri kullanılarak İkrime’nin faaliyetleri ve Hâricîlik iddialarının dayandığı rivayetler değerlendirilmiştir. Elde edilen bulgular, İkrime el-Berberî’nin Hâricî görüşleri benimsediğine dair rivayetlerin tarihî bir temele dayandığını ve bu yöndeki nakillerin çeşitli kaynaklarda tekrarlandığını göstermektedir. İkrime’nin Basra’nın önde gelen âlimlerinden biri olması ve hayatının ilerleyen dönemlerinde Horasan, Yemen, Mısır ve Mağrib bölgelerine gitmesi, Hâricîlerin siyasi baskı sebebiyle takip ettiği güzergâhlarla örtüşmektedir. Bu seyahatlerin yalnızca coğrafi değil aynı zamanda fikrî bir yönü bulunduğu anlaşılmaktadır. Nitekim Kuzey Afrika’daki erken dönem Hâricî topluluklarının İkrime’nin görüşlerinden etkilendikleri ve onun bu bölgelerde Hâricî düşüncenin yayılmasına öncülük ettiği aktarılmaktadır. Mağrib halkının büyük kısmının Berberî kökenli olması ve İkrime’nin de aynı etnik kimliğe sahip bulunması, bu etkide önemli bir rol oynamıştır. Kaynaklarda, İkrime’nin Emevî otoritesinden gizlendiği, cenazesine kimsenin katılmadığı ve bu durumun onun yönetimle sorunlu ilişkisine işaret ettiği de belirtilmektedir. Ayrıca Fesevî ve Zehebî gibi müellifler, İkrime’nin bazı ifadelerini ve davranışlarını doğrudan Hâricî karakterde değerlendirmişlerdir. Mamafih İkrime’nin Hâricî muhalefet içerisinde yer alması, onun Hâricîliğin ilerleyen yüzyıllarda sistematik hâle gelen itikadi doktrinlerinin tamamını kabul ettiği anlamına gelmemektedir. Zira İkrime’nin vefatı hicri ikinci yüzyılın başlarına denk gelmekte ve bu dönemde Hâricîlik henüz tam anlamıyla doktriner bir mezhep kimliği kazanmış bulunmamaktadır. Bu sebeple onun Hâricîliği, siyasi bir muhalefet hareketine katılım ve yönetim karşısında siyasi bir duruş olarak değerlendirilebilir. Bu yönüyle araştırma, hem klasik kaynakların yeniden yorumlanması hem de Hâricîlik tanımının siyasi olarak değerlendirilmesi bakımından literatüre özgün bir katkı sunmaktadır.

İbâziyye’nin Ehl-i Sünnet ve’l-Cemâat Eleştirisi: Kalhâtî Örneği - Atalay, Hakan (e-Makalat Mezhep Araştırmaları Dergisi, 2025)
İbâzî âlimlerden Kalhâtî el-Keşf ve’l-beyân adlı eserinde, birçoğu Ehl-i Sünnet çatısı altında kabul gören mezhepleri “Sıfâtiyye”, “Müşebbihe” ve “Haşviyye” gibi isimlendirmeler altında tasnif ederek onları hem itikadî hem de siyasî bağlamda tenkit etmektedir. Bu eleştirilerde sıfatlar, rü’yetullah ve imamet gibi temel meseleler ön plana çıkmakta; bu konular üzerinden söz konusu mezhepler teşbih, tecsîm ve rivayetleri kendi ideolojik kabulleri doğrultusunda tahrif etmekle suçlanmaktadır. Bu tenkitlerin Mu‘tezilî söylemlerle yer yer örtüştüğü görülmektedir. Bu bağlamda söz konusu isimlendirmeler, yalnızca Ehl-i Sünnet’i değil, aynı zamanda literalist eğilimleriyle öne çıkan ve kimi zaman Ehl-i Sünnet dışında kalan zümreleri de kapsayan daha geniş bir eleştiri zeminine işaret etmektedir. Bu açıdan Kalhâtî’nin kullandığı kavramlar, yalnızca teolojik bir değerlendirme değil, aynı zamanda mezhebî kimlik inşasına hizmet eden polemiksel bir dilin ürünüdür. Bu kavramların Ehl-i Sünnet’le birebir özdeşleştirilmesi mümkün olmasa da, Ehl-i Sünnet anlayışını da içine alan genelleyici eleştiri kategorileri oldukları anlaşılmaktadır. Kalhâtî’nin mezhepleri isimlendirme ve tasnif etme biçiminin çoğu zaman muğlaklık içerdiği; bu nedenle kullandığı kavramların kapsamı ile eleştirilerin hedef kitlesi arasında belirgin bir sınır bulunmadığı hususu da bu çalışmada altı çizilen hususlardandır. Bu makale, Kalhâtî örneğinde İbâzîliğin Ehl-i Sünnet’e yönelik eleştirilerini sistematik biçimde ortaya koyarken, bu eleştirilerin hem kelâmî hem de siyasî boyutlarına ışık tutmaktadır.

İbâdî Alîm Ebû Ya’kûb el-Vercelânî’nin ed-Delîl ve’l-Burhân’ı Bağlamında Siyasi Görüşleri - Bilen, Osman; Rençber, Fevzi (e-Makalat Mezhep Araştırmaları Dergisi, 2025)
Bu çalışma, Hâricî fırkaları içerisinde en ılımlı ve sistematik düşünce yapısına sahip kabul edilen İbâdiyye mezhebinin imâmet anlayışını ve siyasal düşüncesini incelemektedir. Araştırmanın konusu, mezhebin itikadî ilkeleri ile imâmet doktrininin, İbâdî düşünür Ebû Ya‘kūb Yûsuf b. İbrâhim el-Vercelânî’nin (ö. 570/1175) ed-Delîl ve’l-Burhân li-Ehli’l-ʿUkūl adlı eseri çerçevesinde değerlendirilmesidir. Çalışmanın kapsamını, İbâdiyye’nin imâmeti veraset yahut tayinden bağımsız olarak cemaatin icmâ ve biatine dayandıran yaklaşımı; dört halife hakkındaki değerlendirmeler; İslâm toplumunun bölünmesine yol açan tarihsel, siyasal ve teolojik faktörlere dair yorumlar; bu süreçte ortaya çıkan temel kavramlara ilişkin tutum; ayrıca müşrikler ve Ehl-i kitapla ilişkilere dair görüşler oluşturmaktadır. Araştırmanın amacı, Vercelânî’nin siyasal ve kelâmî düşüncesinin İbâdiyye mezhebinin genel çizgisi içindeki yerini tespit etmek ve bu düşüncenin mezhebin ana ilkeleriyle uyum düzeyini ortaya koymaktır. Çalışmada nitel yöntem benimsenmiş; Vercelânî’nin eseri başta olmak üzere klasik İbâdî kaynaklar analiz edilmiş, diğer İslâm fırkalarının imâmet anlayışlarıyla karşılaştırmalı bir inceleme yapılmıştır.Araştırmanın sonucunda, Vercelânî’nin düşüncesinde ilk üç halife döneminin örnek alınması gereken ideal bir yönetim modeli olarak görüldüğü; ümmetin parçalanmasının temel nedeninin yöneticilerin hatalı tutumları ve yanlış açıklamaları olarak değerlendirildiği; müşriklere karşı ihtiyatlı ve mesafeli bir yaklaşım benimsendiği tespit edilmiştir. Ayrıca Vercelânî’nin siyasal görüşlerinin genel hatlarıyla İbâdiyye’nin yerleşik siyasal anlayışıyla uyumlu olduğu sonucuna ulaşılmıştır.

Tunus ve Tunus İbâdîleri Üzerine Gezi Notları - Göksün, Ahmet Faruk (e-Makalat Mezhep Araştırmaları Dergisi, 2025)
Bu çalışma, İbâdîlik araştırmaları kapsamında Tunus’a yapılan on günlük ziyaretin gezi notlarından oluşmaktadır. Bu gezi kapsamında başta başkent Tunus olmak üzere Benzert ve Kayrevân şehri ayrıca Tunus İbâdîlerinin merkezi konumunda olan Cerbe adası ziyaret edilmiştir. Bu gezi sadece İbâdîlik araştırmalarına hasredilmemiş, gezi esnasında mezkur bölgelerin tarihi, kültürel ve turistik yerleri ziyaret edilmiş, İbâdî merkezlere gidilmiş ve İbâdî isimler ile görüşmeler yapılmıştır. Bu yazıda zikredilen faaliyetler esnasındaki gözlem ve yorumlar aktarılmış, anlatılanlar resimler ile desteklenmiştir.

منهج أحمد بن حمد الخليلي في تفسير الآية السابعة من سورة آل عمران - Kaya, Hamdi (İlahiyat Akademi, 2025)
دراسة مناهج مفسري المذاهب الإسلامية المعتدلة وربطها بمناهج مفسري أهل السنة لها أهمية كبيرة في معرفة تفكير علماء هذه المذاهب، ومعرفة قرب تفسير هذه المذاهب من تفاسير أهل السنة، الأمر الذي يؤدي إلى إضافة علمية تخدم النص القرآني من وجهين: الأول- تعدد المعاني التفسيرية للآية القرآنية، واتضح ذلك في موضوع الاختلاف في الوقف على اسم الجلالة ﴿اللَّه﴾، أو الوقف على ﴿وَالرَّاسخون فِي الْعِلْمِ﴾؛ فالوقف على الأول يمثل مدرستين من مدارس أهل السنة، وهما مدرستا التفويض والإثبات، والوقف على ﴿وَالرَّاسخون فِي الْعِلْمِ﴾ يمثل مدرسة التأويل التي منها الإباضية، وهذا الاختلاف اختلاف تنوّع يجعل المسلم لا يتعصب لمدرسة من هذه المدارس، ويقبل الرأي الآخر، والثاني- ترسيخ معنى من المعاني المتفق عليها، كموضوع وقوع المجاز في اللغة والقرآن والحديث، الذي يتفق على وقوعه جمهور علماء الأمة، ومنهم علماء الإباضية، وهذا ما وضح من منهج الخليلي، وتتناول هذه الدراسة بيان منهج الخليلي في تفسيره للآية السابعة من سورة آل عمران، الذي يمثل منهج التفسير الإباضي، واتخذت الدراسة المنهجَين الوصفي التحليلي والنقدي في بيان منهج الخليلي في تفسير الآية السابعة من سورة آل عمران؛ وذلك بوصف موضوعاته التي تناولها والشرحِ لها أو ذكرِ مصدرها، وأما النقد فهو يتجه إلى الآراء التي تبناها الخليلي، ودافع عنها، وبخاصة ما كان من آيات الصفات وكان متعصبا لمنهج مدرسة التأويل، الذي يوصف بأنه منهج الخلف، وكان يصف علماء مدرسة الإثبات خاصة بالحَشْوية والْمُجسِّمَة، و تتمثل إشكالية الدراسة في عدم وجود دراسات تتمتع بالحيادية في دراسة منهج مفسري القرآن الكريم من الإباضية، وبخاصة تفسير الخليلي؛ فمنها المغالي في الإطراء والموافق لكل ما يقوله الخليلي، ومنها المغالي في النقد والواصف للإباضية بالمبتدعة وغير ذلك، ومن هنا كانت هذه الدراسة في بيان منهج التفسير الإباضي متمثلا في تفسير الخليلي، ومحاولة الوصول إلى القول الراجح في تفاسير الإباضية مع الالتزام بالحيادية العلمية دون تجريح أو إطراء، وقد قامت الدراسة على العناصر الرئيسية التي ذكرها الخليلي في تفسيره للآية بالتحليل والمناقشة والنقد، وأبرزت أهمية دراسة منهج التفسير الإباضي وبخاصة تفسير الخليلي لما له من أهمية علمية ودينية، ومما أبرزته الدراسة أيضا تميز الخليليِّ في ردِّهِ على مُنكرِي المجاز، فقد استند فيه على أقوال العلماء المعتبرين قديما وحديثا، وكان محقًّا في تناوله اضطرابَ ابن القيم(ت751هـ) وتناقضه في موضوع المجاز، لكنه لم يكن مُنصفًا في هجومه على المثبتين لآيات الصفات؛ إذ سماهم حَشوية، ووصف عقيدتهم بأنها اسْتُقِيت من الفكر اليهودي، واستند إلى نصوص مبتورة؛ ليؤكد فكرته، وهذا الفعل لا يجوز من عالم كبير في مكانة الخليلي! وقد اتضح أنَّ منهج الإباضية في التفسير قريب جدًّا من منهج مفسرِي أهل السنة مع بعض الاختلافات في تناول آيات الصفات؛ وهذا يرجع إلى اختلاف التنوُّع، لا اختلاف التضاد.

Li̇bya'daki̇ Vakif Kurumunun Sürdürülebi̇li̇rli̇k Ve Sosyal Adaleti̇n Sağlanmasindaki̇ Rolü: Sorunlar Ve Çözüm Öneri̇leri̇ - Shaban, Mohamed Khalifa A. Ben; Azrak, Tawfik (Karatay İslam İktisadı ve Finans Dergisi, 2025)
Vakıflar, İslam tarihinde önde gelen dini ve ekonomik kurumlardan biri olarak kabul edilmektedir. Sosyal dayanışma ilkelerini güçlendirmede, dini ve eğitimsel faaliyetleri desteklemede ve aynı zamanda yüzyıllar boyunca yerel toplulukların gelişimine katkıda bulunmada önemli bir rol oynamışlardır. Bu araştırma, Libya’daki vakıf yönetiminin mevcut durumunu incelemeyi amaçlamakta; bu kurumun tarihî ve hukukî çerçevesini analiz ederek, toplum dengesini sağlamak amacıyla toplumun bazı kesimlerini desteklemedeki ekonomik ve sosyal rollerini ortaya koymaktadır. Çalışma, özellikle siyasi ve ekonomik değişimlerin bu kurumun sürdürülebilirliğini ve etkinliğini nasıl etkilediğine odaklanarak, vakıf sisteminin karşı karşıya olduğu zorlukları ele almaktadır. Ayrıca, mevcut sorunların çözümünde ve vakıf yönetiminin etkinliğinin artırılmasında yerel bir idarî model olarak İbazıyye mezhebine özgü Azzabe sistemine ışık tutulmaktadır. Bu sistem, toplumsal katılımı ve halk nezdindeki güveni tesis etmede potansiyel bir çözüm olarak değerlendirilmektedir. Araştırma, betimsel ve analitik yöntemlere dayanmakta olup, yeterince incelenmemiş olan Azzâbe sistemi aracılığıyla yerel bir yönetim modeli sunmasıyla dikkat çekmektedir. Ayrıca, bu kurumun sosyal adalet ilkeleri ve sürdürülebilir kalkınma hedefleriyle uyumlu şekilde etkinliğini artırmayı hedefleyen bir dizi reform önerisi de sunulmaktadır.

Ibāḍī Maritime Law in the Indian Ocean: Transport, Trade and Taxes in the 2nd-3rd/8th-9th Centuries - Bouzenita, Anke Iman (Ilahiyat Studies, 2025)
Seafaring and trade across the Indian Ocean have played a pivotal role for Oman and its scholars. Islamic law compendia are reflective of and an important source on the material culture of their times. They discuss all aspects of human life, questions of personal status and trade and international relations. Despite the exposure of Oman and its scholars to the sea and related legal cases, maritime law in the Ibāḍī fiqh encyclopedias is a neglected field of research. This study aspires to close a gap in the literature. It focuses on the earliest extant Omanī fiqh encyclopedias and other relevant material of the 2nd-3rd/8th-9th centuries, mainly the Kitāb Jāmiʿ Abī l-Ḥawwārī (alive in 272/885), Kitāb Jāmiʿ al-Faḍl ibn al-Ḥawwārī (d. 278/891) and Jāmi’ Ibn Jaʿfar al-Izkawī (alive in 277/892), with references to later sources, primarily the Kitāb Bayān al-sharʿ of Muḥammad ibn Ibrāhīm al-Kindī (d. 508/1115), the Muṣannaf of Abū Bakr al-Kindī (d.557/1162), and others. This research analyses the available material to identify the earliest possible source material and authorities of dicta on Ibāḍī maritime law while referencing later material for clarification. Case studies on different questions, such as hiring ships and vessels for transportation, contract work, shipwreck and jettison, taxation, and persons missing at sea, are analyzed with respect to the sea as spatial factor that may (or may not) impact Islamic legal rule.

İbâdî Âlim Osman b. Halîfe es-Sûfî’nin Fırka Tasnif Metodu Üzerine Bir İnceleme - Eski, Duran (Kader, 2025)
Hz. Peygamber’in vefatından sonra Müslümanlar arasında başta imâmet olmak üzere çeşitli meselelerde ihtilaflar meydana gelmiştir. Özellikle Hz. Osman’ın öldürülmesi ve ardından Cemel ve Sıffîn savaşlarıyla devam eden süreç, Müslümanların kendi içinde gruplara ayrılmasının ve çeşitli fırkalara bölünmesinin temelini teşkil etmiştir. Bu bağlamda ortaya çıkan ilk fırkalardan biri İbâdiyye olmuştur. Abdullah b. İbâd’a nispetle İbâdiyye diye anılan bu fırka, varlığını günümüze kadar da devam ettirmiştir. Bununla birlikte İbâdiyye üzerinde yeterli çalışmaların yapıldığını ve her açıdan objektif bir şekilde ele alındığını söylemek mümkün değildir. Muhalifleri tarafından parça-bütün ilişkisi kurularak Hâricîlerin alt kollarından biri şeklinde tasnif edilen İbâdiyye, genellikle bu şekildeki bir tanımlamayı kabul etmemiş ve Hâricîlik tabirinin zihinlerde uyandırdığı olumsuz anlamdan uzak durmaya çalışmıştır. Kendilerini de esasen Sıffîn Savaşı’ndaki Hakem Olayı ile birlikte Hz. Ali’nin ordusundan ayrılan ve Muhakkime denilen grubun devamı olarak görmüştür. Bu noktada mezhebin daha iyi anlaşılması ve değerlendirilmesi noktasında İbâdiyye’nin kendi kaynaklarından hareketle görüşlerinin ortaya konulması oldukça önemlidir. Dolayısıyla bu çalışmada, 6./12. asırda Kuzey Afrika’da yaşamış İbâdî âlim Ebû Amr Osman b. Halîfe el-Mârağnî es-Sûfî’nin Risâletü’l-fırak adlı eseri konu edilmiştir. Eserde ilk olarak İbâdiyye’nin kendi içindeki ayrışmalara yer verilmiş ve bu bağlamda altı alt fırkadan bahsedilmiştir. Söz konusu fırkalar, klasik İslâm Mezhepleri Tarihi kaynaklarında İbâdiyye’nin alt kolları olarak zikredilen fırkalardan tamamen farklıdır. İbâdiyye’den sonra da Hâricî fırkalara geçilmiştir. Bu fırkalardan genel anlamda bahsedilip ayrıntıya girilmemiş ve burada mutedil bir Hâricîlik algısı oluşturulmaya çalışılmıştır. En sonunda da Mârika, Mürcie, Kaderiyye ve Sebbâbiyye/Şîa şeklinde İslâm tarihinde ortaya çıkan mezheplere yer verilmiştir. Genellikle Ehl-i sünnet tarafından Hâricîler için kullanılan Mârika ismi, burada ters bir mantık yürütülerek Ehl-i sünnet hakkında kullanılmıştır. Muhakkime’den İbâdiyye’nin Vehbiyye kolu ise hak fırka olarak kabul edilmiştir. Böyle bir kabul eserin amacını, üslubunu ve metodunu doğrudan etkilemiştir. Bu çalışmada Osman es-Sûfî’nin hayatı, ilmî kişiliği ve yaşadığı dönem hakkında bilgi verilmiş, ardından Risâletü’l-fırak’ta uyguladığı fırka tasnif metodu ve bu tasnifin nitelikleri üzerinde durulmuştur. Çalışmanın amacı, Osman es-Sûfî bağlamında İbâdiyye’nin diğer İslâm mezheplerine dair yaklaşımını ve onlar arasında kendilerini nerede konumlandırdığını ortaya koymaktır. Ayrıca 6./12. asır İslâm düşünce dünyasının İbâdiyye tarafından nasıl algılandığı, hangi mezheplerin tekfir edilip uzak durulduğu ve tekfire konu edilen meselelerin neler olduğu gibi hususlar da çalışma kapsamına girmektedir.

Abdullah b. İbâz’ın Abdülmelik b. Mervân’a Gönderdiği Risâle - Çolak, Muhammet Ali (Düzce İlahiyat Dergisi, 2025)
Hâricîlik, İslam tarihinde ilk ayrılık hareketini gerçekleştiren itikâdî mezheptir. Bu sebeple İslam Mezhepler Tarihi müellifleri tarafından zamanla ortaya çıkan Hâricî fırkalar ve görüşleri büyük bir titizlikle kayıt altına alınmıştır. Bununla birlikte erken döneme ait ana Hâricî fırkalardan olup varlığını günümüze kadar sürdürebilmiş olan İbâzîliğin yazılı metinlerinin bir kısmı bugün ulaşılabilir vaziyettedir. Çalışmamızda yer verdiğimiz Abdullah b. İbâz’ın (ö. 86/705 [?]) dönemin Emevî halifesi Abdülmelik b. Mervân’a (ö. 86/705) gönderdiği risâle İbâzîliğin temel itikâdî görüşlerini anlama noktasında erken dönemde kaleme alınmış oldukça önemli bir yazılı kaynaktır. Bu risâle incelendiğinde İbâzîler’in itikâdî görüşlerinin dayanakları büyük oranda ortaya çıkmaktadır. Ayrıca her ne kadar mezhebî taassup ile kaleme alınmış olsa da ilk dört halife dönemi olayları ve erken dönem Emevî tarihine kaynaklık edebilecek bilgiler barındırmaktadır. Bizler de çalışmamızda günümüze kadar ulaşabilmiş bu risâlenin çevrisini ve değerlendirmesini yaparak İslam Mezhepler Tarihi alanındaki araştırmacılarının istifadesine sunmaya karar verdik. Söz konusu bu risâle hem İbâzî geleneğe ait eserler hem de Ehl-i sünnet ve Şiî geleneğe ait diğer klasik İslam Mezhepler tarihi eserleriyle karşılaştırmaya, üzerinde tahlil ve tenkit yapmaya elverişlidir.

Mağrib’de Fatımi İktidarına Karşı Bir Meydan Okuma: İbadî Ebū Yezīd en-Nukkārī İsyanı (332-336/943-947) - Demir, Ferda (Ankara Üniversitesi Ilâhiyat Fakültesi Dergisi, 2025)
Şiʿa’ya bağlı bir mezhep olarak gelişen İsmailiyye, Caʿfer es-Ṣādıḳ’ın (ö.148/765) vefatından sonra yürütülen gizli davet faaliyetleri ile Müslüman coğrafyada yayılmış, özellikle Yemen’de ve Mağrib’de etkili olmuştur. İsmailî başdāʿīsi Ebū ʿAbdullāh eş-Şīʿī’nin (ö. 298/911) çağrısı üzerine Mağrib’e ulaşan dönemin İsmailî imamı ʿUbeydullāh el-Mehdī (297-322/909-934), hilafetini ilan ederek Fatımi Devleti’ni kurmuştur (296/909). Akdeniz kıyılarından Ṣaḥrā Çölü’ne kadar uzanan, coğrafi açıdan çeşitli bir yapıya sahip Mağrib’de, nüfusun çoğunluğunu Berberiler ve Araplar oluşturuyordu. Dinî yapı ise ağırlıklı olarak Maliki Sünniler, İbadî Hariciler ve Şiî İsmailîlerden meydana geliyordu. Dinî, etnik ve coğrafi unsurların bir araya gelişi, İsmailî-Fatımi yönetimine yönelik siyasi ve askerî gerilimlerin oluşmasına elverişli bir zemin hazırlamıştır. Harici-İbadîliğin Nukkārī kolundan olan Ebū Yezīd Maḫled b. Keydād’ın başlattığı uzun soluklu isyan (332-336/943-947), Fatımi Devleti’nin kuruluş döneminde Mağrib’in dinî, etnik ve siyasî etkenlerini bütüncül biçimde yansıtan bir olaydır. Bu çalışmada, Ebū Yezīd İsyanı’nın arka planı, gelişim süreci ve sonuçları, ana kaynaklara dayanılarak kapsamlı biçimde ele alınmıştır. Bölgenin siyasi, dinî ve demogrofik yapısına ilişkin önemli bilgilere ulaşılan bu çalışmada, Mağrib halkının Fatımi iktidarına yönelik teāmülü, dönemin dinî ve toplumsal dinamikleri bağlamında değerlendirilmiştir.

الدور العماني في دعم الحملات الكشفية البريطانية في شرق أفريقيا خلال النصف الثاني من القرن 19م - الكيومي, د سليمان بن سعيد بن حبيب (مجلة الشرق الأوسط للعلوم الإنسانية والثقافية, 2025)
يتناول هذا البحث الدور العُماني في دعم حركة الكشوفات الجغرافية البريطانية في شرق أفريقيا خلال النصف الثاني من القرن التاسع عشر الميلادي، من خلال تحليل طبيعة العلاقة بين سلاطين زنجبار وروّاد الحملات الكشفية الأوروبية، ولاسيما البريطانية منها. ويسعى إلى إبراز الكيفية التي أسهمت بها التسهيلات السياسية والإدارية واللوجستية التي قدمها سلاطين زنجبار، بدءًا من عهد السيد سعيد بن سلطان، مرورًا بالسيد ماجد بن سعيد، وانتهاءً بالسلطان برغش بن سعيد، في تمكين المستكشفين من اختراق المناطق الداخلية لشرق أفريقيا. ويعتمد البحث على المنهج التاريخي التحليلي، مستندًا إلى الوثائق العُمانية والبريطانية، والمراسلات الرسمية، إلى جانب المصادر العربية والأجنبية المعاصرة للأحداث. ويكشف عن أن الدعم العُماني للحملات الكشفية لم يكن بدافع المشاركة في الأهداف الاستعمارية أو التنصيرية، بل جاء في إطار سياسة الانفتاح والتسامح التي انتهجها سلاطين زنجبار، وسعيهم إلى تعزيز مكانة زنجبار التجارية والسياسية في الإقليم. كما يوضح البحث التداخل الوثيق بين النشاط الكشفي والنشاط التنصيري، إذ شكلت الحملات الجغرافية غطاءً لانتشار الإرساليات المسيحية، التي استفادت من الحماية والتسهيلات الممنوحة للمستكشفين. ويخلص إلى أن هذه التسهيلات، وإن قُدِّمت بحسن نية، أسهمت دون قصد في تمهيد الطريق أمام التغلغل الأوروبي في شرق أفريقيا، وكان لها آثار بعيدة المدى على التوازن الديني والثقافي في المنطقة، رغم استمرار قوة الحضور الإسلامي ومقاومته للنشاط التنصيري.
Keywords: Relations -- Oman -- Royaume-Uni

من رجالات النضال والإصلاح في مدينة الأغواط (الشيخ صالح بليدي1910-2015م أنموذجا) - سعودي, أحمد (مجلة العلوم الإنسانية والحضارة, 2025)

İbâdîliğin Kuzey Afrika’ya Yayılışı: Tarihsel Süreç ve Belirleyici Faktörler - Borsbuğa, Coşkun; Ekinci, Mustafa (Ondokuz Mayıs Üniversitesi İlahiyat Fakültesi Dergisi, 2025)
Bu araştırma makalesi, İbâdîliğin Kuzey Afrika’ya (Mağrib) yayılma sürecini tarihsel, sosyo-politik ve mezhepsel dinamikler çerçevesinde incelemektedir. Çalışmanın temel amacı, İbâdîliğin Mağrib coğrafyasında hangi tarihsel şartlar altında benimsendiğini ve nasıl kalıcı bir yapı hâline geldiğini ortaya koymaktır. Bu bağlamda, İslam mezhepleri tarihi ilmi perspektifi dikkate alınarak İbâdî ve İbâdî olmayan kaynaklar karşılaştırmalı bir yöntemle analiz edilmiştir. Emevî yönetiminin bölgede uyguladığı baskıcı politikalar, Arap olmayan unsurlara karşı ayrımcı tutumu ve merkezi otoritenin toplumsal adaletsizlikleri artıran uygulamaları, Berberî kabileleri arasında ciddi huzursuzluklara yol açmıştır. Aynı dönemde bölgede etkili olan Hâricî Sufrî hareketinin aşırı ve şiddet yanlısı tutumu, Berberîlerin Sufrîlere nazaran daha mutedil bir dini anlayışa yönelmelerine zemin hazırlamıştır. Bu şartlar altında İbâdîlik, özellikle barışçıl yaklaşımı, ahlakî bütünlüğü önceleyen söylemi ve toplumsal düzeni gözeten siyasal söylemi bölgedeki Berberî kabileler nezdinde önemli bir karşılık bulmuştur. İbâdîliğin Mağrib’de yayılmasında etkili olan bir diğer önemli unsur ise Ebû Ubeyde Müslim öncülüğünde Hameletü’l-ilm teşkilatının örgütlü ve sistematik çalışmalarıdır. Bu yapı, mezhebin öğretilerini hem sözlü hem yazılı yollarla taşraya ulaştırmada ve çeşitli kabilelerle mezhebin ilkelerini buluşturmada etkili bir aracı rolü üstlenmiştir. Ayrıca, İbâdîler arasında yaygın olan gizlilik esasına dayalı eğitim ve öğretim yöntemleri, hac dönemlerinde hacılara yönelik ilmî faaliyetleri ve İslam coğrafyasının birçok yerindeki ticarî faaliyetleri mezhebin baskı dönemlerinde varlığını sürdürmesini sağlamıştır.
Keywords: Ibadisme -- Afrique du Nord

The Mental Image of Omani Identity in the English Press (1875–1950) - Kharusi, Mohammed Juma al-; Djabri, Sara (Journal of Studies in Language, Culture, and Society, 2025)
Keywords: Récits de voyage -- Oman

The Geographical and Demographic Distribution of Islamic Legal Schools in Algeria during the Ottoman Era (1519-1830). - Ziouche, Ismail (Zaouli, 2025)
This research examined the demographic and geographical map of jurisprudential schools in Algeria during the Ottoman era, highlighting the competition and coexistence between the three schools: Maliki (the popular majority), Hanafi (the official school of the authorities), and Ibadhi (the school of the Beni Mezab). The study relied on a descriptive and analytical approach, drawing on contemporary sources and archival documents, and concluded that the Ottoman authorities did not impose their school of jurisprudence by force, but rather created a ‘dualistic’ system at the official level that allowed the Maliki school to remain the unifying national reference, while the Hanafi school remained confined to the military and civilian elites. The sectarian specificity of the Ibadhi followers in the M'zab Valley and even those who migrated to the northern cities was also respected.
Keywords: Ibadisme -- Algérie

منهج الشيخ سعيد بن خلفان الخليلي "ت. 1287 هـ." في التفسير من خلال أجوبته - الراشدي, سعيد بن مسلم; الخروصي, محمد بن ناصر بن حمد (مجلة الأندلس للعلوم الإنسانية والاجتماعية, 2025)

الاعتبارات الأخلاقية عند الإمام أبي سعيد من خلال كتاب الجامع المفيد - المسكري, جابر بن أحمد (صحار - مجلة مركز البحوث والدراسات العمانية, 2025)
يتناول هذا البحث الأبعاد الأخلاقية في كتاب "الجامع المفيد من جوابات أبي سعيد" للشيخ أبي سعيد محمد بن سعيد الكدمي، أحد الأئمة البارزين في المدرسة النزوانية في الفقه الإباضي بعُمان. يبدأ البحث بالتعريف بصاحب الجوابات ومدرسته ومؤلفاته، ثم يعرّف بكتاب "الجامع المفيد" من خلال بيان موضوعاته وخصائصه المنهجية. وبعد ذلك يستقرئ الباحثُ الاعتباراتِ الأخلاقية المتناثرة في فتاوى الشيخ وأحكامه، مثل توقير الصحابة، وإحسان الظن بالمؤمنين، والتلطف في تربية الصغار، ورفع الحرج عن الناس في الأحكام، واجتناب الغلو في الدين، والتواضع والتجرد للحق، ورعاية الفئات الضعيفة كاليتامى والمساكين والنساء، والإنصاف والعدل في التعامل حتى مع السلطان الجائر. ثم يعمد البحث إلى تأصيل هذه الاعتبارات الأخلاقية تأصيلاً شرعيًّا بالاستدلال من القرآن والسنة وأقوال علماء الإباضية بعُمان. ويخلص البحث إلى أن المبدأ الأخلاقي حاضرٌ حضورًا بيّنًا في البناء الفقهي عند أبي سعيد، وأن استحضار البعد الأخلاقي يفتح آفاقًا أوسع لفهم الأحكام الفقهية ومقاصدها، ويدعو الباحث إلى مزيد من الدراسات في تراث أبي سعيد وتحقيق كتاب "الجامع المفيد" تحقيقًا علميًّا شاملاً.

الشيخ درويش بن جمعة المحروقي (ت1086هـ) ومنهجه في تعزيز الأخلاق الاجتماعية: قراءة تحليلية في الباب الثامن والعشرين من كتابه (الدلائل على اللوازم والوسائل) - الكندي, ماجد بن محمد (صحار - مجلة مركز البحوث والدراسات العمانية, 2025)
يستعرض هذا البحث سيرة الشيخ درويش بن جمعة المحروقي (1020-1086هـ/1611-1676م)، أحد أعلام القرن الحادي عشر الهجري في عُمان، الذي جمع بين العلم والزهد والقضاء والإصلاح الاجتماعي، وكان له أثر بارز في النهضة العلمية والأخلاقية في عصر الدولة اليعربية. ويركّز المقال على كتابه "الدلائل على اللوازم والوسائل"، الذي يُعد موسوعة تربوية فقهية شاملة، مزج فيها المؤلف بين الأحكام الشرعية والتوجيه الأخلاقي بأسلوب وعظي مباشر يخاطب القلوب والعقول معًا. ويكشف البحث عن المنهج التربوي الذي اعتمده الشيخ في غرس الأخلاق الاجتماعية، من خلال التأصيل العقدي والروحي، والوسائل العملية، والدوائر الاجتماعية المتنوعة كالوالدين والأرحام والجيران، مع مزاوجة بين الترغيب والترهيب، وبين الفقه والتربية. كما يبرز المقال انعكاس شخصية المؤلف في كتابه، حيث يظهر الجمع بين الفقه والزهد، وبين العلم والعمل، مما يجعل الكتاب شاهدًا على مرحلة ذهبية من تاريخ الفكر العُماني، ودليلًا على وعي مبكر بربط الدين بالهوية والوطن، وإبراز دور الأخلاق في بناء السلم الاجتماعي وترسيخ قيم الوحدة والعدل.

حِجاجيّة القِيم والمواضع في كتاب الاهتداء لأبي بكر أحمد بن عبد الله الكندي - المسكري, عبد الرحمن بن سعيد (صحار - مجلة مركز البحوث والدراسات العمانية, 2025)
يبحث هذا المقال في كتاب الاهتداء لأبي بكر أحمد بن عبد الله الكندي (ت 557هـ)، الذي ألّفه في سياق الانقسام الفكري والسياسي الذي نشأ في عُمان عقب انعزال الإمام الصلت بن مالك الخروصي (ت 275هـ) عن الإمامة سنة 272هـ، وهو الحدث الذي أفرز جدلًا واسعًا بين الطائفتين الرستاقية والنزوانية، وترك أثرًا ممتدًا في الفكر الإباضي العُماني عبر قرون طويلة. يبرز البحث كيف اعتمد الكندي في خطابه على المزج بين الاستدلال البرهاني العقلي، والجدلي المبني على المشهورات، والخطابي المستند إلى القيم الأخلاقية والاجتماعية، موظفًا المواضع والقيم بوصفها عناصر مضمرَة تعكس الحسّ المشترك والوجدان الجمعي للجماعة. ومن خلال هذا البناء الحجاجي المتدرج، استطاع الكندي أن يقدّم حجّة يقينية تنتهي إلى الانتصار للطائفة الرستاقية، بما يكشف عن البنية الذهنية والثقافية التي شكّلت مسارات الفكر والسياسة في عُمان، ويؤكد دور المواضع والقيم في صياغة الخطاب الحجاجي في لحظات التحول التاريخي.

البنية الأخلاقية في المجتمع العُماني بين الفطرة والتوجيه النبوي قراءة في الخطاب القيمي والسياسي للوفود العُمانية - الهادي, سيف بن سالم (صحار - مجلة مركز البحوث والدراسات العمانية, 2025)
يهدف هذا البحث إلى تقديم قراءة موسّعة لمفهوم الأخلاق من حيث التعريفات اللغوية والاصطلاحية ومصادرها في الفكر الإسلامي والفلسفة الغربية، مع التركيز على انعكاساتها في البنية الاجتماعية والسياسية للمجتمع العُماني المبكر. يوضح المقال كيف تناول علماء المسلمين مثل ابن مسكويه والجرجاني والفارابي وابن سينا الأخلاق باعتبارها ملكة راسخة أو فطرة إيمانية، وكيف وظّفوا التصنيفات الفلسفية لتفسير السلوك الإنساني في ضوء الرؤية الشرعية، بينما قدّم الفلاسفة الغربيون مثل كانط ولوك وهيوم وجون ستيوارت مل وويليام جيمس تصورات مختلفة للأخلاق من منظور العقل والواجب والمنفعة والبراغماتية. كما يبرز البحث تجليات الأخلاق في الوفود العُمانية إلى النبي ﷺ، التي جسدت قيم الكرم، الحوار، وحدة الكلمة، والدعاء للوطن، بما يعكس وعيًا سياسيًّا وأخلاقيًّا مبكرًا يربط بين الدين والهوية والوطن، ويؤكد أن الأخلاق في التجربة العُمانية لم تكن مجرد سلوك فردي، بل مشروع جماعي يرسّخ قيم الوحدة والأمن والعدل في سياق حضاري وإنساني واسع.

الأخلاقيات الطبية في الفقه الإباضي - السيابية, حنان بنت حميد (صحار - مجلة مركز البحوث والدراسات العمانية, 2025)
تتناول هذه الورقة البحثية موضوع الأخلاق العملية من زاويتين: التنظير والتطبيق، مركزة على دور القدوة الحسنة في ترسيخ الأخلاق عبر الأجيال، حيث ينطلق البحث من دراسة ميدانية سابقة قام بها الباحث في مساق التربية في الإسلام بكلية العلوم الشرعية حول صناعة القدوة، وهل هي طبع متوارث أم مكتسبة بالتربية والملاحظة. يُعزز البحث هذا الإطار النظري بنموذج تطبيقي حيّ من واقعنا العُماني، يتمثل في شخص الشيخ أبي سرور حميد بن عبد الله الجامعي، رحمه الله، حيث نعرض سيرته وأبرز مواقفه العملية التي تجسدت فيها الأخلاق التطبيقية في الحياة الاجتماعية والإدارية والتعليمية، كما يتطرق البحث إلى أثر التربية المبكرة، لا سيما دور الأم في صناعة القدوة، ويحلل انعكاس هذه التربية في سلوكيات الممارسين وتأثيرها على تقاليد العلوم والصنائع وأخلاقياتها المتوارثة. يخلص البحث إلى أن صناعة القدوة لا تنحصر في الجانب الوراثي، بل تعتمد بدرجة كبيرة على الممارسة الواعية والتوجيه التربوي، ويقدم توصيات عملية لتفعيل دور القدوة الحسنة في المؤسسات التربوية والاجتماعية.

تأثير برنامج السنع العماني في تعزيز القيم بين الطالب في ظل تحديات وسائل التواصل الاجتماعي (دراسة ميدانية في ضوء تكامل أدوار الأسرة والمدرسة والإرشاد الديني) - الصبحية, عايدة بنت سعيد; الصبحية, شيماء بنت سعيد بن محمد; الصبحي, حمود بن سعيد بن محمد (صحار - مجلة مركز البحوث والدراسات العمانية, 2025)
يشكّل غياب "السنع العماني" بين الطلبة أحد أبرز التحديات التي تواجه الهوية الثقافية العمانية في الوقت الراهن؛ إذ أصبحت المجتمعات المعاصرة تواجه تحديات متزايدة نتيجة الاستخدام المكثف لوسائل التواصل الاجتماعي، والتي أثرت بشكل مباشر في منظومة القيم لدى النشء. وفي هذا السياق، تسعى الدراسة الحالية إلى تحليل تأثير "برنامج السنع العماني" بوصفه أحد البرامج التربوية الهادفة إلى ترسيخ القيم الوطنية والدينية والاجتماعية الأصيلة لدى الطلاب. كما تستكشف الدراسة أوجه التكامل بين الأسرة والمدرسة والإرشاد الديني في دعم هذا البرنامج وتعزيز أثره في بناء شخصية الطالب. وتركز الدراسة على ثلاثة أركان أساسية تسهم في تشكيل شخصية الطالب: المدرسة، والأسرة، والمرشد الديني. ويتم تحليل آراء المعلمين وأولياء الأمور والمرشدين الدينيين حول مدى تأثير البرنامج في السلوك اليومي للطلبة، لا سيما فيما يتعلق بالقيم الأخلاقية والاجتماعية، مثل: الاحترام، والأمانة، والانضباط، والنظافة، وتقبّل الآخر. كما يتناول البحث، بوجه خاص، دور المرشدين الدينيين في دعم هذه القيم من خلال الحصص الدينية، والإرشاد الطلابي، والأنشطة التوعوية؛ نظرًا لما لهم من أثر روحي وتربوي مباشر. واعتمدت الدراسة على المنهج الوصفي التحليلي، واستخدمت أدوات بحثية نوعية وكمّية شملت استبانة مبنية على مقياس ليكرت الخماسي، إلى جانب مقابلات معمقة. بلغ حجم العينة 110 مشاركين من المعلمين وأولياء الأمور والمرشدين الدينيين. وتم تحليل البيانات إحصائيًّا ونوعيًّا لاستخلاص النتائج. وأظهرت نتائج الدراسة أن مستوى تفعيل قيم السنع العُماني في المؤسسات التربوية والمجتمعية يتراوح بين الإيجابي والمرتفع، حيث بلغت المتوسطات الحسابية ما بين 3.80 و4.70؛ مما يعكس وعيًا كبيرًا بأهمية ترسيخ هذه القيم الأصيلة. كما بينت النتائج أن الأسرة تؤدي الدور الأبرز في غرس قيم السنع، تليها المدرسة والمؤسسات الدينية. ومع ذلك، كشفت النتائج عن وجود بعض القصور في تفعيل هذه القيم من خلال الأنشطة الصفية واللاصفية، والتي جاءت دون المستوى المأمول. وتوصي الدراسة بتعزيز التعاون بين الأسرة والمدرسة والمرشدين، وتحديث محتوى البرنامج لمواكبة التحديات المعاصرة، وتوفير برامج تدريبية للمعنيين لنقل القيم بصورة فعالة، بما يسهم في الحفاظ على الهوية الوطنية في ظل المتغيرات الاجتماعية المتسارعة.

دور المرأة العمانية في ترسيخ الأخلاق - العزرية, مريم بنت سعيد (صحار - مجلة مركز البحوث والدراسات العمانية, 2025)
تتناول هذه الدراسة دور المرأة العُمانية في ترسيخ الأخلاق من خلال استقراء كتب السير والمصنفات الفقهية العُمانية، بوصفها فاعلًا تربويًّا واجتماعيًّا محوريًّا في بناء القيم والأخلاق وتعزيزها، وضبط السلوك في المجتمع؛ بل مرتكزًا جوهريًّا في عملية التنشئة الأخلاقية والتربوية، وصياغة الفكر الأخلاقي، وتكوين الوعي القيمي المجتمعي. وتهدف الدراسة إلى إبراز حضور المرأة العُمانية في كتب السير والمصنفات الفقهية من حيث دورها الأخلاقي، وتحليل الأبعاد الأخلاقية التي ارتبطت بالمرأة كما عكستها تلك المصنفات، وبيان إسهامات المرأة في تعزيز القيم داخل الأسرة والمجتمع، وربط الموروث الفقهي بواقع المرأة المعاصرة في الجانب الأخلاقي. واقتضت خطة الدراسة تناولها في ثلاثة محاور: أولها يناقش موضوع التحلي بالقيم والأخلاق والاستقامة في السلوك عند المرأة العمانية، والثاني: يبحث أدوار المرأة في أسرتها، منطلقاتها وأبعادها، وثالثهما يبحث دور المرأة في نشر القيم الأخلاقية وتعزيزها في المجتمع. ومن النتائج المتوقعة للدراسة: تأكيد حضور المرأة بوصفها فاعلًا أخلاقيًّا مهمًّا في التاريخ والفقه العُماني، وإبراز قيمة كتب السير والمصنفات الفقهية كمصدر غني لإعادة تشكيل الوعي الأخلاقي المجتمعي، والتأكيد على ارتباط الأخلاق بالتشريع في السلوك والخطاب الفقهي العُماني.

دور قسم الثقافة الدينية في تعزيز القيم الأخلاقية لدى طلبة مدارس سلطنة عمان - الخزيري, قيس بن خليفة; الصالحي, بدر بن سعيد (صحار - مجلة مركز البحوث والدراسات العمانية, 2025)
تتكاتف جهود المؤسسات الدينية والتربوية والخدمية في تعزيز القيم العُمانية لدى الشعب العُماني، كل في مجاله، ووزارة التربية والتعليم بوصفها مؤسسة تربوية لها إسهاماتها الواضحة في تعزيز وترسيخ القيم العُمانية من خلال المناهج الدراسية والبرامج التثقيفية والمسابقات الدينية والعلمية والأدبية، وللمديرية العامة لتطوير المناهج دورها المتميز في هذا المجال من خلال تطوير المناهج الدراسية وفق مستجدات العصر والتقدُّم التقني. ولقسم الثّقافة الدينية بدائرة تطوير مناهج التربية الإسلامية دوره الفاعل، إلى جانب المناهج الدراسية، في تقديم البرامج التثقيفية لطلبة المدارس، وله إسهاماته في تعزيز القيم العُمانية الأصيلة لدى الطلبة، ومن خلال قراءة اسم القسم يتبادر إلى ذهن المتلقي بأنه معني بتعزيز القيم الدينية، ولكن هل للقسم دور في تعزيز القيم الأخلاقية لدى الطلبة؟ هذا هو السؤال الذي انطلقت منه هذه الدراسة. تهدف الدراسة إلى التعرُّف على إسهام قسم الثّقافة الدينية في تعزيز القيم الأخلاقية لدى طلبة مدارس سلطنة عُمان من خلال الموضوعات التثقيفية للأعوام الدراسية ٢٠١٦/٢٠١٧م إلى ٢٠٢٤/٢٠٢٥م، واتبعت الدراسة المنهج التحليلي الاستقرائي من خلال تحليل الموضوعات التثقيفية، واستقراء القيم الأخلاقية التي تضمنتها تلك الموضوعات. وقد توصلت الدراسة إلى أن لقسم الثّقافة الدينية دورًا فاعلًا في تعزيز القيم الأخلاقية لدى الطلبة، وتوصي الدراسة بتعزيز القسم بمزيد من الدعم المادي واللوجستي لتحقيق المزيد من الأهداف.

المجالس العُمانية (السبلة) كمنظومة ثقافية واجتماعية: دورها في ترسيخ قيم الاحترام والتسامح في ظل التغيُّرات المجتمعية المعاصرة - الصبحية, هنية بنت سعيد (صحار - مجلة مركز البحوث والدراسات العمانية, 2025)
تُعدُّ المجالس العُمانية التقليدية (السبلة) من أبرز المكونات الثقافية والاجتماعية التي شكَّلت على مدى عقود طويلة فضاءً للتفاعل الإنساني، ومصدرًا لترسيخ القيم الأخلاقية والسلوكيات الاجتماعية الإيجابية في المجتمع العُماني. إلا أن هذه المؤسسة المجتمعية تواجه اليوم تحديات متعددة في ظل التحولات الاجتماعية المتسارعة، وتغير أنماط التواصل بين الأفراد، وتنامي التأثيرات الخارجية عبر وسائل الإعلام والتكنولوجيا الحديثة. تتمحور المشكلة حول سؤال رئيس: ما مدى استمرار الدور الثقافي والاجتماعي للمجالس العُمانية (السبلة) في ترسيخ قيم الاحترام والتسامح في المجتمع العُماني المعاصر؟ يتفرّع عنه أسئلة مساندة: كيف تعيد السبلة إنتاج القيم في سياق التحوّلات التقنية والاتصالية؟ وما التحديات التي تُضعف تأثيرها، لا سيما تراجع الحضور الفيزيقي للشباب وتنامي الفردانية؟ وما مسارات التكيّف الممكنة للحفاظ على جوهر المؤسسة-السبلة؟ تعتمد الدراسة على منهج وصفي تحليلي، يستند إلى مراجعة الأدبيات المحكّمة والكتب والدراسات حول المجتمع العُماني، إلى جانب وثائق رسمية صادرة عن المركز الوطني للإحصاء والمعلومات وجهات ثقافية، فضلًا عن تحليل مضمون ثانوي لتغطيات صحفية (مقال مجلس الخنجي نموذجًا)؛ لكونه أحد المجالس والفضاءات التقليدية. وما تشمله إجراءات التحليل: مسح سردي منظَّم، وترميز موضوعاتي لمفاهيم (الاحترام، والتسامح، والوساطة، والحضور، والشباب، والوسائط الرقمية)، وبناء مصفوفة ربط بين المفاهيم النظرية والشواهد. أظهرت الدراسة أن المجالس العُمانية التقليدية (السبلة) لا تزال تحتفظ بدورها المركزي بوصفها منصة حيوية لترسيخ قيم الاحترام والتسامح، وتعزيز التماسك الاجتماعي في المجتمع العُماني، وذلك عبر طقوسها وأعرافها التي تولِّد هيبتوسًا اجتماعيًّا يُنظم التفاعل اليومي بين الأفراد، كما برهنت النتائج على أهمية السبلة في إدارة النزاعات والوساطة المجتمعية؛ مما يسهم في تقليل التصعيد وتعزيز الاستقرار المحلي. مع ذلك، تواجه هذه المؤسسة تحديات جوهرية ناجمة عن التحوُّلات الرقمية والديموغرافية؛ إذ لوحظ تراجع ملحوظ في الحضور الفيزيقي للشباب، وهو ما يؤثر على نقل القيم عبر الأجيال ويضعف الروابط الاجتماعية الرابطة. كما أدت وسائط التواصل الحديثة إلى تغييرات في طبيعة الحوار وطرق التفاعل، ما يستدعي إعادة النظر في آليات عمل المجالس؛ لضمان استمرارها في أداء وظائفها الثقافية والاجتماعية. تُبرز النتائج أيضًا إمكانات التكيُّف من خلال اعتماد نماذج هجينة تجمع بين الحضور المباشر والقنوات الرقمية المكملة، مع التركيز على تضمين موضوعات شبابية وثقافية حديثة تواكب الاهتمامات المعاصرة. وتوصي الدراسة بوضع قواعد سلوكية مرنة توفّر إطارًا للحوار البناء والإصغاء الفعّال، إلى جانب توثيق تجارب الوساطة والنجاحات للحفاظ على الذاكرة المجتمعية. بالتالي، تؤكد الدراسة أن استمرار دور السبلة يتطلب موازنة بين المحافظة على جوهرها الثقافي وفتح آفاق جديدة تضمن دمج الشباب والوسائط الرقمية؛ لتعزيز دورها كحاضنة للثقافة والقيم المجتمعية في عُمان المعاصرة.

أخلاق العمانيين في تحبيب الإسلام للغير: الهدوء والسمت نموذجًا - البكاري, هزاع بن جمعة (صحار - مجلة مركز البحوث والدراسات العمانية, 2025)
يُعد الخُلق الرفيع من أنجع الوسائل في تبليغ دعوة الإسلام وتحبيبها إلى قلوب الناس، وقد مثّل العمانيون نموذجًا حضاريًّا فريدًا في هذا السياق، حيث اتسمت تحركاتهم الدعوية والتجارية خارج حدودهم بسلوك راقٍ يتجلى في "الهدوء" و"السمت الحسن"؛ مما أسهم في إقناع كثير من الشعوب بالدخول في الإسلام طواعية. تسلط هذه الورقة الضوء على القيم الأخلاقية التي تحلّى بها العمانيون، وبخاصة سِمَتا الهدوء والسمت، اللتين ظهرتا جليًّا في تعاملهم مع المجتمعات المختلفة، لا سيما في سواحل شرق إفريقيا، وعالم الملايو، والهند، حيث انعكست هذه الأخلاق في التواضع، والسكينة، وضبط النفس، ولين الجانب، والالتزام بالآداب الإسلامية الرفيعة في القول والعمل. يعتمد البحث على المنهج الوصفي التحليلي، مستندًا إلى المصادر التاريخية، وروايات الرحالة المسلمين، وشهادات محلية من شعوب البلدان التي تفاعل معها العمانيون. ويهدف إلى تقديم قراءة أخلاقية/ دعوية لدور العمانيين في نشر الإسلام، بعيدًا عن السرد الجغرافي والتجاري المعتاد، مع إبراز كيف شكلت الأخلاق الهادئة وسيلة فعّالة غير مباشرة للدعوة إلى الله. وتؤكد الورقة أن الهدوء والسمت لم يكونا مجرد سلوك شخصي، بل كانا جزءًا من هوية عمانية متجذّرة، تشكّلت بفعل عوامل دينية (المذهب الإباضي)، واجتماعية، وثقافية؛ مما جعل من العماني داعيةً عمليًّا بمجرد حضوره قبل أن ينطق بكلمة واحدة، بالإضافة إلى ذلك يناقش البحث كيف أن الهدوء العماني لم يكن ضعفًا، بل حكمة، وأن السمت لم يكن تصنعًا، بل طبعًا أصيلًا، جعلا من العُماني داعية بقيمه قبل كلماته. كما يناقش كيف يمكن استلهام هذا النموذج الأخلاقي في خطابنا المعاصر؛ لمواجهة الصور النمطية عن الإسلام، وتقديم بديل حضاري فعال في ميادين الدعوة والتواصل الثقافي العالمي.
Keywords: Ibadisme -- Oman

تحقيق في مدة إمامة عبد الوهاب وابنه أفلح للدولة الرستمية - بوشامة, أحمد (مجلـة البحوث التاريخية, 2025)
Keywords: Dynastie rustumide

الشركة الإمبراطورية البريطانية لشرق أفريقيا 1888-1894 - الحجي, محمد مثكال (مجلة جامعة دمشق للدراسات التاريخية, 2025)

العلاقات السياسية بين سلطنة عمان والمملكة المغربية : 1971-1982م - جدعان, نبراس خصير; فرحان, فهمي أحمد (مجلة دراسات في التاريخ والآثار, 2025)
يتناول هذا البحث تطور العلاقات السياسية بين سلطنة عُمان والمملكة المغربية خلال المدة من 1971 حتى 1982م، وهي مرحلة شهدت تحولات سياسية مهمة في العالم العربي. ركّزت الدراسة على توثيق اللقاءات الرسمية بين القيادتين، وتوضيح مواقف البلدين المتقاربة من القضايا العربية والإسلامية، خاصة القضية الفلسطينية. كما ناقش البحث التعاون بين البلدين داخل المنظمات الإقليمية كجامعة الدول العربية ومنظمة المؤتمر الإسلامي. وبيّن أن العلاقات بين السلطنة والمملكة اتسمت بالاحترام المتبادل وعدم التدخل في الشؤون الداخلية. وقد ساهمت زيارات القادة المتبادلة في ترسيخ هذا التعاون. كما أبرز البحث تطور المواقف الدبلوماسية المتبادلة تجاه قضايا الوحدة العربية والتضامن الإسلامي، كما أشار البحث إلى دعم كل من عُمان والمغرب للشرعية والاستقرار في المنطقة، ورفضهما للتدخلات الخارجية. وخلصت الدراسة إلى أن العلاقات بين البلدين في تلك المدة شكّلت نموذجًا للتنسيق السياسي البنّاء في العالم العربي.
Keywords: Relations -- Oman -- Arabie Saoudite

المجالس العُمانية (السبلة) كمنظومة ثقافية واجتماعية: دورها في ترسيخ قيم الاحترام والتسامح في ظل التغيُّرات المجتمعية المعاصرة - الصبحية, هنية بنت سعيد بن محمد (صحار - مجلة مركز البحوث والدراسات العمانية, 2025)
تُعدُّ المجالس العُمانية التقليدية (السبلة) من أبرز المكونات الثقافية والاجتماعية التي شكَّلت على مدى عقود طويلة فضاءً للتفاعل الإنساني، ومصدرًا لترسيخ القيم الأخلاقية والسلوكيات الاجتماعية الإيجابية في المجتمع العُماني. إلا أن هذه المؤسسة المجتمعية تواجه اليوم تحديات متعددة في ظل التحولات الاجتماعية المتسارعة، وتغير أنماط التواصل بين الأفراد، وتنامي التأثيرات الخارجية عبر وسائل الإعلام والتكنولوجيا الحديثة. تتمحور المشكلة حول سؤال رئيس: ما مدى استمرار الدور الثقافي والاجتماعي للمجالس العُمانية (السبلة) في ترسيخ قيم الاحترام والتسامح في المجتمع العُماني المعاصر؟ يتفرّع عنه أسئلة مساندة: كيف تعيد السبلة إنتاج القيم في سياق التحوّلات التقنية والاتصالية؟ وما التحديات التي تُضعف تأثيرها، لا سيما تراجع الحضور الفيزيقي للشباب وتنامي الفردانية؟ وما مسارات التكيّف الممكنة للحفاظ على جوهر المؤسسة-السبلة؟ تعتمد الدراسة على منهج وصفي تحليلي، يستند إلى مراجعة الأدبيات المحكّمة والكتب والدراسات حول المجتمع العُماني، إلى جانب وثائق رسمية صادرة عن المركز الوطني للإحصاء والمعلومات وجهات ثقافية، فضلًا عن تحليل مضمون ثانوي لتغطيات صحفية (مقال مجلس الخنجي نموذجًا)؛ لكونه أحد المجالس والفضاءات التقليدية. وما تشمله إجراءات التحليل: مسح سردي منظَّم، وترميز موضوعاتي لمفاهيم (الاحترام، والتسامح، والوساطة، والحضور، والشباب، والوسائط الرقمية)، وبناء مصفوفة ربط بين المفاهيم النظرية والشواهد. أظهرت الدراسة أن المجالس العُمانية التقليدية (السبلة) لا تزال تحتفظ بدورها المركزي بوصفها منصة حيوية لترسيخ قيم الاحترام والتسامح، وتعزيز التماسك الاجتماعي في المجتمع العُماني، وذلك عبر طقوسها وأعرافها التي تولِّد هيبتوسًا اجتماعيًّا يُنظم التفاعل اليومي بين الأفراد، كما برهنت النتائج على أهمية السبلة في إدارة النزاعات والوساطة المجتمعية؛ مما يسهم في تقليل التصعيد وتعزيز الاستقرار المحلي. مع ذلك، تواجه هذه المؤسسة تحديات جوهرية ناجمة عن التحوُّلات الرقمية والديموغرافية؛ إذ لوحظ تراجع ملحوظ في الحضور الفيزيقي للشباب، وهو ما يؤثر على نقل القيم عبر الأجيال ويضعف الروابط الاجتماعية الرابطة. كما أدت وسائط التواصل الحديثة إلى تغييرات في طبيعة الحوار وطرق التفاعل، ما يستدعي إعادة النظر في آليات عمل المجالس؛ لضمان استمرارها في أداء وظائفها الثقافية والاجتماعية. تُبرز النتائج أيضًا إمكانات التكيُّف من خلال اعتماد نماذج هجينة تجمع بين الحضور المباشر والقنوات الرقمية المكملة، مع التركيز على تضمين موضوعات شبابية وثقافية حديثة تواكب الاهتمامات المعاصرة. وتوصي الدراسة بوضع قواعد سلوكية مرنة توفّر إطارًا للحوار البناء والإصغاء الفعّال، إلى جانب توثيق تجارب الوساطة والنجاحات للحفاظ على الذاكرة المجتمعية. بالتالي، تؤكد الدراسة أن استمرار دور السبلة يتطلب موازنة بين المحافظة على جوهرها الثقافي وفتح آفاق جديدة تضمن دمج الشباب والوسائط الرقمية؛ لتعزيز دورها كحاضنة للثقافة والقيم المجتمعية في عُمان المعاصرة.
Keywords: Vie culturelle -- Oman

صورة الأخلاق العمانية في الصحافة الفرنسية المعاصرة - بن معاد, منجي بن علي (صحار - مجلة مركز البحوث والدراسات العمانية, 2025)
يهدف هذا البحث إلى تحليل صورة سلطنة عُمان في الصحافة الفرنسية، مُقَدِّمًا إياها كنموذج فريد يقوم على "نظرية أخلاقية" راسخة تتجاوز الحسابات البراغماتية. يُحدد البحث أربعة مبادئ رئيسة لهذه النظرية: التوازن بين الأصالة والمعاصرة، والاعتزاز بالهوية، والدبلوماسية القائمة على القيم، والتسامح. وتتجلى هذه المبادئ في الهوية البحرية والدور العُماني كـ "وسيط دولي" وفي مبادرات نشر التسامح. وبالرغم من الصورة الإيجابية العامة، يكشف البحث أن المقالات الفرنسية لا تُغفل بعض التناقضات، مثل: وجود "رقابة صارمة" على الشأن الديني، وازدواجية الخطاب الديني (بين المفتي والسلطة الرسمية)، وظهور تأثير "القانون المحلي" على العدالة الدولية (قضية الطفل الفرنسي-العُماني). يناقش البحث الصورة المقدمة عن عُمان التي تجانب الموضوعية في بعض الأحيان، وتفتقر إلى فهم "الأنساق الداخلية للنموذج الإسلامي" بناء على نقد أوليفييه روا للمنظور الغربي في الفهم والتعامل مع العالم الإسلامي. ويُثبت النموذج العُماني، في جوهره، نظرية "الحداثة الأخلاقية" لطه عبد الرحمن، رافضًا عمليًّا النموذج الحداثي الغربي المنفصل عن الأخلاق.

إحياء الأخلاق الإسلامية في العصر المعاصر: دراسة في كتاب روح الفضيلة للشيباني وتجلياته في السياق الماليزي - عثمان, رحمة بنت أحمد الحاج; العثمان, عبد الرحمن; كمال, نور شفيقة بنت أحمد (صحار - مجلة مركز البحوث والدراسات العمانية, 2025)
يشهد العالم المعاصر أزمة متنامية في القيم، حيث تتراجع الأخلاق والعادات الرفيعة، لا سيما بين الأجيال الناشئة؛ مما يجعل الحاجة إلى إحياء الوعي الأخلاقي أكثر إلحاحًا من أي وقت مضى. تنطلق هذه الورقة من هذا التحدي لتتناول كتاب روح الفضيلة: الأخلاق عند العمانيين نظرًا وعملًا، للمؤلف سلطان بن مبارك الشيباني، الذي يعرض رؤية غنية حول القيم الأساسية، مثل: الأمانة والتواضع والمسؤولية والاحترام، وكيفية تجسيدها في المجتمع العُماني من خلال التعاليم الدينية والتقاليد اليومية. وتعتمد الدراسة على المنهج التحليلي الوصفي لبيان الأفكار والنماذج العملية التي يقدمها المؤلف، واستجلاء ما تحمله التجربة العُمانية من دلالات معاصرة في إعادة الاعتبار للأخلاق. وتبرز النتائج  واستجلاء ما تحمله التجربة العُمانية من دلالات معاصرة في إعادة الاعتبار للأخلاق. وتبرز النتائج أن الحكمة الأخلاقية التراثية تمثل مرشدًا فاعلًا في بناء شخصية الشباب وتوجيههم نحو القيم الصحيحة في عالم سريع التغير، بما يجعل التجربة العُمانية نموذجًا جديرًا بالاستلهام عربيًّا وإسلاميًّا.

المبادئ الأخلاقية العلمية عند الشيخ كهلان الخروصي التفسير وعلوم القرآن نموذجًا - الطوقي, سليمان بن حمد (صحار - مجلة مركز البحوث والدراسات العمانية, 2025)
عبر التاريخ، لم تكن قيمة تمكنت من سبر أغوار القلوب وقلب الموازين كالأخلاق، بها سقطت دول الجبابرة، وعادت للحقائق مكانتها، ودخلت بسببها أفواج في دين الله تعالى، وبها وصف ربنا الكريم أحب خلقه إليه وأصفى أنبيائه محمد الخاتم رسول الهدى -صلى الله عليه وسلم- بقوله الكريم "وَإِنَّكَ لَعَلَىٰ خُلُقٍ عَظِيم" (القلم: 4)، وقد شملت الدعوة الربانية إلى الأخلاق مختلف الجوانب الحياتية، فدعت إلى حضورها في العلم والمعرفة والتجارة والتعاملات، وبين الحاكم والمحكومين، ورب الأسرة وأهل بيته، والمسؤول مع موظفيه، وكتب في الأخلاق أناس بمداد أقلامهم، ومنهم من خطها بسلوك تمثله، وآخرون بأقوال نطقوا بها، وأهل العلم الراسخون المؤمنون تمثلوا الأخلاق في جميع هذه الجوانب، وكان لزامًا عليهم، وهم القدوة بين الخلق، أن يكونوا كذلك، والعلامة الشيخ كهلان بن نبهان الخروصي أحد هؤلاء الأعلام الذين اعتنوا بهذا الجانب أيما عناية، فهي حاضرة عنده في تعاملاته بين الناس بمختلف أطيافهم، ويركز على ذلك ويستحضره في دروسه ومحاضراته وفتاويه. وقد آليتُ أن أكتب هذا البحث بحسب التقسيم الآتي: تمهيد، وفيه تعريف بالشيخ كهلان الخروصي، وفي المبحث الأول سأتناول المبادئ الأخلاقية في التعامل مع القرآن الكريم ومكانته وقدسيته وحضور هيبته عند المسلم، وفي المبحث الثاني سترتكز الكتابة الموقف الأخلاقي للمسلم في تحري الحق في قصص الأنبياء الكرام التي قصها القرآن الكريم وتناول بيان معانيها المفسرون، ثم خاتمة فيها عرض لأهم نتائج البحث.

النظرية الأخلاقية عند الإمام السالمي من خلال كتابه مدارج الكمال - القرالة, أحمد ياسين (صحار - مجلة مركز البحوث والدراسات العمانية, 2025)
للأخلاق في الإسلام مكانة سامية ومنزلة مرموقة؛ لأن غايتها هو الخير الأسمى والوصول بالإنسان عن طريق الفضائل إلى المثل الأعلى والكمال الإنساني والسعادة الأبدية. ومما يدل على أهمية الأخلاق في الإسلام أن الله تعالى عندما مدح النبي عليه السلام مدحه بعظيم خلقه، فقال تعالى: ﴿ وَإِنَّكَ لَعَلَىٰ خُلُقٍ عَظِيمٍ ﴾القلم:4، وفي ذلك يقول الإمام جعفر الصادق: أمر الله نبيه بمكارم الأخلاق في هذه الآية، وليس في القرآن آية أجمع لمكارم الأخلاق من هذه الآية. لأجل ذلك كانت عناية علماء الإسلام بعلم الأخلاق عناية متميزة. وقد امتاز المذهب الإباضي عن بقية المذاهب بأنه لم يفصل بين الأحكام الفقهية وأخلاقيات فاعلها؛  فهو يسعى دائمًا إلى أن تحقق الأحكام الشرعية مقاصدها التي شرعت لأجلها، فلا يستقيم في نظر هذا المذهب أن يمتنع الإنسان عن الطعام والشراب لكونه صائمًا، ثم يرتكب الموبقات والمحرمات من الكذب والغيبة وغيرها، وهذا الذي حمل الإمام الغزالي، وهو من علماء يرتكب الموبقات والمحرمات من الكذب والغيبة وغيرها، وهذا الذي حمل الإمام الغزالي، وهو من علماء السلوك والأخلاق، في كتابه إحياء علوم الدين على أن يفرق بين فعل العامة في استجابتها للحكم الشرعي من حيث توفر الأركان والشروط المادية للحكم، وبين فعل الخاصة الذي يعنى بتحقيق المقصد الشرعي للتكليف الإنساني؛ لذلك هو يرى أن الصيام صيامان: صيام العامة، وصيام والخاصة، وصيام الخاصة هو الذي يحقق المقصد الشرعي من فرضية الصيام. وبناء عليه، يكون صيام الخاصة هو الصيام الأخلاقي. أما في المذهب الإباضي فلا فرق بين صيام الخاصة وصيام العامة؛ فالصيام هو الصيام، لذلك يمكن تصنيف المذهب الإباضي على أنه مذهب سلوكي أخلاقي. ونظرًا لأهمية الأخلاق في المذهب الإباضي ختم الإمام نور الدين السالمي (750هـ) كتابه معارج الآمال في مختصر الخصال بمبحث الأخلاق، وهذا يستق مع ما بيناه سابقًا من أن المذهب الإباضي لا يفصل، بل يقرن بين الأحكام العلمية والأخلاق، وقد جمع فيه المؤلف جملة كبيرة من الأخلاق العملية التي ينبغي للمسلم أن يتحلى بها. وتسعى هذه الدراسة للإجابة عن التساؤلات الآتية: ما معالم النظرية الأخلاقية عند السالمي؟ كيف وظف السالمي النظرية الأخلاقية في تهذيب السلوك الإنساني. وقد اعتمدنا في هذه الدراسة على المنهج الوصفي والمنهج التحليلي.

نماذج من أحاديث الأخلاق في مسند الإمام الربيع دراسة دلالية - التمتمي, أحمد بن عبيد (صحار - مجلة مركز البحوث والدراسات العمانية, 2025)
يأتي هذا البحث ليلقي الضوء على كتاب هو من أقدم الكتب العمانية تاريخيًّا، وهو مسند الإمام الربيع الفراهيدي العماني، ممثلًا في أحاديث الأخلاق؛ ليدرس نماذج من هذه الأحاديث دراسة دلالية في فروعها المعجمية والصرفية والصوتية والنحوية. وتكمن أهمية البحث في أهمية النص والكتاب والموضوع، فالنص هو الحديث النبوي الذي لا ينطق صاحبه ﷺ عن الهوى ﴿إِنْ هُوَ إِلَّا وَحْيٌ يُوحَى﴾ [النجم: 4]، وهو المصدر الثاني من مصادر التشريع الإسلامي، وأما الكتاب فيعد من أقدم الوثائق العمانية؛ إذ صاحبه الإمام الربيع الفراهيدي العماني (170ه) من علماء القرن الهجري الثاني، وأما الموضوع فهو الأخلاق، والأخلاق من مقاصد التشريع وجوهر الدين، وبها مدح خاتم النبيين ﴿وَإِنَّكَ لَعَلَى خُلُقٍ عَظِيمٍ﴾ [القلم: 4]. وجاءت مشكلة الدراسة في الإجابة عن سؤالين مهمين: هل عرفت العرب قديمًا علم الدلالة بصورته التي يراد منها الآن؟ وما أثر علم الدلالة في فهم النص؟ وتعتمد هذه الدراسة على المنهج الوصفي التحليلي؛ لتحاول الكشف عن أسرار الدلالة: المعجمية والصوتية والصرفية والنحوية والبلاغية لنماذج مختارة من أحاديث الأخلاق في مسند الإمام الربيع، مبتدأ بتمهيد عن بعض فضائل الأخلاق وذكر عناية علماء المسلمين بها، ثم الكلام في المبحث الأول عن تعريف علم الدلالة وأنواعه ونشأته ثم دراسة تطبيقية لنماذج مختارة من أحاديث الأخلاق في مسند الإمام الربيع في مبحثه الثاني. وخلصت الدراسة إلى عناية الإسلام بقضية الأخلاق عناية بالغة، وإلى أهمية علم الدلالة في فهم النص وتحليله، فتبين من خلالها أثر علم الدلالة في فهم النص فهمًا دقيقًا إلى حد كبير، وإلى أن العرب عرفت علم الدلالة قديمًا بصورته الحالية من حيث العموم.

لغة الفقهاء العمانيين في مقررات الفقه للناشئة ومعالمها التربوية والخلقية - الخروصي, أحمد بن سالم (صحار - مجلة مركز البحوث والدراسات العمانية, 2025)
لطالما عجت مصنفات العمانيين الموجهة للناشئة بجملة من المصطلحات والرؤى التي تمد يدها لتربية النشء على الخلق القويم، ولم تكن مصنفات الفقهاء بمنأى عن هذا البحر العباب، بل كانت في مطلع الركب، كيف وقد وجدناها تؤكد بلسان الحال والمقال هذه الحقيقة، سواء كان ذلك في تركيبها المصطلحي وكذا فيما تحمله تلك البنية اللغوية من معالم تربوية وقيم خلقية رفيعة، وقد جاءت هذه الصفحات لتضع هذا جميعًا في سياق أوحد، ركز المبحث الأول على البنية اللغوية والمنهج الذي سارت عليه مصنفات الفقهاء الموجهة للنشء، واتجه المبحث الثاني لبيان المعالم التربوية التي تنبئ عنها لغة الفقهاء في تلكم المصنفات، وكل هذا كان مسبوقًا بمقدمة حول المصطلح الفقهي وأثره، فضلًا عن سرد مركز ويسير عن المصنفات التي اختارتها الدراسة لتسلط عليها الضوء في بيان المعالم الخلقية، وكان من أهم نتائج البحث التدليل على عناية الفقهاء بترسيخ الخلق الرفيع إبان تشوُّف الطالب ودراسته لفقه الشريعة، كما أن الدراسة أثبتت أن العلوم عامة والفقه خاصة ما لم تكن وشيجة العلاقة بينه وبين قواسم التربية المختلفة حاضرة فإنه لا يحقق الغاية منه. ولعل أبرز توصية توصي بها الدراسة ضرورة عناية الدارسين ابتداء بالنظر الحصيف في مصطلحات أهل الفقه ومعالمها التربوية، وتقترح وضع فهرس اصطلاحي يخص مصنفات العمانيين الفقهية في هذا السياق.

عدل الأئمة بين التنظير والتطبيق خلال الإمامة الإباضية الثانية - الرواحي, محمد بن مبروك; الندابي, ناصر بن علي (صحار - مجلة مركز البحوث والدراسات العمانية, 2025)
العدل أساس الحكم، والدولة الظالمة لا تدوم أبدًا، والعدل في الإسلام مفهوم واضح المعالم، وما علينا إلا قراءة التاريخ لمعرفة أساليب تطبيقه. من هذا المنطلق جاءت دراستنا التي عنوناها بعدل الأئمة بين التنظير والتطبيق خلال الإمامة الإباضية الثانية، وهدفت الدراسة إلى إلقاء الضوء على مفاهيم العدالة في مختلف المدارس الإسلامية، وتبصير القارئ بدور العدل في إرساء الأمن والاستقرار في الدولة. وطرحت الدراسة عددًا من الأسئلة، كان من بينها: ما المقصود بمفهوم العدالة عند علماء المسلمين؟ كيف جسّد الإباضية العدالة على أرض الواقع؟ كيف ساهم العدل في أمن الدولة واستقرارها؟ وخرجت الدراسة بعدد من النتائج، كان من بينها: حرص أهل الحل والعقد على اختيار شخص الإمام المناسب الذي يجعل من العدل أساسًا لحكمه. واتضح لنا من خلال سبر أغوار التاريخ نماذج جديرة بالوقوف عندها في تطبيق العدل على شتى شرائح المجتمع بدءًا من الإمام، وانتهاء عند أصغر فرد في المجتمع. وفي الختام قدّمت الدراسة توصيات، من بينها: أن تتبنى مؤسسة ذاكرة عمان الاحتفاء بالأئمة في تاريخ يوم وفاتهم؛ لتذكير النشء بدورهم وجهودهم.

الأخلاق العملية وصناعة القدوة: الشيخ أبو سرور وأثر القدوة الحسنة في ترسيخ الأخلاق في الحياة الاجتماعية والإدارية (أنموذجًا) - الجامعي, عادل بن حميد (صحار - مجلة مركز البحوث والدراسات العمانية, 2025)
تتناول هذه الورقة البحثية موضوع الأخلاق العملية من زاويتين: التنظير والتطبيق، مركزة على دور القدوة الحسنة في ترسيخ الأخلاق عبر الأجيال، حيث ينطلق البحث من دراسة ميدانية سابقة قام بها الباحث في مساق التربية في الإسلام بكلية العلوم الشرعية حول صناعة القدوة، وهل هي طبع متوارث أم مكتسبة بالتربية والملاحظة. يُعزز البحث هذا الإطار النظري بنموذج تطبيقي حيّ من واقعنا العُماني، يتمثل في شخص الشيخ أبي سرور حميد بن عبد الله الجامعي، رحمه الله، حيث نعرض سيرته وأبرز مواقفه العملية التي تجسدت فيها الأخلاق التطبيقية في الحياة الاجتماعية والإدارية والتعليمية، كما يتطرق البحث إلى أثر التربية المبكرة، لا سيما دور الأم في صناعة القدوة، ويحلل انعكاس هذه التربية في سلوكيات الممارسين وتأثيرها على تقاليد العلوم والصنائع وأخلاقياتها المتوارثة. يخلص البحث إلى أن صناعة القدوة لا تنحصر في الجانب الوراثي، بل تعتمد بدرجة كبيرة على الممارسة الواعية والتوجيه التربوي، ويقدم  توصيات عملية لتفعيل دور القدوة الحسنة في المؤسسات التربوية والاجتماعية.

البعد الأخلاقي في الرحلات العمانية إلى منطقة جنوب شرق آسيا دراسة في المضامين والآثار - طاهر, رشدي; سامي, عبد الغفار (صحار - مجلة مركز البحوث والدراسات العمانية, 2025)
هدفت الدراسة إلى الكشف عن البعد الأخلاقي في الرحلات العمانية إلى منطقة جنوب شرق آسيا، معرجًا على المضامين والآثار على أهل المنطقة. وتذكر الروايات التاريخية أن الإسلام دخل إلى منطقة جنوب شرقي آسيا منذ القرن الأول الهجري/ السابع الميلادي، وأن ذلك كان عن طريق التجار العرب، من عمان وحضرموت واليمن، وأن أوائل المناطق التي دخلها الإسلام في هذه الرقعة الجغرافية هي سواحل سومطرة الشمالية. وأما السبب في انجذاب أهل تلك المنطقة إلى الإسلام فهي ما تفصح عنها تلك الروايات بأن المكون الأخلاقي لهؤلاء التجار هو ما أثر بالفعل على أهل تلك المنطقة، ودعاهم إلى تغيير ما هم عليه من عقائد وأفكار، والاقتداء بهذه الفئة من الناس الذين قدموا عليهم من مناطق بعيدة ومختلفة عنهم كل الاختلاف، وهذا ما يؤكد - قطعًا بما لا مجال للشك فيه - التأثير القوي لهذا البعد في المنظومة الاجتماعية؛ لذا فإن الدراسة الحالية تحاول الإجابة عن التساؤل الرئيسي الآتي: "ما أبرز مضامين البعد الأخلاقي في الرحلات العمانية إلى منطقة جنوب شرق آسيا وما آثاره على أهلها؟" وتوصلت الدراسة إلى نتائج، أهمها: عُرف العرب وبخاصة العمانيين بالرحلة والترحال، واشتهارهم بالرحلات التي قاموا بها على مر التاريخ. إتقان العمانيين لصنعة البحّارة وما يتعلق بها، والتجارة وما يتوصل إليها، جعلتهم في مصاف المشاهير وأكسبتهم ثقة الناس وحبهم، انتشار الإسلام في منطقة جنوب شرق آسيا بسبب المكّون الأخلاقي الذي يؤكد على أهميته، وأن الأخلاق أساس التعامل، وهي مرآة المجتمعات والأمم. من أهم المضامين الأخلاقية في الرحلات العمانية لمنطقة جنوب شرق آسيا والتي تناولتها الدراسة الحالية هي: التسلح بالإيمان، التدين، العلم، الفقه، الصنعة، الإتقان، القوة، الشجاعة، الأمانة، الصدق، العلاقات الإنسانية، الحفاظ على الموروث الثقافي)، وهي على سبيل المثال لا الحصر. آثار هذه المضامين الأخلاقية على أهل منطقة جنوب شرق آسيا كبيرة وعميقة ومتغلغلة في هذه المجتمعات في جميع نواحي حياتهم، وإذا أظهرنا تقبلهم للإسلام واعتناقهم له عن قناعة ويقين ومحبة لكفى بذلك أثرًا. وأوصت الدراسة بتوصيات ومقترحات، أهمها: العناية والاهتمام بالرحلات العمانية؛ لأنها كنوز تراثية جمة من العلم والأدب والمعرفة والقصص والأحداث والعلوم التي تحويها، ولا يمكن أن يحويها أي مسار من مسارات الحياة. التأكيد على أهمية المكون الأخلاقي في الرحلات العمانية؛ لأنه الوجه الحضاري في عصر تعصف فيه رياح التغيير والحروب والعنف والشدة. إجراء دراسات معمقة عن مكونات وأبعاد الرحلات العمانية وتأثيرها على أهل المناطق التي يجوبونها ويرتحلون إليها. إجراء دراسات عن العلاقات والصلات المختلفة (دينية – ثقافية – اجتماعية – سياسية- اقتصادية – تجارية- وغيرها) بين أهل عمان ودول جنوب شرق آسيا.

التجربة العُمانية في تعزيز الأخلاق الإسلامية: من التأصيل إلى الممارسة - الحداد, أحمد بن علي (صحار - مجلة مركز البحوث والدراسات العمانية, 2025)
تُعَدَّ الأخلاق الإسلامية ركيزة أساسية في بناء الحضارات وضبط سلوك الأفراد وتماسك الجماعات؛ إذ تُشكِّل الإطار المرجعي الذي يوجّه الخطاب الديني والسياسات المجتمعية. وتمثل سلطنة عُمان أنموذجًا متميزًا في هذا المجال؛ حيث استطاعت عبر تاريخها أن تجمع بين التأصيل الشرعي والفكري للأخلاق وتجلياتها العملية في الواقع الاجتماعي والمؤسسي. وقد انعكس ذلك في تراثها العلمي والفقهي، وفي السلوك المجتمعي الذي حافظ على تماسك المجتمع واستقراره. تتمثل مشكلة البحث في التساؤل عن الكيفية التي تحوّل بها هذا التأصيل النظري إلى ممارسات عملية قابلة للرصد والتقويم في المجتمع العُماني، ومدى قدرة هذا النموذج على مواجهة التحديات الراهنة، مثل: التحولات الثقافية والرقمية والعولمة. ويهدف البحث إلى تحليل الأسس الشرعية والفكرية للأخلاق في التجربة العُمانية، والكشف عن آليات ترجمتها إلى ممارسات اجتماعية ومؤسسية، مع إبراز دور السياسات الوطنية الحديثة ورؤية عُمان 2040 التي جعلت الهوية والقيم محورًا استراتيجيًّا للتنمية الشاملة. يعتمد البحث على المنهج الوصفي التحليل

جهود الشيخ إبراهيم بيوض في الإصلاح الاجتماعي - بوغرة, نسرين (مجلة الإعلام والمجتمع, 2025)
تهدف هذه الدراسة للكشف عن جهود الشيخ إبراهيم بيوض في الإصلاح الاجتماعي، في المجتمع الميزابي خاصة، والقطر الجزائري عامة، بعد أن حاول الاستعمار الفرنسي - بكل ما أوتي من قوة القضاء على مقوماته، من دين، ولغة، وتاريخ، من خلال مخططاته الاستعمارية الاستيطانية التغريبية التنصيرية، حيث وقف الشيخ بيوض بفكره الإصلاحي الشامل، وتجربته العملية الرائدة في الميدان الاجتماعي والتربوي والتعليمي والصحفي، متصديا لتلك الحملات الرامية لضرب الوحدة الوطنية، وزرع الفرقة بين أوساط الشعب الجزائري، وذلك من خلال خطبه ودروسه المسجدية والتعليمية في معهده، ومن خلال مقالاته في الصحف الإصلاحية العربية الجزائرية، التي يستند فيها إلى القرآن الكريم والسنة النبوية، و احتكاكه بمجتمعه ومعرفته العميقة بأمراضه، فأسهم بفعالية في الإصلاح والتغيير من أوضاع المجتمع الجزائري، بما لا تزال آثاره إلى يومنا هذا. Abstract: This study aims to shed light on the efforts of SHEIKH IBRAHIM BIYOUDH in the realm of social reform, particularly within the Mozabite community and more broadly across Algeria. His work came in response to the relentless attempts of French colonialism—which employed all its might—to eradicate the foundations of Algerian identity, including its religion, language, and history, through its settler-colonial, Westernizing, and missionary agendas. In the face of these aggressive campaigns, SHEIKH IBRAHIM BIYOUDH stood firm with his comprehensive reformist vision and his pioneering practical experience in the social, educational, pedagogical, and journalistic fields. Through his sermons, mosque lessons, and educational efforts at his institute, as well as his writings in Algerian Arab reformist newspapers, he staunchly opposed these efforts aimed at undermining national unity and sowing division among the Algerian people. Drawing upon the Qur’an, the Sunnah of the Prophet, and his close engagement with his society and deep understanding of its afflictions, SHEIKH IBRAHIM BIYOUDH played an active and enduring role in reforming and transforming the conditions of Algerian society—an impact that remains evident to this day.

العادات والتقاليد في المجتمع الأباضي من خلال كتاب السير لبدر الدين الشماخي (ت 928هـ/1522م) - فاضل, زهراء سعيد; شرقي, علي عطية (مجلة الأستاذ للعلوم اإلنسانية والإجتامعية, 2025)

Sectarian Dynamics and Political Reconfiguration in the Islamic Maghreb during the Fatimid Era: A Historical-Analytical Study of Doctrinal Conflict, Power Struggles, and Governance Transformations (4th–5th Centuries AH / 10th–11th Centuries CE) - Chebli, Rabia; Zineb, Salmi (Science, Education and Innovations in the context of modern problems, 2025)
The Fatimid era in the Islamic Maghreb represents a decisive historical phase marked by profound sectarian tensions and accelerated political transformations that reshaped the region’s structures of authority, governance, and collective identity. The expansion of the Fatimid Ismaili mission during the early 4th century AH/10th century CE did not occur in an ideological vacuum; rather, it interacted dynamically with an already diverse doctrinal landscape characterized by Sunni, Ibadi, Kharijite, and tribal affiliations. These interactions generated a complex pattern of alliances, resistances, and conflicts that transcended purely theological disagreement and evolved into broader struggles over political legitimacy, sovereignty, and control of space. This study adopts a historical-analytical approach to examine the nature and implications of sectarian conflict in the Islamic Maghreb during the Fatimid period. It explores how doctrinal disputes intersected with tribal structures and local power centers, contributing to the reconfiguration of political authority and the emergence of new governance models. Particular attention is given to the role of Ibadi movements and the establishment of the Rustamid state, as well as to major uprisings such as the revolt of Abu Yazid Makhlad ibn Kidad, which embodied a dual confrontation—both sectarian and political—against Fatimid rule. The study argues that sectarian conflicts during the Fatimid era functioned as instruments of political mobilization and state formation rather than mere reflections of religious divergence. By analyzing these conflicts within their social, tribal, and geopolitical contexts, the paper demonstrates how the Islamic Maghreb became a laboratory for competing models of authority that left a lasting imprint on the region’s historical trajectory. The findings contribute to a deeper understanding of the relationship between doctrine and power in medieval Islamic history and highlight the central role of the Maghreb in shaping broader Islamic political developments.

المطبعة السلطانية في زنجبار (1879-1964م) - الضويانية, رنا بنت حمدا; الريامية, رقية بنت حمد (مجلة هيرودوت للعلوم الإنسانية والاجتماعية, 2025)
The study addresses the Omani cultural and intellectual movement in East Africa during the reign of Sultan Barghash bin Said (1870–1888), and his desire to achieve an Omani intellectual renaissance in East Africa, specifically in Zanzibar. This was pursued through the introduction of the printing press, which marked a unique transformation that contributed to the outreach of Omani and Arab culture. The study addresses the factors that led to the emergence of the idea of the Royal Printing Press, highlight its most significant intellectual publications, and explain its impact in Zanzibar’s society specifically, and in East Africa in general. The importance of the research lies in shedding light on the influence resulting from the establishment of the Royal Printing Press in East Africa. The research focus is reflected in presenting the reasons that led to the idea of introducing a printing press in Zanzibar, by exploring the contributing influences that supported the scientific and cultural renaissance in East African society and its role in stimulating intellectual thoughts and scientific awakening. The study will rely on the analytical method by examining and analyzing the conditions that played a role in motivating Sultan Barghash bin Said to introduce the printing press in Zanzibar and its impact on society. It will also utilize the descriptive method by presenting the most prominent productions, publications, and bulletins printed by the Royal Printing Press. The study concludes that the social environment in which the Omani Sultan grew up in, played a role in enhancing his interest in scientific and cultural pursuit. In addition, the cultural impact of the printing press extended through the preservation of Omani and Arab heritage through the diversity of its publications.
Keywords: Imprimerie -- Zanzibar

هيئة العزابة ودورها في التصدي لحملات التنصير"تعزيزالهوية الدينية والثقافية في المجتمع الميزابي" - نعوم, أأحمد; هارون, فاطمة (معارف, 2025)
قامت السلطات الاستعمارية الفرنسية منذ احتلالها للجزائر سنة 1830 م على محاولة إذابة المجتمع الجزائري في الكيان الفرنسي، وإحكام سيطرتها عليه، فعملت على تنفيذ العديد من الإجراءات في مختلف الميادين من أجل إنجاح مخططاتها الاستعمارية من بينها الميدان الديني محاولة نشر المسيحية عن طريق سياسة التنصير للقضاء على الهوية الوطنية والديانة الإسلامية، خاصة وأن رين ِّ المبش لقوا الدعم والسند من طرف السلطة الفرنسية،كما أنهم وجدوا في الجزائر أرضا خصبة لبث دعوتهم مع انتشار الفقر والأمية.وهذا ما أدى إلى بروز هيئات دينية في الجزائر وقفت بالمرصاد لهذه السياسة، ولعبت الدور المنوط بها في مواجهة كل ما يؤثر على الهوية الجزائرية،ومن بينها هيئة العزابة التي كانت لها مواقف بارزة.في منع هذا المشروع مبرزة خطر التبشير المسيحي على المجتمع الجزائري عموما والميزابي خصوصا
Keywords: Missionnaires -- Mzab

L’œuvre naturaliste de Georges Henri Parent (1937-2014), avec la liste - Antoine, Sébastien; Muller, Serge (Les Naturalistes Belges, 2025)
Georges H. Parent (1937-2014) was one of Belgium's most active and prolific naturalists during the second half of the 20th century and the beginning of the 21st century, having published more than 300 articles and books, some of which were very voluminous. His work focused on the fauna, mainly herpetofauna, and vascular flora of Belgium, but also on the neighboring territories of the Grand Duchy of Luxembourg, Germany, and northeastern France, particularly French Lorraine. These field investigations were accompanied by extensive bibliographic and biographical research and were supplemented by educational works on biology and publications on the protection of biodiversity and nature.
Keywords: Biographies -- Belgique; Faune -- Djerba

Le commerce Mozabite : une continuité du commerce Ibadite - Messouaf, Youcef (Revue Abhath, 2025)
Keywords: Commerce -- Mzab

Preserving the Architecture of the Ksour of the Mzab Valley through Islamic Urban Jurisprudence( fikh el-imran) and Its Sustainability - Dahmani, Belkacem; Djoudi, Mohamed (Revue Abhath, 2025)
Keywords: Architecture -- Mzab

السلع والبضائع في عمان خلال القرون الهجرية الأولى 1-6 هـ/7-12م: رصد وتحليل - الجهورية, أحلام بنت حمود (مجلة عصور الجديدة, 2025)
Keywords: Commerce -- Oman

Nineteenth-Century Mzabite Marriage Customs and Traditions - Gherbi, Faycal; Djaafri, Ahmed (Maghreb Journal of Historical and Social Studies, 2025)
Keywords: Moeurs et coutumes -- Mzab

An Omani Visitor in Ḥimā: Insights Into Connections During the Hellenistic Era - Prioletta, Alessia; Arbach, Mounir (Arabian Archaeology and Epigraphy, 2025)
ABSTRACT This study presents a new epigraphic inscription from Ḥimā (Najrān, Saudi Arabia), which records the arrival of an individual from ʿUmān during the reign of Abīyathaʿ Ghaylān, king of the Amīr tribe. Written in a South Arabian script but showing non‐Ancient South Arabian—possibly Hasaitic—linguistic features, the inscription provides rare evidence of trans‐Arabian mobility and diplomatic relations during the Hellenistic period. By contextualizing this text alongside other inscriptions and coins from southern and eastern Arabia, the article explores the political role of Abīyathaʿ, the integration of the al‐Asd tribe and the significance of long‐distance networks involving Gerrha and Mleiha. A newly discovered graffito referencing the gentilic Ġr‐ite also contributes to ongoing debates on the ancient name of Gerrha. The use of regnal and Seleucid‐era dating in these inscriptions offers further insight into evolving chronological systems across pre‐Islamic Arabia.
Keywords: Archéologie -- Oman

Oman’s Transformation after 1970 - Hughes, Geraint (Bustan: The Middle East Book Review, 2025)
Scholars and students of the history and politics of the Sultanate of Oman will in all likelihood acknowledge John E. Peterson as the doyen of their field, being active in the study of this Gulf state for just over fifty years. Oman’s Transformation after 1970 is a follow-up to his 2007 book Oman’s Insurgencies, which provided a detailed historical account of the Jebel Akhdar (1955–59) and Dhofar (1963–c.1976) rebellions and the counter-insurgency campaigns Sultans Said bin Taimur (1932–70) and Qaboos bin Said (1970–2020) waged with British support to defeat them.Over the past fifty-five years, Oman has evolved from an impoverished tribal state under Britain’s informal imperial influence to a fully sovereign, prosperous, but absolute monarchy. It has close ties to the Western powers and other members of the Gulf Co-operation Council (GCC), while playing an active role in regional diplomacy and preserving a semblance of neutrality (Oman has, for example, acted as a mediator between the US and the Islamic Republic of Iran and has tried to broker peace between the Houthis and their enemies in Yemen). Although the Sultanate did experience some internal unrest during the 2011 “Arab Spring” (442–44), it has not only emerged as one of the most stable states in the Middle East but also managed a peaceful transition of power after Qaboos’s death in January 2020. This was not an outcome that contemporary observers would have anticipated in the context of both Qaboos’s seizure of power in a palace coup in July 1970 or his regime’s struggle for survival against insurgent movements both in the Southern province of Dhofar and Northern Oman.1
Keywords: Recension

Traces of Clay: Exploring Slave and Migrant Identities in Medieval Swahili Zanzibar - Rødland, Henriette (Cambridge Archaeological Journal, 2025)
Abstract The East African coast has long been recognized as a cosmopolitan region, where different cultures and peoples met and exchanged ideas, goods and knowledge. The culture that developed there from the seventh century ce was shaped by these relations, often referred to under the term Swahili, and many of the coastal residents engaged in Islamic practice, long-distance trade, conspicuous consumption of valued goods, and spoke a common language. This paper investigates the presence of slaves and migrants from the East African interior, through pottery assemblages uncovered at two eleventh- to fifteenth-century ce sites in northern Zanzibar: Tumbatu and Mkokotoni. These are groups of people not usually discussed in relation to medieval Swahili towns, and slavery has been especially difficult to study archaeologically on the coast. Through a material culture of difference, I argue that enslaved and non-elite migrants can be recognized and allow for a fuller understanding of socio-economic and cultural complexity in Swahili towns.
Keywords: Esclavage -- Zanzibar

Al-Umma: Reform, Resistance, and the Periodical’s Role in Pan-Islamic Thought - Emara, Nagat (Oriente Moderno, 2025)
Abstract This paper explores alternative political imaginaries, envisioned communities, and forms of resistance as articulated in the Arabic newspaper al-Umma: ǧarīda ʿarabīyya taṣduru kull yawm ǧumʿa (Al-Umma: An Arabic Newspaper published every Friday), published and edited by Sheykh Abū al-Yaqẓān (d. 1973), a former student of the Ibadite reformist scholar Muḥammad Aṭṭfiyaš (d. 1914), in Algiers in 1933. It examines how the periodical fashioned itself as an embodiment of the umma (nation) and how its readership formed a community around it. This analysis draws on Jutta Ernst and Oliver Scheiding’s perspective on periodicals, which posits that they function as assemblages that transcend their physical form, becoming expressions of social networks and communities. Focusing on the periodical’s characteristics and features, its language, editorials, symbols, and calls to action, the paper demonstrates how al-Umma was transformed into a subject associated with the umma for its readers. Using Birgit Meyer’s concept of aesthetic formations as a framework, this paper investigates how the newspaper helped construct and embody a pan-Maghrebian identity in 1930s Algeria, beyond the notion of a fixed, bounded social entity.
Keywords: Journalisme -- Mzab; Réformisme -- Mzab

الجغرافيا التاريخية لإقليم ظفار في ضوء المصادر الكلاسيكية: قراءة في المواقع والحواضر القديمة - القرن الخامس قبل الميلاد - القرن الثاني الميلادي - الكثيري, سالم أحمد سالم (دورية کان التاريخية: المستقبل الرقمي للدراسات التاريخية, 2025)
Keywords: Urbanisme -- Oman

الموقف العُماني من المعاهدات البريطانية في تجارة الرقيق في شرق أفريقيا ودور فرنسا الثانوي فيها (1822-1873) - لفته, مثنى أيوب (الملوية للدراسات الآثارية والتاريخية, 2025)
The slave trade was a complex economic and political system closely connected to Omani influence along the East African coast, where Zanzibar became a major center for exporting enslaved people and employing them in the clove plantations that formed the backbone of the economy at the time. The Omani presence contributed to organizing this trade and developing its structure, making it an important source of wealth and power. In contrast, Britain and France approached the slave trade from purely colonial perspectives: Britain sought to use the slogan of "combating slavery" to expand its maritime and political influence, while France aimed to protect the interests of its agricultural colonies that depended on enslaved labor. As the rivalry between the two European powers intensified, the issue of slavery turned into a tool of political and economic pressure on the rulers of Zanzibar. Despite the treaties and imposed restrictions, the trade continued through covert methods, including smuggling and the use of foreign flags, until the late nineteenth century.
Keywords: Esclavage -- Oman

Between Interconnectedness and Insularity: Soqoṭrā from the Sixth to the Sixteenth Century CE - Hatke, George (Rocznik Orientalistyczny, 2025)
The history of the Yemeni island of Soqoṭrā from Late Antiquity to the European Age of Exploration is the history of an alternation between interconnectedness and insularity. On the one hand, Soqoṭrā was linked through commerce with other regions in the Indian Ocean, as well as with regions as far afield as the Mediterranean. Additionally, the Church of the East had, by the sixth century, put down roots on Soqoṭrā, a development that afforded the island a connection, however tenuous, to a wider world of eastern Christianity. A further link with the outside world was established in the mid-eighth century, when the Ibāḍī imamate of Oman briefly established rule over Soqoṭrā. On the other hand, Soqoṭrī history is also characterized by the equally strong pull of insularity. As a case in point, the indigenous islanders speak their own, unique Soqoṭrī language, which belongs to the Modern South Arabian branch of Semitic. As for Omani rule, this was ultimately overthrown through a revolt by Christian Soqoṭrīs, and while foreign merchants continued to visit the island, Soqoṭrā gained something of a reputation as a haven for pirates and an abode of magicians. It was also widely known as an outpost of Christianity. Over time, however, Soqoṭrā lost contact with the normative Christianity represented by the Church of the East, such that, by the time that the Portuguese first made contact with the island in the early sixteenth century, they found the indigenous inhabitants practicing a vestigial form of Christianity that centered on a veneration of the cross, but retained little else that could be deemed Christian.
Keywords: Soqotra -- Histoire

Masjid Strategies in Improving Community Economy with Cooperatives (Case Study of Oman Al-Makmur Masjid) - Arif, Weldy; Habibi, Khairul; Juhari (Perisai : Islamic Banking and Finance Journal, 2025)
This study examines the role of the Oman Al Makmur Mosque in empowering the local community's economy through a sharia-based cooperative. The research focuses on assessing two main aspects: the mosque's role as a center of economic activity and the impact of the cooperative on the welfare of its members and the surrounding environment. A qualitative descriptive method was used, with data collected through in-depth interviews, observation, and documentation. The uniqueness of this study lies in its emphasis on the role of the mosque economy and the application of Qardhul Hasan in cooperative practices, which is rarely explored. The data were analyzed thematically to discuss issues of cooperative management, the implementation of the Qardhul Hasan mechanism, as well as the challenges and opportunities faced. This study also makes a significant contribution to the discourse on Islamic-based economic empowerment and provides practical guidance for mosque managers and financial institutions in supporting community-based MSMEs. The research results show that since its establishment in October 2022, the mosque cooperative has facilitated interest-free capital for more than 130 members to start and develop micro, small, and medium enterprises (MSMEs). Bank Indonesia and BPRS Hikmah Wakilah have strengthened access to capital. This research makes an important contribution to the discourse on Islamic-based economic empowerment and offers practical guidance for mosque managers and financial institutions in supporting community-based MSMEs. The uniqueness of this study lies in the emphasis on the role of the mosque economy and the application of Qardhul Hasan in cooperative practices, which are still rarely explored.
Keywords: Vie sociale -- Oman

المؤثرات الحضارية العربية في زنجبار في عهد السيد سعيد بن سلطان 1832-1856 - محمدي, مليكة (مجلة عصور, 2025)
Sayyid Said bin Sultan, who assumed the rule of Oman in 1806, was able to link Oman with East Africa and unite them under his rule. He made Zanzibar his capital. Sayyid Said worked to establish his rule in Zanzibar on strong foundations to advance the Arab-African Sultanate. He was interested in various economic activities and made Zanzibar an oriental city by establishing various Arab customs and traditions, including civil and religious architecture and others. This study aims to introduce the personality of Sayyid Said, who is considered one of the prominent figures in modern Arab history, by highlighting the reasons that led him to make Zanzibar the capital of his state and to rule Oman from East Africa, and how he was able to make it a prosperous city with an oriental character.
Keywords: Vie politique -- Zanzibar -- 1806-1856

بنو ميزاب والمعاملات المالية في مدينة الجزائر أواخر العهد العثماني من خلال بعض وثائق سجلات المحاكم الشرعية -إقتراض الأموال أنموذجا - بخاخ, سعدون (مجلة الدراسات التاريخية, 2025)
Keywords: Mzab -- Histoire -- 1510-1830

Islamic Work Ethics as a Driver of Trade Sustainability in Algeria - Bouguerra, Nour El Houda (مجلة دراسات في الاقتصاد وإدارة الأعمال, 2025)
This study aims to highlight the extent to which work ethics based on Islamic values contribute to the sustainability of trade among merchants in the M’zab region of Ghardaia, Algeria. To achieve this goal, a questionnaire was distributed to a random sample of 100 merchants, and 76 valid questionnaires were retrieved for analysis. Results show a significant relationship between elements of Islamic work ethics, such as religious commitment, honesty in work, truthfulness in work, good customer relations, and cooperation and sharing, but with varying degrees. Good customer relations and honesty in work showed a stronger correlation with the sustainability of trade among M’zab merchants. The survey results indicated that the elements of Islamic work ethics among M’zab merchants affect the sustainability of their trade, and 17.1% of the variation in trade sustainability in the study sample can be explained by different levels of Islamic work ethics elements.
Keywords: Commerce -- Mzab

Afterlives of revolution: everyday counterhistories in southern Oman: by Alice Wilson, Stanford, CA, Stanford University Press, 2023, 336 pp., ISBN 978-1-5036-3578-4. - Alsraiha, Kassim (British Journal of Middle Eastern Studies, 2025)
Keywords: Recension

Simulation hydraulique des écoulements dans un canal d’irrigation de la fin du IVe millénaire en Oman - Bertrand-Krajewski, Jean-Luc; Pouzol, Tanguy; Brochier, Jacques Elie; Baudet, Robinson; Castel, Corinne (Techniques Sciences Méthodes, 2025)
Une mission archéologique pluridisciplinaire conduite par Corinne Castel, sous l’égide du CNRS, de l’Université Lyon 2 et du Ministry of Heritage and Tourism of Oman, mène des fouilles au Sultanat d’Oman depuis 2019 sur le secteur d’Al-Arid. Ce secteur est situé sur la rive gauche du wadi Khuwaybah, dans une large vallée au pied des monts Al-Hajar, à une quinzaine de kilomètres au nordouest du site archéologique de Bāt classé au patrimoine mondial de l’Unesco. Les fouilles ont mis en évidence deux phases principales d’occupation du site d’Al-Arid au début de l’âge du Bronze, aux périodes Hafit (environ 3200-2700 avant notre ère) puis Umm an-Nar (environ 2700-2000 avant notre ère). Elles ont révélé un nombre remarquable de vestiges : sept tours, une nécropole, des bâtiments, un atelier de transformation du minerai de cuivre en métal de la période Hafit.
Keywords: Archéologie -- Oman; Irrigation -- Oman

دور الشيخ محمد بن يوسف أطفيّش (ت1332ه/1914م) في التعريف ببعض مواضع مدينة غرداية- قراءة في مخطوط الرسالة الشافية - علاوي, العيد (مجلة الناصرية للدراسات الاجتماعية والتاريخية, 2025)
يسجل المتشغلون بالبحث والكتابة في المجال الطوبونيمي انعدام المصادر والوثائق المكتوبة التي يُنطلق منها في معرفة أصول تسميات الأماكن أو التغيّر الذي طرأ على بعضها، مما يدفعهم، في الغالب، إلى الاعتماد على الروايات الشفوية. وانطلاقا من هذا العائق، تأتي هذه الدراسة الموسومة بـ: دور الشيخ محمد بن يوسف أطفيّش في التعريف ببعض مواضع مدينة غرداية- قراءة في الرسالة الشافية- . ويمكننا القول بأن لهذه الرسالة مكانة كبرى؛ ذلك أنها تحوي معارف في مجالات مختلفة نحو: الأديان، المذاهب الفقهية، علم الكلام، التاريخ، علم الأنساب، الجغرافية، اللغة، الأدب... تهدف هذه الدراسة إلى التعرف على جغرافية مدينة غرداية من خلال التواصل مع المدونة(الرسالة الشافية)، وذلك برصد بعض المواضع التي جاءت فيها، وعرض الروايات المبينة لأصول تسمياتها، ولعلها(الدراسة)، بهذا الرصد والعرض، تضع أمام الدارسين مادة يُنطلق منها في التحقيق والصناعة المعجمية. Typically, toponymists note the lack of sources and written documents from which to base their knowledge of the origins of places’ names or the alterations that have occurred in some of them. This often leads them to rely on oral narratives. As the title suggests, the present study comes to light to address such an obstacle. Notably, the treatise holds great significance because it contains knowledge in various fields, including religions, schools of jurisprudence, theology, history, genealogy, geography, language, and literature. The presentstudyaims to identify the geography of the city of Ghardaia by engagingwith the corpus (Al-Risalah Al-Shafiyya), by identifying some of the places where it appears and presenting narratives explaining the origins of its names. Most importantly, through this exploration and presentation, the study will provide scholars with material from which to begin investigation and lexicographical development.
Keywords: Mzab -- Histoire

Fatwa Making in the Ibadi School: Requirements and Qualifications - Mosbah, Aissa (مجلة الواحات للبحوث والدراسات, 2025)
Issuing fatwa—among other aspects— preserves religion among people, showcases the timelessness of the Islamic legislation in addition to its superiority over time and place. Allah Almighty decrees the preservation and eternity of the tolerant sharī’ah, as He said: “Indeed, it is We who sent down the Reminder; and indeed, We are its guardian.” [Al-Hijr: 9]. Considering its noble status and high regard, significant attention, guidance, and religious rooting ‘ta’asil’ have been given to issuing fatwas by the Islamic law in terms of clarifying its concept, conditions, ethics, principles, benefits, and the methodologies used by jurists to derive legal rulings. This research paper aims to clarify the conditions necessary for making fatwas, the ranks of muftis and their qualifications, and the ruling on the fragmentation of ijtihad and fatwa from mainly an Ibadi standpoint. That is, this inquiry opens up on some works of scholars from other Islamic schools with the aim of broadening its scope.
Keywords: Fatwas -- Mzab

Women's Volunteer Work in the Mozabite Community - Rai, Faiza; Rabahi, Mustapha (مجلة الواحات للبحوث والدراسات, 2025)
This study examines women’s voluntary work in the Mozabite community, exploring whether it is an individual initiative or a cultural and religious tradition. Field research was conducted through interviews with women volunteers from the “Tamsiridin” organization, chosen as a model for this study. The findings reveal that this organisation forms the core of women’s voluntary work in the community. It transformed women’s voluntary work from isolated individual acts into an institutional and social practice that was once exclusively for men. Thanks to the "Tamsiridin" organization, women have gained the opportunity to assert their presence as active and productive members of society. Women now contribute to the construction, stability, and continuity of the social system alongside men.
Keywords: Vie sociale -- Mzab

The Role of Marketing-Oriented Urban Planning and Design in Enhancing a City's Visual Image: A Case Study of Ghardaïa City - Boukerch, Abdelkader; Abidi, Fatiha (Journal of Business Administration and Economic Studies, 2025)
This research examines the strategic role of marketing-oriented urban planning and design in enhancing the city's visual image, using Ghardaïa, a UNESCO World Heritage city in southern Algeria, as a case study. The study highlights the problem of the city's eroding visual image, which is a result of the poor integration between urban planning and city marketing. The clarity of a city's visual image generally reflects the interaction between its urban formation elements—buildings, urban blocks, and internal and external spaces—and the background of the visual scene, such as topography and climate. However, the focus of this study is on the formative structure of the city's visual image, which is the combination of physical planning elements and the natural background. This can be conceptualized as the sum of two mathematical functions influenced by a primary variable, time (t). This is not necessarily a quantitative measurement of the visual image's clarity, but rather a qualitative assessment and interpretation of this image's significance, achieved by using strategic urban planning, innovative architectural design, and an effective marketing mix.
Keywords: Tourisme -- Mzab; Urbanisme -- Mzab

The Impact of Commercial Caravans Crossing the Sahara on the Archaeological Heritage of Southern Algeria - Sagueni, Mahammed (Historical Studies, 2025)
Keywords: Commerce transsaharien

New Lights on Prophecy-Pretending and Mimetic Religions in Medieval Islamic North Africa - Mansouri, Mabrouk (Al-Jami'ah: Journal of Islamic Studies, 2025)
This paper addresses the proliferation of prophetic movements and mimetic religions in medieval Islamic North Africa, focusing on the Barghwāṭa and Ghumāra tribes. It critiques medieval Arabic and Orientalist terminologies used to explain this complex issue, arguing that they fail to capture the dynamics of these movements. The paper introduces the concept of mimetic religion to interpret localized prophetic movements that emerged on the periphery of the established religion, namely Islam, retaining its structure while presenting parallel, rather than counteractive, religio-cultural projects. Drawing on primary sources, it highlights how misrule and exploitative practices by early conquerors fueled North African resistance, leading to revolutionary and prophetic movements. It challenges both medieval historiographical reductions of these movements to sectarianism and modern interpretations shaped by French colonial Orientalism, which often reduced them to ethnic or religious conflicts between Arab-Muslim conquerors and indigenous North Africans. By analyzing primary sources and questioning Orientalist biases, the paper emphasizes the interplay of political, economic, social, and cultural factors in shaping North African religious settings. Ultimately, it defines new boundaries for re-contextualizing and re-interpreting mimetic religion as expressive of a complex texture framing religious, cultural, and social nomenclature rooted in local North African indigenous heritage.
Keywords: Croyances populaires

The narrative approach of Abu Abbas Al-Darjini through his book The Classes of the Scholars in Morocco: a critical analytical perspective - Kindī, Aḥmad b. Yaḥyā al-; Hinaei, Abdullah Salim b. Hamed al-; Mushrafi, Ahmed Bin Said b. Khalfan Al- (Science, Education and Innovations in the context of modern problems, 2025)
This research discusses the topic of narration according to Abu Abbas Al-Darjini. It begins with a brief biography of the author and his scholarly life, before moving on to his book The Classes of the Scholars in Morocco. The study then examines his methodology for tracking narration, focusing on his presentation methods and the evidence he provides, as well as the classifications he presents and their intended benefits. It also explores his methods of transmitting narratives, whether through chains of transmission (isnad), written sources or oral communication. Finally, the research concludes with a detailed discussion of the scientific value of the material in the book and how Abu Abbas Al-Darjini correctly utilised it. It also addresses how Orientalists such as Montelensky benefited from the evidential and scientific value of the book in their documentary and critical studies. The study aims to highlight the unique methodology adopted by Abu Abbas Al-Darjini in his collection of narratives and biographies, particularly within the Ibadhi tradition of North Africa. The study emphasises his temporal classifications for each era, building on the work of his predecessors and inspiring later researchers to improve their skills in gathering, researching and understanding this subject. Familiarity with earlier scholars‘ methodologies equips researchers with the competence to handle texts and strengthens their ability to write scientifically. Given Abu Abbas Al-Darjini‘s exceptional knowledge, narrative skills and documentation, he deserves the attention of researchers who can draw on his work and balanced methodology. Undoubtedly, the benefit Orientalists derived from his works in their critical studies reflects the scientific value of his book and its esteemed status among his contemporaries.
Keywords: Prosopographie -- Afrique du Nord

مؤسسات التعليم الديني القرآني؛ بين أصالة الثوابت وتحدي المتغيرات - حاج سعيد, بكير (مجلة رفوف, 2025)
ملخص: تتناول هذه الورقة إلى موضوع المدارس الدينية القرآنية ومدى تأثرها بالتغيرات المجتمعية، وسعيها الدائم إلى المحافظة على أصالتها، وهذا من خلال محاولة الإجابة على الإشكالية الآتية: ما الثابت وما المتغير في التعليم الديني القرآني؟ وما علاقته بالمتغيرات المجتمعية؟ للإجابة على الإشكالية، رصدت الورقة أهم التغيرات التي مست التعليم القرآني الديني، خلال أهم الفترات التاريخية المتعاقبة، ثم عرجت بعد ذلك إلى مناقشة مدلول الثابت والمتغير ومظاهره، واقترحت مجموعة قواعد يمكن أن تكون المفصل في موضوع الثابت والمتغير، وكتطبيق عملي لموضوع الثابت والمتغير، عرضت الورقة أهم محطات التغير المجتمعي والنوازل المحرجة، التي أحرجت مؤسسات التعليم القرآني؛ بعضها يمس عمق العمل التربوي وأخرى علاقات المؤسسة بالواقع الاجتماعي، وخلصت الورقة في النهاية إلى مجموعة من النتائج، ثم بتوصيات عملية تحافظ بها مؤسسات التعليم الديني القرآني على هويتها، وتحقق غاياتها. Abstract: This paper addresses the subject of Qur’anic religious schools and the extent to which they are influenced by societal changes, as well as their ongoing efforts to preserve their authenticity. It does so by attempting to answer the following problem: What are the constants and what are the variables in Qur’anic religious education? And what is their relationship to societal changes? The paper examines the most significant changes that have affected Qur’anic religious education throughout key successive historical periods. It then moves on to discuss the meaning and manifestations of constants and variables, proposing a set of principles that can serve as a reference point for distinguishing between them. As a practical application of the topic, the paper presents the most important milestones of societal change and critical challenges that have placed Qur’anic education institutions in difficult positions, some of which touch the core of educational process, while others concern the institutions’ relationship with social realities. The paper concludes with a set of findings and practical recommendations to help Qur’anic religious education institutions preserve their identity and achieve their objectives.
Keywords: Enseignement -- Mzab

سياسة سلطنة عُمان الخارجية أتجاه الجمهورية الإسلامية الإيرانية (۱۹۷۹ - ۲۰۰۷م) - عطيوة, عبد الرحمن طارق (مجلة مركز بابل للدراسات الانسانية, 2025)
The relationship between the Sultanate of Oman and Iran is distinct from that of other Gulf Cooperation Council (GCC) countries in terms of historical political relations. What distinguished this relationship was the geographical factor and the nature of the Sultanate of Oman s foreign policy, especially when Sultan Qaboos bin Said took over the Sultanate of Oman and made its foreign policy a starting point for a prudent policy, making its relationship whith Iran a focus of regional and international that it expressed since the advent of the Islamic Revolution in Iran in 1979 . the location of the Sultanate of Oman in the Arabian Gulf made it between the two major poles of conflict in the Gulf and the region Iran and Sauadi Arabia despite this it was able to maintain a balanced policy towards Iran as the Sultanate of Oman was able to adopt a balanced position in its foreign policy, unlike the rest of the countries in the region, at a time when the middle East witnessed many events and experiences that made some countries seek to find a space for alliances and join them . the Sultanate of Oman is considered among all the Gulf cooperation Council countries to be the most comfortable country towards Iran this is a result of the balanced behavior that the Sultanate of oman follows in its foreign policy towards Iran as a way to maintain its security because it does not see, in light of its capabilities to deter military threats rather, by managing the threads of balance through calming external threats in the Arabian Gulf it seeks as much as possible to be a source of regional and international trust in order to maintain a balance between the conflicting interests of its neighbors and its supreme national interest represented by its security within a foreign policy that places national intersts and avoiding conflicts as a fundamental goal in its orientations, even after the invasion of Iraq by the United states of America in 2003, to the liberation of the British sailors hostages in 2007 and the effective role the Sultanate of Oman in resolving these crises. أن علاقة سلطنة عُمان مع إيران علاقة تتميز عن غيرها من دول مجلس التعاون الخليج العربية من حيث العلاقات السياسية التاريخية ، والذي ميز هذه العلاقة العامل الجغرافي وطبيعة سياسة سلطنة عُمان الخارجية وخاصة عندما تولى السلطان قابوس بن سعيد سلطنة عُمان وجعل من سياستها الخارجية منطلقاً نحو سياسة حصيفة جعل من علاقتها مع إيران محط وساطة إقليمية ودولية عبرت عنها منذ مجئ الثورة الإسلامية في إيران عام 1979 . أن موقع سلطنة عُمان في الخليج العربي جعل منها ما بين قطبي الصراع الكبيرين في الخليج والمنطقة ايران والسعودية ورغم ذلك فإنها استطاعت من ان تحافظ على سياسة متوازنة تجاه إيران حيث أستطاعت سلطنة عُمان من تبني موقف متوازن في سياستها الخارجية عكس بقية دول المنطقة في وقت شهدت منطقة الشرق الأوسط العديد من الأحداث والتجارب جعلت من بعض الدول تسعى الى إيجاد مساحة من التحالفات والانضمام إليها وتُعد سلطنة عُمان من بين جميع دول مجلس التعاون الخليجي هي الدولة الأكثر أرتياحاً تجاه ايران ، وهذا نتيجة السلوك التوازني الذي تتبعه سلطنة عُمان في سياستها الخارجية تجاه ايران كسبيل للحفاظ على آمنها . لأنها لا ترى في ضوء ما تمتلكه من قدرات على ردع التهديدات العسكرية ، وانما من خلال إدارة خيوط التوازن عبر تهدئة التهديدات الخارجية في الخليج العربي . فهي تسعى قدر الأمكان لكي تكون موضع ثقة إقليمية ودولية ، لأجل الحفاظ على التوازن بين المصالح المتضاربة لجيرانها وبين مصلحتها القومية العُليا المتمثلة بأمنها في ضمن سياسة خارجية تضع المصالح الوطنية والبُعد عن الصراعات كهدف أساسي في توجهاتها حتى بعد غزو العراق من قبل الولايات المتحدة الامريكية عام 2003 . الى تحرير الرهائن البحارة البريطانيين عام 2007 ودور سلطنة عُمان الفعال في حل هذه الأزمات.
Keywords: Politique étrangère -- Oman -- 1970-2020; Relations -- Oman -- Iran

Omani Folk Literature and Its Impact on Society - Siddig, Omer (Journal of Cultural Analysis and Social Change, 2025)
Omani folk literature represents a living mirror of the cultural and historical identity of Omani society, reflecting its values, traditions, and worldview through various forms such as Nabati poetry, folktales, proverbs, chants, and performing arts. This literature serves as a repository of collective experiences and a medium for documenting the social, political, and economic transformations Oman has undergone throughout the ages. Folk literature has significantly contributed to strengthening social cohesion by embedding moral and religious values and reinforcing intergenerational bonds through the exchange of stories and proverbs that carry profound wisdom and human experiences. It has also played an educational and awareness-raising role, instilling positive principles such as courage, generosity, and solidarity. Moreover, Omani folk literature has had a notable impact on shaping national consciousness and fostering belonging, as it celebrates heritage, maritime and agricultural traditions, and Oman’s historical role in trade and navigation. With the evolution of Omani society, folk literature has remained a vital tool for preserving cultural identity in the face of globalization, as well as a key pillar in academic studies of heritage and anthropology. Therefore, studying Omani folk literature reveals its central role in nation-building, not merely as a cultural luxury but as a fundamental force in shaping the Omani character and safeguarding its cultural legacy.
Keywords: Littérature -- Oman

العلاقة بين سلطنة زنجبار وألمانيا في عهد السلطان خليفة بن سعيد (1888 – 1890م): دراسة وثائقية - الجهورية, أحلام بنت حمود (دورية کان التاريخية: المستقبل الرقمي للدراسات التاريخية, 2025)
شهدت العلاقات بين سلطنة زنجبار وألمانيا خلال فترة حكم السلطان خليفة بن سعيد (1305-1307هـ/ 1888-1890م) تقاربًا على المستوى الدبلوماسي، وتجاذبًا على المستوى السياسي، حيث تزامن اعتلاء السلطان خليفة بن سعيد عرش زنجبار مع اعتلاء ولهلم الثاني (1305-1336هـ/ 1888-1918م) -الشهير في المصادر العربية بالملك غليوم الثاني-عرش ألمانيا. وتوجد نماذج من المراسلات المتبادلة بين السلطان خليفة بن سعيد والامبراطور ولهلم الثاني لدى هيئة الوثائق والمحفوظات الوطنية بسلطنة عُمان، منها: رسالة تعزية من السلطان خليفة إلى الملك ولهلم الثاني بوفاة والده وتهنئته باعتلائه العرش، ورسالة شكر من الملك ولهلم الثاني إلى السلطان خليفة متمنيا من خلالها استمرار العلاقات الودية بين الطرفين. ورسالة شكر من المستشار الألماني بسمارك إلى السلطان خليفة بن سعيد على الوفد المُرسل من قبله لتهنئة الملك بتولي الحكم وغيرها من المراسلات. كما تم عقد اتفاقية اقتصادية بين السلطان خليفة بن سعيد والشركة الألمانية الأفريقية، والمعروفة تاريخيًا باتفاقية تأجير البر الأفريقي، وتم توقيعها في 16 شعبان 1305هـ/ 28 أبريل 1888م، وتتضمن الاتفاقية خمسة عشر بندًا. وخرجت الدراسة بعدد من النتائج، أبرزها أن جذور العلاقات التاريخية الرسمية بين الألمان وسلطنة زنجبار تعود إلى عهد السلطان ماجد بن سعيد بتوقيعه اتفاقية تجارية مع المدن الهانزية الحرة الألمانية: (لوبيك، بريمن، هامبورغ) حول المصالح التجارية المشتركة بين الطرفين، والموقعة بتاريخ: 11/11/1275هـ -13/6/1859م. كما توصلت الدراسة إلى أن العلاقات الألمانية مع سلطنة زنجبار في عهد السلطان خليفة بن سعيد اتخذت بعدين، البعد السياسي- الاقتصادي (الاستعماري)، وهذا يظهر من خلال الشركة الألمانية الأفريقية ومحاولتها التعدي على أملاك سلطنة زنجبار. والبعد الدبلوماسي، ويظهر من خلال المراسلات الودية بين الجانبين، وتبادل السفراء، والوفود والهدايا.الاستشهاد المرجعي بالدراسة:أحلام بنت حمود الجهورية، "العلاقة بين سلطنة زنجبار وألمانيا في عهد السلطان خليفة بن سعيد (1888 – 1890م): دراسة وثائقية".- دورية كان التاريخية.- السنة الثامنة عشرة- العدد الثالث والسبعون؛ نوفمبر 2025. ص150 – 171.
Keywords: Relations -- Zanzibar -- Allemagne

بنو مكي اللواتيين في قابس دراسة في اوضاعهم السياسية (٦٢٥ - ٧٩٦هـ/۱۲۲۷ - ۱۳۹۳م) - محمد, نهى احمد (مجلة مركز بابل للدراسات الانسانية, 2025)
The history of the Hafsid state (625-981 AH / 1227-1573 AD) witnessed the emergence of many families that ruled many cities in the country as deputies of the central authority in Tunisia. These families oscillated in the ruling authority between the ebb and flow of sometimes with complete dependence and sometimes with only nominal dependence and in many cases by declaring complete independence. Among these families is the Banu Makki family, which belongs to the Berber tribe of Lawata, whose star shone in the city of Gabes during the reign of Sultan Abu Zakaria al-Hafsi (625-647 AH / 1227-1249 AD), who appointed them as his deputies in ruling Gabes. However, their loyalty to the central authority soon changed with the beginning of signs of weakness in the state, as they declared their independence from the ruling authority in Tunisia, thus establishing their hereditary emirate, which was ruled by five princes. Due to the importance of the history of these families in that it sheds light on the overall conditions of that era, we chose to study this family in a comprehensive study. The research came in several paragraphs. In the first paragraph, we discussed the city of Gabes from its inception until the era of this family. In the second paragraph, we talked about the lineage of Banu Makki and their appearance on the stage of political life. As for the third paragraph, it came to talk about their most prominent princes. Arriving at the fourth paragraph, which included talking about the relationship of this family with the central authority on the one hand and the other princes who lived with it on the other hand.
Keywords: Lawata -- Gabes

La composition tribale de l'armée ibadite au Maghreb médiéval - Haddaji, Aymen (Middle East Journal of Scientific Publishing, 2025)
La composition de l’armée ibadite au Maghreb durant la période médiévale fut soumise à de nombreux facteurs et circonstances, rendant sa structure tribale instable et en perpétuelle évolution. Dans cet article, nous nous proposons d’analyser cette composition en examinant les contributions des tribus berbères à cette armée à travers deux grandes étapes : celle de la fondation de l’État ibadite (à Tripoli et à Tahert), et celle des révoltes ibadites, en particulier la révolte d’Abû Yazîd et l’insurrection de Bâghây au IVe siècle de l’hégire / XIe siècle de l’ère chrétienne.
Keywords: Baghaï, Ksar (Baghaya, Algérie); Conflits -- Afrique du Nord; Ibn Kaydad

Measuring the Corporate Entrepreneurship in the Hotel sector in Djerba island (Tunisia) during a critical period - Hadj Hassine, Abir (Revue internationale des sciences de gestion, 2025)
This paper investigates the concept of Corporate Entrepreneurship (CE) in the Tunisian hotel sector, focusing on Djerba Island during a critical period marked by the 2015 terrorist attacks that severely impacted tourism. The study relies on Zahra’s (1996) conceptual framework, defining CE as a multidimensional construct encompassing Innovation, Corporate Venturing, and Strategic Renewal. An empirical survey was conducted among managers and department heads of 26 operational hotels in Djerba, totaling 158 respondents. Data were analysed using exploratory and confirmatory factor analyses to assess the validity and multidimensionality of CE in this context. Results indicate that CE is a measurable multidimensional construct, with process innovation being the most emphasized dimension, followed by product and organizational innovation, corporate venturing initiatives, and strategic renewal. This research contributes to the literature by providing empirical evidence of CE during a crisis in the hotel sector and offers practical insights for management and decision-making.
Keywords: Tourisme -- Djerba

The Trajectories of Separation: Transatlantic Networks, Disciplinary Boundaries, and the Isolated Histories of Mizrahim - Gerber, Noah S.; Moreno, Aviad (AJS Review: The Journal of the Association for Jewish Studies, 2025)
Most sociological and ethnographical studies of Israeli Mizrahim are disconnected from those of Sephardic and MENA Jewish communities worldwide. Rooted in academic cultures that predate the country's establishment, Mizrahi history in Israel is often deemed either a success story or a shameful story of marginalization in these communities' global histories, and as a sui generis case of Jewish migration. We trace the early origins of this seemingly arbitrary disconnect to nineteenth-century European scholarship on "Sephardic" turned "Oriental" Jews and follow its subsequent entrenchment not only in Mandate Palestine and Israel but also in the United States. By focusing on key scholars working across transregional networks, we show how a Sephardic bias evolved into disciplinary divisions that have constrained the development of MENA Jewish studies. Finally, we call for renewed attention to the historical and contemporary patterns of separation, diffusion, and diasporic mobility that have long characterized MENA Jewish communities.
Keywords: Judaïsme -- Djerba; Judaïsme -- Mzab

الحركة العلمية في الدولة الرستمية 160 - 296 هـ/ 777 - 909 م - راشد, ريم محمود محمد (مجلة البيان العلمية المحكمة, 2025)
Keywords: Dynastie rustumide; Vie intellectuelle -- Rustumides

Tiskriwin in Aɣlan, Algeria: revitalising traditional neighbourhood committees for modern challenges - Mohammedi, Louiza; Gueliane, Nora (Journal of Urban Ethnology, 2025)
This article takes as its geographical context the M’Zab, a region known for its social, doctrinal and historical particularities, but also for its own institutional organisation. These institutions include tiskra/tiskriwin, the traditional version of neighbourhood committees that have been adapted to modern forms of association. The aim is therefore to look back at these neighbourhood committees, their origins, their organisation and their role in a Mozabite town. The research underscores the integral role of tiskriwin in promoting local solidarity and cultural continuity in the M’Zab valley. Despite evolving under national policies, these associations retain traditional wisdom and community support, ensuring their ongoing relevance in neighbourhood governance and social cohesion. To achieve this, in addition to documentary research, we carried out field surveys. The survey took place mainly in the ksar of Ghardaïa, with some return visits to the town of Béni Isguen. The aim was to find out how these tiskriwin were structured and managed, and what roles they fulfilled. By analysing all these sources, interviews and documents, we were able to understand how the tiskriwin were organised and what role they played within their communitites.
Keywords: Vie sociale -- Mzab

مدينة قلهات في المراسلات الرسمية البرتغالية (1508-1520م) دراسة وثائقية - الكيومي, سليمان بن سعيد (مجلة الشرق الأوسط للعلوم الإنسانية والثقافية, 2025)
قلهات مدينة قديمة تقع على ساحل بحر عمان، وتذكرها المصادر بأنها كانت أول عاصمة عمانية في التاريخ قبل ظهور الإسلام بعدة قرون، وقد اشتهرت كمدينة تجارية، وورد ذكرها في العديد من كتب الرحالة، مثل ابن بطوطة الذي وصفها بأنّها مركز تصدير الخيول ومنها يتم استيراد البهارات، كذلك وصفها الرحالة الإيطالي ماركو بولو في القرن الثالث عشر الميلادي في أوج ازدهارها وأطلق عليها اسم «قلاياتي، ووصفها ياقوت الحموي في كتابه معجم البلدان بقوله: مدينة بعمان على ساحل البحر إليها ترفأ أكثر سفن الهند." عندما قدم البرتغاليون للمنطقة مع مطلع القرن السادس عشر الميلادي قاموا بالسيطرة على بعض المدن العمانية الساحلية، وكانت قلهات من أوائل المواقع التي سيطروا عليها، ومنذ السيطرة البرتغالية على المدينة نجد اسم قلهات يتردد كثيرا في الوثائق والمراسلات البرتغالية، سواء في مجال التجارة أو في المجال العسكري أو غيرها من الأحداث العامة، حيث أصبحت قلهات مركز تجاريا وعسكريا للأسطول البرتغالي في الفترة من 1507- 1649م. ومن هنا تأتي هذه الدراسة من أجل تتبع ومناقشة ما دونه البرتغاليون في مراسلاتهم الرسمية حول قلهات أثناء فترة وجودهم في المنطقة، وقد صنف الباحث تلك المراسلات في مجالين ، المجال الأول هو المراسلات البرتغالية حول السيطرة على قلهات، والمجال الثاني يتعلق بالمراسلات البرتغالية الخاصة بالنشاط التجاري لمدينة قلهات في  فترة السيطرة البرتغالية. سوف تعتمد الدراسة على العديد من الوثائق البرتغالية التي تعود إلى فترة الوجود البرتغالي على سواحل عمان والخليج العربي، والتي نشرت مؤخرا في عدة مجلدات، حيث سيقوم الباحث في هذه الدراسة بفرز وتحليل الوثائق التي تطرقت إلى موضوع الدراسة، وذلك من أجل الوصول إلى صورة متكاملة عن الوضع العسكري والتجاري في قلهات في فترة السيطرة البرتغالية.
Keywords: Relations -- Oman -- Portugal; Sources -- Oman

واکاوی عملکرد خوارج اباضیه از پیدایش تا فروپاشی حکومت رستمیان در مغرب - فتاحی, قاسم; ظفریان, داراب (پ‍‍‍ژوهش‌نامه فرهنگ و معارف دینی, 2025)
چکیدههدف این پژوهش واکاوی سیر تحولات تاریخی پیدایش خوارج اباضیه از ظهور این فرقه تا سقوط دولت رستمیان در مغرب است. در ابتدا بنا بر ضرورت ضمن اشاره‌ای کوتاه به تاریخ پیدایش خوارج و فرقه‌های مختلف آن بویژه اباضیان، به علل و چگونگی ورود خوارج اباضیه به شمال آفریقا و تشکیل دولت بنی‌رستم(رستمیان) در مغرب و تحولات دوران حکومت آنان پرداخته شده است. اهمیت بررسی تاریخ این فرقه در آن است که اباضیان با گرایش به اعتدال‌گرایی و پرهیز از خشونت که از ویژگی‌های اصلی خوارج بود، توانستند تا زمان حاضر هم‌چنان به حیات خود در جامعه اسلامی ادامه دهند. روش انجام این تحقیق، توصیفی - تحلیلی بوده و به منظور گردآوری داده‌ها برای پاسخ‌گویی به سوالات پژوهش، اسناد و مدارک مرتبط با موضوع مورد تجزیه و تحلیل قرار گرفته است. نتایج حاصل از این پژوهش نشان می‌دهد که عقاید فرقة اباضیه بنا به دلایل سیاسی، اجتماعی، اقتصادی و فرهنگی در مغرب اسلامی مورد پذیرش بربران قرار گرفته و به مرور زمان گسترش یافت، تا جایی که اباضیان با انتخاب «عبدالرحمن بن رستم» به عنوان امام، و تأسیس سلسله رستمیان به مرکزیت شهر تاهرت، عصر طلایی اباضیان مغرب را رقم زدند. حکومت رستمیان مغرب در تجربه بسیار موفقی در این مذهب به شمار می‌رود که ضمن ارائه خدمات کم نظیر اقتصادی، عمرانی، فکری، سیاسی، اجتماعی و علمی، در مجموع حکومتی مقبول و نمونه خوبی از تمدن و میراث شهری از خود بر جای گذاشتند.
Keywords: Dynastie rustumide

The Ottoman Ibadis of Cairo: A History by Paul M. Love Jr. (review) - Pierce, Stephen (African Studies Review, 2025)
Keywords: Recension

The Ottoman Ibadis of Cairo: A History by Paul M. Love Jr. (review) - Sabra, Adam (Manuscript Studies: A Journal of the Schoenberg Institute for Manuscript Studies, 2025)
Keywords: Recension

Acteurs et itinéraires du commerce des esclaves au temps des empires soudanais Soninké et Manding - Coulibaly, Pédiomatéhi Ali (Rivages, 2025)
This study analyzes the actors, networks, and commercial routes that structured the trans-Saharan slave trade during the Soninke and Manding empires (8th–13th centuries) through a critical examination of Arabic-Islamic sources, including alYaʿqūbī, al-Idrīsī, Ibn al-Fakīh, and Ibn Ḥawqal, supplemented by modern historiography. While the trade predated Islam, it intensified significantly following Arab-Berber expansion into the Sahel, operating through collaboration between Sudanese rulers who organized slave raids and market provisioning, and Maghrebi and Eastern merchants (particularly Ibadite Berbers) who established purchasing posts, financed caravans, and secured desert passage. Three principal itineraries channeled enslaved populations northward: the western Tahert–Sijilmassa–Awdaghost–Ghana axis; the Tripoli–Zawila–Kanem corridor linking Fezzan to Lake Chad; and an Egypt–Ghana route traversing Gao, Kawar, and the Kharga/Dakhla oases. Religious-legal discourse, notably the equation of unbelief (kufr) with enslavability, as articulated in Aḥmad Bābā's legal opinions, and elite demand for luxury commodities sustained capture and exchange, with urban centers like Koumbi Saleh, Awdaghost, Gao, and Zawila serving as nodal points. By correlating political chronologies with documented caravan geography, the research illuminates how state authority, commercial mediation, and desert infrastructure converged to transform localized enslavement into systematic trans-Saharan labor traffic supplying North Africa and the Middle East.
Keywords: Commerce transsaharien

Aillet, Cyrille. L’archipel ibadite. Une histoire des marges du Maghreb médiéval. Collection Mondes Médiévaux. Lyon: CIHAM-Éditions, 2022. ISBN: 9782956842644. 592 pp. €45 paper. - Bosanquet, Antonia (Al-ʿuṣūr al-wusṭa, The Bulletin of Middle East Medievalists, 2025)
Keywords: Recension

الروابط الحجاجية ودورها في بناء الواقع الشعري عند أبي سلام الكندي العماني (1960م) - حالو, أحمد عبد المنعم; الريامي, محمود بن سليمان; حالو, شمس الإسلام (حوليات آداب عين شمس, 2025)
Keywords: Poésie -- Oman

دور المرأة العمانية في تحقيق الاستدامة في ضوء رؤية عمان 2040 - العبرية, ليلى بنت سويد بن سعيد (المجلة العربية للإدارة, 2025)
Keywords: Vie politique -- Oman -- 2020-....

Using Artificial Intelligence in Managing Renewable Energy Projects in the Western Mountains (Gharyan, Jadu, and Nalut) - Abughalia, Jalal al-Mahdi; Farjani, Abdullah Younis al- (Libyan Journal of Contemporary Academic Studies, 2025)
This study aims to explore the potential of using artificial intelligence (AI) in managing renewable energy projects in the Western Mountains of Libya, specifically in Gharyan, Jadu, and Nalut. The research relied on a theoretical and environmental analysis of the three regions, a survey of expert opinions, and statistical analysis using tools such as SPSS and Python to develop prototypes that contribute to improving production and operational efficiency. The results demonstrated promising opportunities for adopting smart renewable energy in these regions, with the need to strengthen infrastructure and train local talent. The study also proposed a practical vision for establishing solar and wind power plants, as well as smart models for production forecasting and predictive maintenance. The study concludes with technical and regulatory recommendations to accelerate the implementation of these projects in line with the global transition to sustainable energy.
Keywords: Développement durable -- Djebel Nefousa

ʿUdūl in the Practice of Islamic Law: Notarial Ledgers from 19th-Century Tunisia - Masmoudi, I. A. (Islamic Law and Society, 2025)
Abstract This article analyzes ‘udūl ledgers from southern Tunisia in the late 19th-century to answer two questions: how useful are they as a source for historical study, and what can they tell us about the role of ‘udūl in the daily practice of Islamic law? On the first question, I suggest the ledgers are likely a reliable source of history and constitute an untapped archive for an understudied region. I also offer a guide to deciphering their difficult pages. On the second question, I suggest that the function of ‘udūl in the practice of Islamic law was more significant than previously recognized. Far from being mere judges’ assistants, notaries were independent legal practitioners who served broad segments of society with their scribal skills, provided a stable foundation for the enforceability of contracts and the establishment of facts, and likely intervened in the agreements they recorded, educating the parties on the relevant law and helping to resolve disputes.
Keywords: Notariat -- Djerba

رحلة السلطان برغش بن سعيد إلى أوروبا عام 1875م - الكيومي, سليمان بن سعيد (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2025)
Sultan Barghash bin Said ruled the Sultanate of Zanzibar from 1870 to 1888 AD. His reign was marked by many achievements in the cultural, civilizational and economic fields, as Sultan Barghash was a lover of science and eager to develop and introduce civilization to Zanzibar. On the cultural level, he established the Royal Press, attracted scholars to Zanzibar, and printed books. In the field of construction, he focused on building palaces and introducing electricity and water networks to Zanzibar. Some researchers believe that Sultan Barghash's idea of development was the result of the Sultan's trip to Egypt and European countries in 1875 AD, during which he saw the development those countries had achieved in all fields. When he returned from his trip, he began implementing some of the civilisational projects he had seen. From this perspective, this paper discusses Sultan Barghash's journey to Europe in 1875 AD, examining its route, the Sultan's companions, the Sultan's observations in the countries he visited, and the extent to which this influenced Sultan Barghash's development policy in Zanzibar after his return from that trip. The researcher will rely mainly in covering this topic on the book “Tanzih al-Absar wa al-Afkar fi Journey of Sultan Zanzibar” by its author Zahir bin Saeed, considering that it is the main source for the details of Sultan Barghash’s journey to Europe, as Zahir bin Saeed was accompanying the Sultan. It describes the events and what the Sultan and his companions witnessed on that journey from their departure from Zanzibar in 1875 AD until their return in the same year, in addition to the sources and references that dealt with the reign of Sultan Barghash.
Keywords: Récits de voyage -- Zanzibar

The three voyages of Black Eagle: Piracy, transnationality and the first French East India Company’s flagship - Belhacel, Abdelhakim (International Journal of Maritime History, 2025)
This article explores the story of the French East India Company’s first flagship, originally a Dutch-built privateer vessel, from its inception in the 1660s through three significant voyages. Through an analysis of travel accounts, archival documents and secondary literature, the study explores how the ship’s transformation into a symbol of French ambition reflects the broader struggles of France’s imperial ventures under Louis XIV. Initially named Black Eagle and infamous for piracy, the vessel was repurposed as Saint-Paul and served in the nascent French East India Company. Its voyages highlight challenges such as disease, lack of maritime expertise and strained resources, which hindered the Company. By examining the ship’s role, this article sheds light on the transnational networks, political rivalries and economic aspirations that shaped France’s entry into the Indian Ocean trade. The study highlights the relationship between a ship’s tumultuous history and the French East India Company’s strategic ambitions and transnational entanglements.
Keywords: Commerce -- France

الأثر الجيومورفولوجي لسد وادي زارت في مرتفعات نفوسة -ليبيا - أبو حربة, الصديق مولود (مجلة شمال إفريقيا للنشر العلمي, 2025)
Keywords: Géologie -- Djebel Nefousa

Rapatriement en France métropolitaine et migration en Israël des Juifs d’Algérie : deux faces d’une expérience migratoire postcoloniale - Scioldo-Zürcher, Yann (Archives Juives, 2025)
Keywords: Judaïsme -- Mzab

أحكام البغاة عند الإمام السالمي ومبادي القانون الدولي الإنساني (دراسة مقارنة) - الحوسني, صالح بن سعيد (مجلة بحوث الشريعة, 2025)

الإمام الصلت بن مالك وجهوده في التنظير للقواعد المنظمة للنزاعات المسلحة - الندوي, سيد أزهر (مجلة بحوث الشريعة, 2025)

دور الفكر الإباضي في تشكيل المشروعية السياسية للدولة الرستمية في عهد عبد الرحمن بن رستم (160-171هـ/ 777-787م) - أبو نحل, أسامة محمد (دورية کان التاريخية: المستقبل الرقمي للدراسات التاريخية, 2025)
تُعتبر الدولة الرستمية (160-296هـ/ 777-909م)، التي أسسها عبد الرحمن بن رستم، نموذجًا استثنائيًا للعدالة في التاريخ الإسلامي بعد عصر الخلفاء الراشدين وعهد الخليفة الأموي عمر بن عبد العزيز، حيث دمجت بين الفِكر والسياسة في أول تجربة إباضية مستقرة بالمغرب الإسلامي. تأسست شرعية الدولة الرستمية في فترة عبد الرحمن بن رستم (160-171هـ / 777-787م) على الفكر الإباضي، الذي أرسى مبادئ الشورى والعدل كأساس للحكم. جاءت بيعته نتيجة لمكانته العلمية وتقواه، وفق آليات الاختيار الجماعي. وساهم الخطاب الإباضي في توحيد القبائل البربرية لمقاومة الظلم ورفض الهيمنة العباسية، مما عزز الاستقلال السياسي والثقافي للدولة. اتسم عهده بالتسامح مع المخالفين مذهبيًا، مما ساهم في الاستقرار والازدهار الفكري والاقتصادي. اعتمدت الدراسة الراهنة المنهج التاريخي، والوصفي التحليلي، ونظرية صنع القرار، بهدف عرض الخلفية التاريخية والفِكرية لتأسيس الدولة الرستمية. وتحليل نشأة الدولة الرستمية وتأثير المبادئ الإباضية في تشكيل مشروعيتها السياسية. وتوصلت إلى أن اختيار ابن رستم للإمامة كان بسبب عدله وعدم امتلاكه سند قبلي، مما عزز مراقبة تصرفاته. الاستشهاد المرجعي بالمقال:أسامة محمد أبو نحل، "دور الفكر الإباضي في تشكيل المشروعية السياسية للدولة الرستمية في عهد عبد الرحمن بن رستم (160-171ه / 777-787م)".- دورية كان التاريخية.- السنة الثامنة عشرة- العدد الثاني والسبعون؛ أكتوبر 2025. ص 31 – 44.
Keywords: Dynastie rustumide

أثر التنظيم التشريعي على واقع تنمية الأوقاف في سلطنة عمان من وجهة نظر المؤسسات الوقفية - الغافرية, زهرة بنت علي; بن صالح, يوسف; روسل, محمد إخلاص (مجلة إسرا الدولية للمالية الإسلامية, 2025)
المستخلص عرف المسلمون الوقف منذ عهد النبي صلى الله عليه وسلم، وقامت الدولة الإسلامية على الأوقاف إلى أن أصبح الوقف مصدرًا تمويليًا ضخمًا، موَّل الدولة في مختلف قطاعاتها الدينية، والصحية، والاجتماعية والعسكرية، ملبيًا بذلك الضرورات الخمس من حفظ الدين، والنفس، والعقل، والنسل، والمال، ولابد لاستقامة أي عمل من تنظيم قانوني، ولابد لهذا التنظيم أن تؤطره الشريعة الإسلامية بما يتناسب مع مستجدات العصر في حال الوقف؛ لذا فإن هذه الدراسة تعالج إشكالية التنظيم التشريعي وأثره على واقع تنمية الأوقاف في سلطنة عمان من وجهة نظر المؤسسات الوقفية، وشملت الدراسة عينة قصدية تتكون من 28 فردًا من القائمين على المؤسسات الوقفية في سلطنة عمان، واستخدم البحث المنهج الوصفي والمنهج التحليلي لإجراء الدراسة، وخلصت إلى أن هناك تحديات تواجه التنمية الوقفية في سلطنة عمان من وجهة نظر المؤسسات الوقفية تتمثل في انخفاض الكفاءة الإدارية، والتعددية في الاستثمار الوقفي، والشمول في القوانين الوقفية، مما يؤثر على الاستدامة التنموية، ويبرز الحاجة إلى إصلاحات قانونية، وتطوير استثمارات مبتكرة، وتعزيز الحوكمة لضمان استدامة الوقف وتحقيق أثر اقتصادي واجتماعي شامل. كلمات مفتاحية: التشريعات، الوقف، التنمية، المؤسسة الوقفية، القائمين على الأوقاف.
Keywords: Waqf (fondations) -- Oman

اقسام و دلایل توحید نزد اباضیه - شریفی, مصطفی; سلطانی, مصطفی; قاسمی, ابراهیم (پژوهشنامه مذاهب اسلامی, 2025)
مسئله توحید، مهم‌ترین اصل اعتقادی بین مسلمانان است. توحید به معنای یگانه‌دانستن خداوند در همۀ ابعاد وجودی است و اولین پیام و آموزه دعوت حضرت محمد (ص) در آغاز رسالت به شمار می‌رود؛ دعوت انسان به کلمه «لا اله الا الله». با شهادت بر این کلمه و اذعان به آن که دربرگیرندۀ چیزی جز شهادت بر یکتایی خدا و دوری از شرک نیست، فرد مسلمان خوانده می‌شود. به توحید در آموزه‌های قرآن کریم و روایات پیامبر اکرم (ص) توجه ویژه‌ای شده است که با جستجو در آیات قرآن به اهمیت آن پی خواهیم برد. خداوند متعال به ‌سبب اهمیت این مسئله و برای رفع هرگونه شبهه، سورۀ «توحید» را نازل کرده است و مسئلۀ توحید را در این سوره به انسان‌ها یادآور می‌شود. اباضیه از مذاهب اسلامی پویا و زنده در جهان اسلام است که با توجه به شواهد تاریخ از ابتدایی‌ترین مذاهب و فرقه‌های اسلامی است. شناخت صحیح دیدگاه این فرقه می‌تواند راهگشای حل بسیاری از اختلاف‌ها در جهان اسلام باشد. اباضیان در مباحث توحید از اصطلاح «جملة التوحید» استفاده کرده‌اند و ادعا می‌کنند از اصطلاحات خاص اباضیان است. عالمان اباضیه معتقدند تفکر و نگاه ایشان به توحید، تمام اقسام الحاد و تشبیه و تجسیم را دفع می‌کند. موضوع علم توحید، صفات خداوند متعال، صفات پیامبران الهی و ممکنات است از آن حیث که به ‌وسیله ممکنات وجود صانع ثابت می‌شود. اباضیان افراد منکر توحید را به سه دسته تقسیم می‌کنند و قائل به مشرک‌بودن دو دستۀ اول هستند؛ اما دربارۀ وجه سوم معتقدند این فرد کافر کفر نعمت است. در این مقاله به بررسی دیدگاه اباضیه دربارۀ مسئلۀ توحید می‌پردازیم.
Keywords: Foi -- Ibadisme

تاريخ القراء في جبل نفوسة قراء نالوت أنموذج - المقدمي, نادية عيسى خليفة (المجلة الأفروآسيوية للبحث العلمي, 2025)
The research addresses the topic of Quran readers in Jabal Nafusa, particularly in the city of Nalut, shedding light on how the Quran was transmitted and preserved. It aims to answer questions regarding the first reader in the area, the methods of memorization used, and the most famous readers. Additionally, it seeks to clarify the role of Nafusa's readers in preserving the Quran and the reasons for its spread in the community. The research is structured into an introduction and two main sections, with the first focusing on the history of readers in Jabal Nafusa and the second on the history of readers in Nalut. The researcher employed a historical narrative approach and analysis to utilize various sources. It is hoped that this work will be a step toward documenting the history of the city's readers.
Keywords: Coran -- apprentissage

Qalhat, A Medieval Port City of Oman. From a field of ruins to UNESCO - Chung-To, Guillaume (Bulletin critique des Annales islamologiques, 2025)
Keywords: Archéologie -- Oman

The karst landscape of the Dhofar Mountains (Sultanate of Oman). Landforms and human exploitation at the edge of the Indian Ocean Monsoon - Zerboni, Andrea; Pezzotta, Andrea; Azzoni, R. S.; Cremaschi, Mauro (2025)
4
Keywords: Archéologie -- Oman

The Mozabite Heritage: Authenticity of Identity and Continuity of Existence. - Mammar, Chachoua (Djoussour El-maarefa, 2025)
This study aims to highlight the importance of the Mozabite heritage in southern Algeria, in terms of its characteristics and features. This includes tangible heritage such as fortified cities (ksour) and towns with their Islamic architectural style, as well as manifestations of intangible heritage found in the customs and traditions that distinguish the Mozabite community and which it has preserved since ancient times. The study concludes that the Mozabite society has remained cohesive through the customs and traditions of their forefathers, passed down through generations. The community has continued to uphold its spiritual and social values to this day. Additionally, some of the ksour in the M‟zab Valley have maintained their architectural style. However, natural and human factors have begun to threaten the integrity of this tangible heritage, making it necessary for the state to intervene in order to restore and protect these ksour from disappearing, as they represent a shared human heritage.
Keywords: Architecture -- Mzab

Amal Sachedina, Cultivating the Past, Living the Modern: The Politics of Time in the Sultanate of Oman:Cornell, Cornell University Press, 2021 274 pages - Ayachi, Mehdi (Critique internationale, 2025)
Keywords: Recension

التراث المائي الإسلامي بين الحكم الفقهي والتطبيق الهندسي (كتاب القسمة وأصول الأرضين (ق05هـ/11م) أنموذجا) - عناق, جمال (مجلة التراث العلمي العربي, 2025)
أدرك المسلمون منذ القدم أهمية الماء كمصدر للحياة، مما جعلهم يولون له عناية خاصة في مختلف تصنيفاتهم الجغرافية والتاريخية والفقهية، ومراعاة لعنصر الماء فقد تنوعت أحكام الفقهاء حسب مضامينها الوظيفية الدنيوية أو الدينية. فراح هؤلاء يجمعون أحكاما متنوعة للمياه في أبواب وأجزاء متكاملة تعكس مدى ما وصل إليه المسلمون من تقدم في حل اشكالية الندرة والخصومة التي تنتج عنها خاصة بين المزارعين والفلاحين. ولعل أبرز هؤلاء الفقهاء نجد "أبا العباس الفرسطائي" الذي عاش في القرن الخامس الهجري الحادي عشر الميلادي والذي أفرد ابوابا في كتابه: "القسمة وأصول الارضين" ليتناول الحلول المناسبة لمختلف مسائل المياه.
Keywords: Irrigation -- Mzab

جهود علماء الإباضية في تفسير القرآن الكريم - عبدالرحمن, محمد حسن محمد (مجلة كلية الشريعة والقانون, 2025)
Keywords: Coran -- Commentaires

Notes et documents. Le Maghreb dans la recherche académique allemande. Représentations, explorations et enjeux - Ouaïssa, Rachid (Maghreb-Machrek, 2025)

موقف سلطنة عمان من الأزمة الخليجية - القطرية عام 2017 - عطية, ريا مجيد; سليم, ماجد عجيمي (الملوية للدراسات الآثارية والتاريخية, 2025)
Discover this 2025 paper in Al Malweah for Archaeological & Historical Studies by ريا مجيد عطية; and, ماجد عجيمي سليم Abstract: In 2017, the Gulf crisis erupted between Qatar on one side, and Saudi Arabia, the United Arab Emirates, and Bahrain on the other, following the severing of diplomatic and economic ties with Qatar and accusations of its support for terrorism. However, the Sultanate of Oman took a different stance from its Gulf neighbors. Moreover, Oman adopted a policy of positive neutrality in the crisis, avoiding alignment with any of the conflicting parties. It also sought to play a mediating role between the rivals, calling for dialogue and de- escalation.
Keywords: Politique étrangère -- Oman -- 1970-2020

نهج السلطان قابوس في احتواء وتحييد النفوذ القبلي فس سلطنة عمان - الخروصية, شيخة بنت عمر (دراسات عربية في التربية وعلم النفس, 2025)
Keywords: Vie politique -- Oman -- 1970-2020

Zanzibar was a Country: Exile and Citizenship between East Africa and the Gulf by Nathaniel Mathews (review) - Vartavarian, Mesrob (Global Black Thought, 2025)
Keywords: Recension

الخصائص الطبوغرافية والجيومورفولوجية للجبل الغربي في ليبيا:دراسة تحليلية مدعمة بالبيانات المكانية - سعيد الحاج, زعيمة (المجلة الأفروآسيوية للبحث العلمي, 2025)
Keywords: Géologie -- Djebel Nefousa

العلاقات العُمانية اليمنية في ضوء النضال العُماني ضد الاحتلال البرتغالي خلال فترة حكم الإمام سلطان بن سيف اليعربي 1059 – 1090 هـ/ 1649 – 1679م - الجهورية, أحلام بنت حمود (دورية کان التاريخية: المستقبل الرقمي للدراسات التاريخية, 2025)
قام الإمام سلطان بن سيف اليعربي (1059-1090هـ/1649-1679م) بدورٍ مهمٍ وحاسمٍ في إنهاء الاحتلال البرتغالي على بعض أجزاء السواحل العُمانية، كما تتبع البرتغاليين في سواحل اليمن والمحيط الهندي. وكان لهذا النضال أثره على العلاقات العُمانية اليمنية؛ لاعتبارات كثيرة يأتي على رأسها الموقع الجغرافي الاستراتيجي المهم الذي تتقاسمه عُمان واليمن. وقد تزامن حكم اليعاربة في عُمان مع حكم أئمة الزيدية في اليمن عُمومًا، كما تزامن حكم الإمام سلطان بن سيف اليعربي في عُمان مع حكم الإمام المتوكل إسماعيل بن القاسم (1054-1087هـ/ 1644-1676م) في اليمن، وخلفه في حكم اليمن الإمام أحمد بن الحسن بن القاسم (1087-1092هـ/ 1676-1681م). من هذا المنطلق تهدف هذه الدراسة إلى توضيح العلاقات العُمانية اليمنية في ضوء النضال العُماني ضد الاحتلال البرتغالي خلال فترة حكم الإمام سلطان بن سيف اليعربي والإمام المتوكل إسماعيل بن القاسم الزيدي، من خلال قراءة تاريخية تحليلية في ضوء ما جاء في بعض المصادر العُمانية واليمنية. ومن خلال استقراء وثيقة تاريخية مهمة تتمثل في رسالة أُرسلت في عام 1080هـ/ 1669م، من الإمام سلطان بن سيف اليعربي إلى الإمام إسماعيل بن القاسم بن محمد، وهي بحوزة هيئة الوثائق والمحفوظات الوطنية تحت الرمز المرجعي: OM.NRAA.A.1.2.1(1)، ومقارنتها بالرسالة التي أوردها المؤرخ اليمني ابن الوزير (ت: 1147هـ/ 1734م) في كتابه: تاريخ طُبُق الحلوى وصِحاف المنّ والسلوى، والمعروف بتاريخ اليمن، وما ذكره بشأنها المؤرخ العُماني نور الدين السالمي (ت: 1332هـ/ 1913م) في كتابه: تحفة الأعيان بسيرة أهل عُمان. تتضمن الدراسة مقدمة ومبحثين وخاتمة. يركز المبحث الأول على رصد وتحليل بعض ما أوردته المصادر العُمانية واليمنية حول العلاقات بين عُمان واليمن في فترة النضال العُماني ضد الاحتلال البرتغالي. والمبحث الثاني يتناول العلاقات العُمانية اليمنية في ضوء جهود الإمام سلطان بن سيف اليعربي في إنهاء الاحتلال البرتغالي على عُمان. أما الخاتمة فتتضمن مناقشة أبرز النتائج التي توصلت إليها الدراسة.الاستشهاد المرجعي بالدراسة:أحلام بنت حمود الجهورية، "العلاقات العُمانية اليمنية في ضوء النضال العُماني ضد الاحتلال البرتغالي خلال فترة حكم الإمام سلطان بن سيف اليعربي (1059-1090هـ/1649-1679م)".- دورية كان التاريخية.- السنة الثامنة عشرة- العدد الحادي والسبعون؛ سبتمبر 2025. ص 76 – 92.
Keywords: Relations -- Oman -- Portugal; Relations -- Oman -- Yemen; Vie politique -- Oman -- 1624-1742

Cyrille Aillet, L’archipel ibadite. Une histoire des marges du Maghreb médiéval, CIHAM Éd., Lyon–Avignon, 2021 ; 1 vol., 582 p. (Mondes médiévaux, 5). ISBN : 978-2-95684-264-4. Prix : € 45,00 - Sénac, Philippe (Le Moyen Age, 2025)
Keywords: Recension

The Mozabite Heritage:Authenticity of Identity and Continuity of Existence - Chachoua, Mammar (جسور المعرفة, 2025)
This study aims to highlight the importance of the Mozabite heritage in southern Algeria, in terms of its characteristics and features. This includes tangible heritage such as fortified cities (ksour) and towns with their Islamic architectural style, as well as manifestations of intangible heritage found in the customs and traditions that distinguish the Mozabite community and which it has preserved since ancient times. The study concludes that the Mozabite society has remained cohesive through the customs and traditions of their forefathers, passed down through generations. The community has continued to uphold its spiritual and social values to this day. Additionally, some of the ksour in the M‟zab Valley have maintained their architectural style. However, natural and human factors have begun to threaten the integrity of this tangible heritage, making it necessary for the state to intervene in order to restore and protect these ksour from disappearing, as they represent a shared human heritage.
Keywords: Moeurs et coutumes -- Mzab

زوائد مسند الربيع بن حبيب الإباضي على كتب السنة، فصل الولاء والبراء بين أهل السنة والإباضية - عبد الحليم حسن, محمد (مجلة کلية الآداب, 2025)
Keywords: Hadith -- recueils

Property Confiscation in the Zanzibar Revolution - Joireman, Sandra F.; Verne, Julia (African Affairs, 2025)
The literature on the Zanzibar Revolution highlights contested views of events leading up to a short period of violence in 1964. Other studies have followed the paths of those who fled the islands of Zanzibar in the aftermath of the revolution, many of whom lost property to government confiscations. How the confiscations impacted and still inform the relation of their previous owners to Zanzibar, however, has received rather little scholarly attention. This article introduces a dataset of georeferenced property confiscation orders, originally published in the Zanzibar Gazettes between 1964 and 1987. The data contribute to our understanding of the Zanzibar Revolution by showing that the temporal arc of the Revolution was decades long and that property confiscations went beyond urban houses in Stone Town and large plantations. Property confiscations, effected by revolutionary decree, persisted into the 1980s on both Pemba and Unguja islands. By bringing the data into conversation with family histories and previous literature on the aftermath of the revolution, this article illustrates the relevance of Revolutionary era property losses for questions of identity, belonging, desire for restitution, and ongoing development efforts.
Keywords: Vie politique -- Zanzibar -- 1963-1964

الخيل في ديوان الشّاعر العماني أبي الفضل (ت 1345 هــ) - البرقاوي, بسام بن بلقاسم (مجلة العلوم الإنسانية (جامعة سبها), 2025)
نهتمّ في هذه الدّراسة بتدبّر قصائد الخيل التي نظمها الشّاعر العماني محمّد بن عيسى بن صالح الحارثي المكنّى بأبي الفضل. وممّا حفّزنا على الاهتمام بهذا الموضوع ندرة الدّراسات التي تصرف الجهد إلى تدبّر وصف الخيل عند هذا الشّاعر وغيره من الشّعراء العمانيين الذين برّزوا في هذا الغرض. ولمّا كان أبو الفضل شاعرا فارسا من فرسان عصره وقائد زمرة الخيّالة في محافظة الشّرقيّة بسلطنة عمان خصّصنا المبحث الأوّل لاستجلاء منزلة الخيل من حياة الشّاعر قبل أن نتدبّرها في شعره وخاصّة في القصائد التي سميّت بـ" الخيليات". وقد تبيّن لنا في ما تبيّن أنّ الخيل سجيّة في وجدان أبي الفضل. فهو قد نشأ عليها وشبّ في بيئة بينها وبين الخيل أسباب وأنساب. ثمّ أتينا بعد ذلك على المدوّنة الشّعريّة فوزّعناها على محورين اثنين: محور لتدبّر خصائص الخطاب الذي يكون فيه الخيل معنى من معاني القصيدة، ومحورًا لتأمّل القصائد التي اقتصر فيها القول على الخيل ولم يجاوزه إلى غيره من المعاني. وبمقاربة إنشائيّة قرأنا نماذج شعريّة أكثرها من قصائد " الخيليات". فخلصنا إلى جملة من النّتائج لعلّ أبرزها أنّ الحارثي كان شاعرا فارسا يسير على خطى المشهورين بنعت الخيل، فيرددّ ما ترسّخ في المدوّنة الشّعريّة التّقليديّة حول الخيل منزلة وصورة. لكنّه في المقابل يأتي في غير قصيدة ببعض ما لم يأت به الأوائل. ومن ذلك أنّه، فضلا عن ذكرها مشتكيا متغزّلا ومفتخرا مادحا وراثيا متألّما وساخرا متهكّما حاورها محاورة طويلة وأنطقها بكلام لم ينطقه بها غيره من الشّعراء.  وهو زيادة على وصفها في ساح المسابقات وفي ما طوّف من برور قد استنفر بعض الشّعراء ليتقارضوا معه القول في شأنها فرسا نبع من غير مثال وسُويَّ على غير منوال وفي شأنه فارسا مغوارا لا يشّق له غبار.
Keywords: Littérature -- Oman

A rural perspective on the Umm an-Nar and Wadi Suq periods from Burj Huraiz (northern Oman) - Olijdam, Eric; Düring, Bleda; Vreeze, Michel de; Litsenburg, Zoe van (Proceedings of the Seminar for Arabian Studies, 2025)
Despite substantial research on the Umm an-Nar (c.2700–2000 BC) and Wadi Suq (c.2000–1600 BC), our understanding of rural settlements and their economies during these periods remains limited. Research on the Umm an-Nar period has focused mainly on large sites and monumental towers, and relatively few vernacular buildings have been excavated. Similarly, the few known Wadi Suq-period settlements have provided scant insights into their nature. The discovery of a series of rural settlements in the northern Bāṭinah, particularly the well-preserved vernacular buildings of the Umm an-Nar and Wadi Suq periods at Burj Huraiz in the 2018 season of the Wadi al Jizzi Archaeological Project (WAJAP) survey and subsequent excavations in 2023–2024, have resulted in new and intriguing data. The main results from these excavations are presented here and contextualized, thereby enhancing our understanding of rural settlements in the Umm an-Nar and Wadi Suq periods.
Keywords: Archéologie -- Oman

The production of Bahlā Ware in the context of late Islamic Oman - Živković, Jelena; Lopez, Jose Carvajal; Döpper, Stephanie; Biezeveld, Irini (Proceedings of the Seminar for Arabian Studies, 2025)
Among glazed Arabian Gulf wares, Bahlā Ware stands out as one of the most documented objects of consumption at sites in Oman, the UAE, Qatar, and Bahrain from the sixteenth to the early twentieth century. Previous scientific studies of Bahlā Ware from UAE and Qatar formed the basis for understanding its production technology and provenance, as well as the unique composition of its lead-barium glaze. This paper presents the new results of petrographic and chemical analyses of thirty-two Bahlā samples from Oman, contributing to a better understanding of the compositional variability of ceramics, the provenance of raw materials, and techniques used for the application of lead-barium glazes. The compositional match between samples of Bahlā Ware from Oman, the UAE, and Qatar reveals the exploitation of the same geological source of raw materials over several centuries. Previous research has associated this source with the ophiolitic geological formation in Oman. The results of chemical analysis of glazes confirmed that the Omani samples were also coated with a lead-barium glaze of the same type as reported for UAE and Qatar.
Keywords: Archéologie -- Oman; Céramique -- Oman

تقييم مدى استدامة الإستراتيجية الوطنية لحماية وتثمين التراث العمراني الصحراوي دراسة حالة القطاع المحفوظ لسهل وادي ميزاب –ولاية غرداية - بركاني, فطيمة الزهراء (مجلة العمارة وبيئة الطفل, 2025)
Keywords: Monuments -- conservation -- Mzab

Khārijite Doctrines and the Formation of Early Islamic Thought in Western Sudan - Akrimah, Alansary (Science, Education and Innovations in the Context of Modern Problems, 2025)
The Great Berber Revolt (2nd century AH) marked the emergence of the first political entities adopting Khārijite doctrines. Its repercussions extended into Western Sudan, where Berber tribal confederations had already established firm foundations and absorbed Khārijite ideas, preceding the dominance of the Sunnī Mālikī school of law. The Mālikī tradition only gained prominence with the rise of the Almoravid Sanhaja state, which itself originated in this region historically referred to as Western Sudan.
Keywords: Ibadisme -- Soudan

الصشاع العبيذي الإباض ثورة مخلذ بن كيذاد انمىرجا - الزيدي, سامي جودة بعيد (المجلة الجزائرية للدراسات التاريخية والقانونية, 2025)
Keywords: Ibn Kaydad

احوال الموتى وأمور الآخرة ( الشفاعة، مرتكب الكبيرة، خلود المؤمن في الجنة، رؤية الله عز وجل) بين أهل السنة والإباضية دراسة سمعية وصفية مقارنة - امير, علي صديق امير عمر صديق (مجلة کلية الآداب جامعة أسوان, 2025)
يتناول البحث دراسة مقارنة بين أهل السنة والإباضية في أربع قضايا عقدية مرتبطة بأحوال الموتى وأمور الآخرة: الشفاعة، وحكم مرتكب الكبيرة، وخلود المؤمن في الجنة، ورؤية الله تعالى. يقرر أهل السنة إثبات الشفاعة للعصاة من أهل التوحيد بشروطها، وعدم تكفير مرتكب الكبيرة إذا لم يستحلها، وأنه قد يُعذَّب ثم يُخرج من النار برحمة الله وشفاعة الشافعين، ويؤمنون بخلود المؤمنين في الجنة وبإمكان رؤية الله تعالى في الآخرة بلا إحاطة ولا تكييف. في المقابل، يقصر الإباضية الشفاعة على المتقين، ويعدّون مرتكب الكبيرة كافرًا مخلدًا في النار إن مات غير تائب، ويتفقون مع أهل السنة على خلود المؤمنين في الجنة، لكنهم ينفون رؤية الله مطلقًا. يعود الخلاف إلى اختلاف مناهج التلقي وفهم النصوص، إذ يميل أهل السنة إلى الإثبات بلا تعطيل، بينما يعتمد الإباضية على التأويل تنزيهًا لله بزعمهم. أوصى البحث بضرورة تعزيز الحوار العلمي بين المذاهب، ودراسة الخلافات العقدية دراسة تأصيلية، وتحقيق كتب الفرق برؤية موضوعية، وفهم الخلفيات التاريخية للخلاف، وتشجيع المبادرات الأكاديمية لتقريب وجهات النظر.
Keywords: Foi -- thèmes et motifs

الخوارج والإباضية (الاتفاق والاختلاف) دراسة في النشأة والمنهج - امير, علي صديق امير عمر صديق (مجلة کلية الآداب, 2025)
تناول هذا البحث دراسة مقارنة بين الخوارج والإباضية من حيث النشأة، والعقيدة، والمنهج السياسي، مبرزًا أوجه الاتفاق والاختلاف بينهما. نشأ الخوارج في القرن الأول الهجري إثر الخلاف السياسي بعد معركة صفين، وتميزوا بالتشدد، وتكفير مرتكب الكبيرة، ورفض التحكيم، وكثرة الصدام المسلح مع السلطة. أما الإباضية، المنسوبة لعبد الله بن إباض، فقد انبثقت عن الخوارج الأوائل لكنها تبنت نهجًا أكثر اعتدالًا، متأثرة بجابر بن زيد، ورفضت الغلو والعنف إلا دفاعًا عن النفس. عقائديًا، يتفق الطرفان في تقديم القرآن كمرجعية عليا، ورفض الوراثة في الحكم، ومشروعية مقاومة الظلم، لكن الخوارج يكفرون مرتكب الكبيرة، بينما الإباضية يصفونه بكفر النعمة دون إخراجه من الإسلام. كما يرفض الإباضية رؤية الله في الآخرة والشفاعة للعصاة غير التائبين، ويتبنون موقف “المنزلة بين المنزلتين”. سياسيًا، مارس الخوارج الثورة المسلحة، بينما فضل الإباضية الإصلاح السلمي وإقامة إمامات قائمة على الشورى. فقهيًا، لم يترك الخوارج تراثًا منهجيًا مستمرًا، في حين أسس الإباضية مدرسة فقهية متينة. خلص البحث إلى أن الإباضية رغم الجذور المشتركة مع الخوارج، تميزت بمنهج معتدل، وتركزت توصياته على ضرورة إعادة قراءة التاريخ بإنصاف، والتمييز بينهما في الدراسات المعاصرة، والاستفادة من التجربة الإباضية في التعايش المذهبي والسياسي.

موقف سلطنة عمان من الجهود البريطانية لتحريم تجارة الرقيق في زنجبار 1822-1914 - جياد, حسين فالح (اكليل للدراسات الانسانية, 2025)
شهدت المرحلة التاريخية 1822- 1914 التوصل الى مجموعة من الاتفاقيات الهامة لإلغاء ظاهرة الرق والإتجار بها في القارة الأفريقية وخاصة في جنوب شرق القارة المذكورة, وقد تركزت الجهود المبذولة لإلغاء الرق بشكل تام في زنجبار وعقدت أول معاهدة بين بريطانيا وسلطنة عمان في عام 1822, وقد سميت تلك المعاهدة بمعاهدة مورسبي نسبة الى العميد مورسبي الذي تولى المفاوضات مع السيد سعيد بن سلطان, وتم الإتفاق بين الجانبين على إلغاء تجارة الرقيق في الممتلكات التابعة للسيد سعيد في زنجبار ومناطق شرق القارة الأفريقية, وقد تلا معاهدة عام 1822 سلسلة من المعاهدات عام 1839 وعام 1845 والتي بموجبها تم التوصل الى إتفاق نهائي بين بريطانيا وسلطنة عمان حول إنهاء تجارة الرقيق وتحريم تلك التجارة نهائياً. وبعد وفاة السيد سعيد بن سلطان عام 1870 تولى الحكم في زنجبار السيد برغش بن سعيد آل بو سعيد, وقد واجهت الحكومة البريطانية صعوبة في إقناع الحاكم الجديد بإستمرار صلاحية المعاهدات المعقودة مع سلطنة عمان, إذ رفض السيد برغش بن سعيد جميع الجهود البريطانية الرامية الى ذلك,إلا أن إستمرار الضغط البريطاني وما تبعه من تهديد للسيد برغش بن سعيد أرغم الأخير على عقد معاهدة عام 1873 والتي نصت على منع تجارة الرقيق منعاً باتاً على طول الساحل الأفريقي ومعاقبة السفن التي تحمل الرقيق مع إغلاق الأسواق الخاصة بهذه التجارة وإستمرت الجهود الرامية لإلغاء تجارة الرقيق وفقاً لبنود هذه المعاهدة حتى عام 1914. يدرج البحث او المقال كاملا هنا دون الاشارة مرة اخرى الى ما ذكر اعلاه
Keywords: Kharijisme

أثر الهنود في زنجبار في القرن التاسع عشر - حسين, ماجد مزهر (الملوية للدراسات الآثارية والتاريخية, 2025)
Keywords: Relations -- Oman -- Arabie Saoudite

أثر الخوارج في الفكر الإسلامي المعاصر - احمد, أسعد محمود محمد طاهر (مجلة كلية العلوم الاسلامية, 2025)
يهدف البحث إلى إبراز مدى تأثر الخوارج في الفكر الاسلامي، وبيان الأمثلة والشواهد الدالة على وجود التأثر والمشابهة بينهم تحذيراً للمسلمين من مسالكهم، فضلاً عن أهمية البحث في الكشف عما تحتويه بعض كتب المتأخرين…
Keywords: Kharijisme

أثر الأحداث السياسية خلال القرن الأول الهجري في تكوين فرقة الخوارج (الجذور والمعتقد) - الموسوي, حسن حمادي سعدون; حسيني, سيد محمد; نوري, علي آقا (مجلة الكلية الاسلامية الجامعة, 2025)
الملخص:- ان ظهور الخوارج في القرن الاول بسبب فكرهم العقائدي الذي شكل لاحقاً حزباً سياسياً اختلف مع الفرق الاخرى في مبدأ اختيار الخليفة أو من يتولى قيادة الدولة الإسلامية وكان ذلك الامر اساسياً في نشأة…
Keywords: Kharijisme

إثر العامل الجغرافي في حرب النهروان مع الخوارج - حمود, علياء حسين علي; وناس, زمان عبيد (مجلة الباحث, 2025)
ان لكل حركة سواء أكانت ذات طابع انساني معاشي أم عسكري محكومة بآثار عوامل الطبيعة ، والاهم من ذلك العوامل الارضية ، ونقصد بها تضاريس الارض ، اضف الى ذلك المناخ ، ومن جراء ذلك تعرضنا في بحثنا هذا للعوامل…
Keywords: Kharijisme

اثر الخوارج في بيئة المشرق الاسلامي في الحقبة (205- 290هـ) الجانب العسكري والاداري انموذجاً - عبد, عثمان مشعان (مجلة مداد الاداب, 2025)
دراسة البحث الموسوم* أثر الخوارج في بيئة المشرق في الحقبة(٢٠٥-٢٩٠) الجانب العسكري والاداري أنموذجا. يسلط الضوء على التركيبة السكانية للمشرق ذات القوميات المتنوعة وبيان اثر الخوارج في التأثير على فكر وعقائد…
Keywords: Kharijisme

الحياة الفكرية في الدولة البوسعيدية في عمان (1744 -1847م) الشيخ جاعد بن خميس الخروصي – (أنموذجاً) - الكاسبي, يوسف; العذوبية, بهية بنت سعيد (مجلة مركز بابل للدراسات الانسانية, 2025)

التنافس والصراع في مدينة عبري العُمانية بين الإمامة والسلطنة (1913- 1954م) - الشعيلي, محمد بن حمد (مجلة مركز بابل للدراسات الانسانية, 2025)
Keywords: Vie politique -- Oman -- 1913-1932; Vie politique -- Oman -- 1932-1970

موقف سليمان الباروني من الدولة العثمانية من فترة حكم عبد الحميد الثاني إلى سقوط الخلافة - مشيخي, هادية صالح (مجلة مركز بابل للدراسات الانسانية, 2025)
يسعى هذا البحث إلى إبراز ملامح الفكر السياسي الإباضي وتبيّن خصائصه من خلال شخصية سياسية إباضية (سليمان الباروني (1873-1940)، تنتمي إلى بلاد المغرب (ليبيا)، عاشت في الفترة الحديثة والمعاصرة باعتبارها وجها من أوجه التعدّد السياسي لها رؤية مختلفة للسلطة والحكم والدولة، ومارست السياسة وتقلدت مناصب سياسية في الدولة العثمانية، فقد كان الباروني واليا وكومندانا على طرابلس الغرب (ليبيا اليوم) التي كانت إيالة عثمانية، وقاد الحرب الطرابلسية ضد إيطاليا التي اندلعت سنة 1911. وكان له موقف من الدولة العثمانية زمن حكم عبد الحميد الثاني الذي اتخذ من الجامعة الإسلامية شعارا للدولته، وقد اشترك الباروني معه في القول بالجامعة الإسلامية باعتبارها تدعو إلى وحدة المسلمين بغض النظرعن عرقهم ومذهبهم وانتماءهم الجغرافي، وتنأى بهم عن التقاتل المذهبي وتدعوهم إلى الوحدة لصد الهجمة الحضارية الغربية، وقد كان الباروني يروّج لهذا التوجه في المنتديات والمجالس التي يحضرها. كما تناولنا موقفه من العثمانيين الأحرار المنتمين لجمعية "الاتحاد والترقي" الذين حدّدوا صلاحيات الخليفة العثماني من خلال المشروطية (الدستور) التي أصدروها سنة 1908، وقد رحّب الباروني بالدستور الذي يساوي بين جميع العرقيات والأقليات والمذاهب في السلطنة العثمانية ويمكّنه من العودة إلى وطنه. ثم درسنا موقفه من حكم مصطفى كمال أتاتورك، وقد كان الباروني من المعارضين لسياسة التتريك التي انتهجها مؤسس الدولة القومية التركية، والمنددين بها في الجرائد العربية باعتبارها سياسة علمانية فصلت الدين عن نظام الحكم من خلال إلغاء الخلافة. ارتبط اختيارنا لهذه الشخصية بقضية أخلاقية سياسية، وهي ضرورة أن يتحقّق عند المفكّر السياسي شرطيْ التفكير والممارسة. وقد كان الباروني مثالا صافيا للمثقف الملتزم. البحث
Keywords: Bārūnī, Sulaymān al- (1870-1940)

سياسة الولايات المتحدة الأمريكية تجاه الصراع بين الإمامة والسلطنة في عمان ١٩٥٤ - ١٩٥٩ - علاوي, علي عادل (مجلة مركز بابل للدراسات الانسانية, 2025)
يُعد الصراع بين الإمامة والسلطنة في عُمان 1954-1959 أحد أبرز الصراعات التي شهدتها منطقة الخليج العربي والشرق الأوسط خلال النصف الثاني من القرن العشرين ، إذ تزامن نشوبه مع متغيرات إقليمية ودولية ارتبطت بتصاعد حدة الحرب الباردة التي شهدها العالم بعد نهاية الحرب العالمية الثانية بين المعسكرين الغربي بقيادة الولايات المتحدة الأمريكية والشرقي بقيادة الاتحاد السوفيتي ، وقد كان لتلك المتغيرات أثر واضح في رسم سياسة الولايات المتحدة تجاه الصراع الذي شهده عُمان بين الإمامة والسلطنة ، على الرغم من بروز المصالح النفطية والاقتصادية والمنافسة الشديدة بين شركات النفط البريطانية والأمريكية على امتيازات التنقيب في عُمان وإمارات الخليج الأخرى ، ودورها الكبير في تحديد الموقف الأمريكي بما يتماشى مع تلك المصالح ، إلا أن الولايات المتحدة الأمريكية أعطت الأولوية للمصالح الاستراتيجية بعيدة المدى في كيفية التعامل مع طرفي الصراع في عُمان والجهات الفاعلة فيه ، مع إيجاد توازن في سياستها تجاه حلفائها على الساحتين الإقليمية والدولية ، والأخذ بنظر الاعتبار ضرورة إغلاق أية ثغرة إمام توغل الشيوعية إلى تلك المنطقة الحيوية بالنسبة للمصالح الأمريكية ، وقطع الطريق على الاتحاد السوفيتي الذي كان يطمح في مد نفوذه إلى تلك المنطقة الغنية بالنفط ، وبالتالي إيجاد موطئ قدم له فيها مستغلًا مثل تلك الصراعات ، الأمر الذي يحقق له نصرًا استراتيجيًا في صراعه مع المعسكر الغربي . وعلى هذا الأساس تعاملت الولايات المتحدة الأمريكية مع ذلك الصراع الذي شهدته عُمان خلال تلك المدة التي كانت تعج بالمتغيرات السياسية والعسكرية والتحالفات الإقليمية والدولية في خضم الحرب الباردة ، ونجحت في الحفاظ على مصالحها في المنطقة مع دعم وجود حلفائها وإبقاء الخطر السوفيتي بعيدًا عنها.
Keywords: Relations -- Oman -- Etats-Unis

مدينة نفوسة في بلاد المغرب الاسلامي دراسة في احوالها العامة حتى عام ٣١١هـ - الاسدي, عقيل محمد صالح (مجلة مركز بابل للدراسات الانسانية, 2025)
يعتبر تاريخ قبيلة نفوسة تاريخ قديم قدم الحضارات الفينيقية والرومانية ولعبت نفوسة دوراً مهماً خلال حكم هذه الحضارات لبلاد المغرب عموماً، كما اعتنقت ديانات هذه الحضارات وتكلمت لغاتها وتفاعلت معها، لكنها وجدت في الإسلام المنقذ لها من عبودية وغطرسة هذه الحضارات لاسيما ما وجدوه من مبادئ إسلامية تحث على العدالة والمساواة فاعتنقوا الدين الإسلامي افواجاً . كما كان لمدينة نفوسة دوراً كبيراً ومهماً في التاريخ الإسلامي عامة وتاريخ بلاد المغرب خاصة، وذلك نظراً لما تمتاز به مدينة نفوسة من موقعٍ حساس ربط بين مشرق العالم الإسلامي ومغربهِ، فشكلت مدينة نفوسة نقطة عبور بين مختلف مدن العالم الإسلامي، إضافة الى جغرافيتها وموقعها وما تمتعت بهِ من تضاريس جبلية وعرة جعلتها مدينة محصنة وقوية، كما وفرت هذه التضاريس أسباب الازدهار الاقتصادي من وديان صالحة للرعي وامطار وتربة صالحة للزراعة مما جعلها تتمتع بحياة اقتصادية مزدهرة، إضافة الى الدور الذي لعبته نفوسة على الصعيد السياسي والاقتصادي والاجتماعي بحكم هذا الموقع. ولقوة ومكانة قبيلة نفوسة ونفوذها في المنطقة فقد غلب اسمها على المنطقة التي استوطنتها وهي منطقة الجبل والتي أصبحت تعرف باسمها بالرغم من سكن الكثير من القبائل هذه المنطقة الا ان قوة قبيلة نفوسة ونفوذها جعل جميع هذا القبائل تتحالف معها او تدين بالطاعة لها، وبحكم موقعها الجغرافي وتحصيناتها الطبيعية وقوة رجالها كان للمدينة دوراً سياسياً كبيراً، إذ شاركت المدينة في جميع الاحداث السياسية والعسكرية في بلاد المغرب، فكان لها موقف حازم تجاه تعنت الولاة الامويين والعباسيين والقيام بالثورات ضدهم وخلعهم وقتلهم احياناً، كما شاركت في العديد من الصراعات السياسية الدولية التي كانت تهدد وجودها ونفوذها فكان لها دوراً كبيراً في رسم الخارطة السياسية للمنطقة، وحسم النزاعات لصالح طرف على حساب طرف آخر.
Keywords: Djebel Nefousa -- Histoire

أثر الاسرة البوسعدية على الحياة الاجتماعية لدى شعب زنجبار في تنزانيا: دراسة ميدانية في الانثروبولوجيا الاجتماعية - البوسعيدي, زيانة بنت هلال بن زاهر (مجلة كلية الآداب, 2025)

المرأة والثروة في المجتمع العماني: قراءة في وثائق الإرث والصداق 1208هـ\1794 – 1391هـ\1971 - السعدي, ناصر بن سيف; العبرية, زهرة بنت سيف (مجلة دراسات الخليج والجزيرة العربية, 2025)
الأهداف: سعت الدراسة إلى إبراز دور الموارد الطبيعية في الاقتصاد التقليدي باعتبارها رمزاً للثروة والرخاء، إضافةً إلى الكشف عن تأثير الإرث والصداق في تعزيز المكانة الاقتصادية للمرأة وتحسين وضعها المالي. كما حاولت رصد التحولات التي طرأت على وثائق الصداق والإرث، إلى جانب التغيرات الاقتصادية والاجتماعية وتطور العملات. وسلطت الضوء على كيفية إدارة النساء لثرواتهن على الرغم من القيود الاجتماعية، ودور العادات في توجيه الملكية، مع إبراز القيم الثقافية والاجتماعية المرتبطة بالصداق والميراث. المنهج: اعتمدت الدراسة على المنهج الإحصائي والتحليل التاريخي من خلال تحليل وثائق تاريخية متنوعة تشمل صكوك البيع والشراء والديون ووثائق الزواج والصداق؛ بهدف الكشف عن مصادر أموال النساء واستخداماتها، ودراسة طبيعة ممتلكاتهن وثرواتهن. واستعين بمصادر ثانوية؛ مثل المصادر الفقهية والتاريخية؛ لتعزيز دقة التحليل. النتائج: توصلت الدراسة إلى أهمية الموارد الطبيعية؛ مثل الأراضي الزراعية والنخيل، كرموز للثروة والمكانة الاجتماعية، ودور الإرث والصداق في تعزيز مكانة المرأة الاقتصادية من خلال أصول متنوعة؛ كالزراعة والمساكن والخدم. كما بينت تطور وثائق الصداق والإرث، واستخدام عملات متنوعة، تعكس التحولات الاقتصادية. وعلى الرغم من القيود الاجتماعية، أظهرت الدراسة قدرة النساء على إدارة مواردهن بمرونة، مع الحفاظ على الملكية داخل العائلة؛ مما يعكس تأثير العادات والقيم الثقافية المرتبطة بالإرث والصداق. الخاتمة: تكمن أهمية وثائق الزواج والصداق في تقديم رؤية شاملة لتاريخ المرأة، ليس من الناحية الاقتصادية فقط، بل امتدت لتشمل الأبعاد الاجتماعية والثقافية والقانونية. وعلى الرغم من تركيز الدراسة على تحليل ملكية ومصادر ثروة النساء، فإنها تفتح المجال لدراسات مستقبلية تتناول الجوانب الاجتماعية والثقافية لهذه الوثائق بمزيد من العمق والتفصيل.

الربيع بن حبيب الإباضي بين أهل السنة والإباضية جزء من رسالة: زوائد مسند الربيع بن حبيب الإباضي على كتب السنة - حسن, محمد عبد الحليم (مجلة کلية الآداب, 2025)
ملخص البحث:يهدف هذا البحث، المعنون "زوائد مسند الربيع بن حبيب الإباضي على كتب السنة: دراسة تحليلية"، إلى تقييم مسند الربيع بن حبيب من منظور أهل السنة والجماعة، مع التركيز على مكانته لدى الإباضية. يتناول البحث التعريف بالربيع بن حبيب ومسنده، مستعرضًا نشأته وشيوخه وتلاميذه ومكانته العلمية من وجهة نظر الإباضية، حيث يعتبرون المسند أصح كتاب بعد القرآن الكريم.إلا أن الدراسة تنتقل بعد ذلك إلى تحليل المسند بمنهج نقدي وفقًا لمعايير أهل السنة والجماعة. وتُبرز الإشكاليات الجوهرية التي تضعف من موثوقية المسند، مثل غياب توثيق الربيع بن حبيب وشيخه أبي عبيدة مسلم بن أبي كريمة في كتب رجال أهل السنة، وإشكالية الانقطاع في إسناد المسند الذي يعتمد على طريق واحد في أغلبه. كما تسلط الضوء على غياب المسند عن مدونات العلماء الأوائل من أهل السنة، واضطراب بعض مروياته ومخالفتها لما صح في كتب السنة المعتبرة، مثل حديث "إنما الأعمال بالنيات" و"اطلبوا العلم ولو في الصين"، وروايات تنفي الشفاعة لأهل الكبائر. ويختتم البحث برفض تبرير السرية التاريخية لغياب المسند، مؤكدًا أن هذه الإشكاليات تجعل المسند غير قابل للاعتماد عليه في إثبات السنة أو العقيدة عند أهل السنة، إلا ما وافق الثابت منها.
Keywords: Hadith -- recueils

Defining the Intangible: Negotiating Intangible Cultural Heritage in Modern Oman - Matani, Ayat al- (Journal of the American Institute for Conservation, 2025)
Intangible Cultural Heritage (ICH), particularly traditional music, is vital yet vulnerable. Traditional music intertwines with cultural rituals, embodying spirituality and diverse human experiences. However, how cultural heritage is negotiated and preserved in modern Oman remains underexplored. This study utilizes ethnographic interviews with government officials, institutional archivists, grassroots archivists, and musicians to reveal perspectives on preserving Omani musical heritage. Findings indicate that governmental institutions regard ICH as pivotal for national identity, tourism, unification, and economic growth, prioritizing structured archiving and formal presentation. Institutional archives thus provide extensive yet static collections of musical recordings and visual media, emphasizing curated representations over dynamic authenticity. Conversely, grassroots archivists favor participatory, flexible preservation methods driven by personal commitment and cultural concerns. They document live, spontaneous musical events, leveraging social media to promote community engagement and cultural continuity. Grassroots efforts effectively capture the evolving, lived experience of musical traditions, complementing institutional strategies. The coexistence of institutional and grassroots archival practices creates a balanced preservation framework, combining structured protection with community-driven authenticity. This dual approach provides a holistic model for sustaining Omani musical heritage as both a national asset and a living tradition.
Keywords: Musique -- Oman

Britain and the Dhofar War in Oman, 1963–76: A covert war in Arabia: by Geraint Hughes, Basingstoke, Palgrave Macmillan, 2024, 325 pp, £119.99, ISBN 978-3-031-49498-7; The Dhofar War: British Covert campaigning in Arabia, 1965–75, by Stephen Quick, Exeter, University of Exeter Press, 2024, 235 pp, £95.00, ISBN 9781804130988. - Beckett, Ian F W (Small Wars & Insurgencies, 2025)
Keywords: Dhofar; Recension

The first collective Neolithic megalithic tomb in Oman - Danielisová, Alžběta; Maiorano, Maria Pia; Šneberger, Jiří; Ackerman, Lukáš; Daněček, David; Garba, Roman; Martinez-Garcia, Alfredo; Lüdecke, Tina (Antiquity, 2025)
, A newly discovered grave in Wadi Nafūn, Oman, features a unique burial structure, combining monumental architecture and the collective deposition of human remains from multiple Neolithic groups. Detailed analysis of the burial community reveals new insights into Neolithic rituals and subsistence strategies during the Holocene Humid Period in southern Arabia.
Keywords: Archéologie -- Oman

Zanzibar Was a Country: Exile and Citizenship between East Africa and the Gulf By Nathaniel Mathews - Wint-Frederick, Hollian (Journal of Social History, 2025)
Tracing the lives, experiences, and ideas of Zanzibari Arabs through rich oral and written archives, Zanzibar Was a Country demonstrates the significance of “experiences in diaspora” to Indian Ocean postcolonial national belonging (2). Belonging, in Mathews’ rendering, refers to both “sentiment” —the idea of Zanzibar as a sovereign state and collective attachment to it—and citizenship—recognized political status and the infrastructures that produce it. The book makes two key intersecting interventions: first, by examining the political economy of citizenship from the era of developmental colonialism to the hydrocarbon-fueled developmentalism of the Arabian Gulf, Mathews presents an important analysis of decolonization as an economic process in which the tensions of the late colonial era continued. Second, he explores the complex and diverse articulations of Zanzibari-Omani belonging that emerged among diasporic Zanzibaris in this context, both in individual memory and through a vibrant vernacular historiography. This is a book that takes seriously not just the memories of its interlocutors, but their scholarship; their own endeavors in writing their history.
Keywords: Recension

أصهل التفديخ عنج الذيخ أطفيش من خلال تفديخه تيديخ التفديخ - الرواحي, بدر بن خليفة بن سعيد (مجلة كلية التربية, 2025)
Keywords: Coran -- Commentaires -- 19e siècle

Sovereigns of the Sea: Omani Ambition in the Age of Empire: by Seema Alavi - Chowdhary, Mir Kamruzzaman (Journal of the Indian Ocean Region, 2025)
Keywords: Recension

أنشطة الإرسالية العربية في مسقط خلال فترة السلطان فيصل بن تركي: 1892-1913 - الباطني, خالد بن عبد الله (حوليات آداب عين شمس, 2025)
تسعى هذه الدراسة الى دراسة نشاط الإرسالية العربية المسيحية الأمريكية في مسقط أثناء حكم السلطان فيصل لعمان. تبين هذه الدراسة ان نشاط الإرسالية في مسقط شكل تحديا دينيا و سياسيا و اجتماعيا و دبلوماسيا للسلطان فيصل و للأهلي في عمان و خلق ردات فعل نجم عنها تطورا على المستوى التعليمي و الطبي في مسقط. tفي عام 1893 تمكنت الإرسالية العربية من إنشاء مقر لها في مسقط حيث كان هدفها التوسع في أرجاء عمان و الوصول إلى أكبر مساحة ممكنة من الجزيرة العربية. أما هدفها الأساسي فكان تنصير سكان المنطقة. قام نشاط الإرسالية على توزيع الأناجيل والكتب الدينية وإجراء النقاشات مع الأهالي. لكن شاءت الظروف آنذاك أن توكل القنصلية البريطانية مجموعة من العبيد المحررين إلى الإرسالية لتهتم بهم، فأصبحوا نواة العمل التبشيري في مسقط. طورت الإرسالية أساليب عملها فبدأت تقدم خدمات طبية وتعليمية إلى مجتمع كان يفتقر إلى مثل هذا الخدمات وفي أمس الحاجة إليها. وهكذا أنشأت مدرسة للبنين وأخرى للبنات وأحضرت أطباء للعمل في مسقط ومطرح. ولكنها واجهت بعض الصعوبات، ولا سيما قلة المنتسبين إلى مدارسها وبروز مشروع بسيط حاول أن ينافس مشروعها التعليمي: بالتزامن مع نشاطها بدأ السلطان فيصل بمحاولة تحسين الخدمات الطبية في مسقط وتبرع بإنشاء مستشفى فيها. ولكن الإرسالية حاولت منافسة هذا المشروع من خلال إنشاء مستشفى في مطرح، ما أدى إلى خلاف كبير بين السلطان من جهة والإرسالية والقنصلية الأمريكية من. استغل الثوار، وبالأخص أنصار الإمامة، نشاط الإرسالية التبشيري وقاموا بمهاجمتها هي والسلطان. لم يقف المجتمع العماني مكتوف اليدين إزاء نشاط الإرسالية خلال فترة حكم السلطان فيصل، فقد تشكلت مبادرات محلية من الأهالي لمواجهتها بالإمكانيات المتاحة.
Keywords: Missionnaires -- Oman; Vie politique -- Oman -- 1888–1913

M’addib s and Migrant Laborers: Migration from Ottoman Trablus al-Gharb to Djerba, Tunisia in the Early 20th Century - Love Jr, Paul M. (International Journal of Middle East Studies, 2025)
This article follows the history of migration from the mountain villages of the Jebel Nafusa in Ottoman Trablus al-Gharb (in today’s northwestern Libya) to the southern Tunisian island of Djerba in the early 20th century. It situates this local history of migration within the broader framework of Maghribi migration both before and during the colonial era in Libya (1911–43), while tracing the histories of two categories of migrants, in particular, manual laborers and Qur’an teachers (m’addib-s). The article makes three claims: (1) Nafusi migration was as much the result of local historical circumstances as it was a response to colonialism; (2) the historical experience of migration of Nafusis differed according to social class; and (3) local circumstances shaped the dynamics of migrant integration in the Maghrib. In doing so, I demonstrate how Nafusi migration to Djerba both conforms to and diverges from the larger history of late Ottoman and colonial-era migration in Tunisia. By shifting the focus away from the colonial moment, I make the case for foregrounding longer-term regional connections and migrations that linked different spaces across the Maghrib and also attend to local histories and what they offer in the way of caveats and exceptions.
Keywords: Bumas'ud, mosquée (Ajim, Djerba); Emigration -- Djebel Nefousa -- Djerba; Enseignement -- Djerba -- 1881-1956; Malāq, mosquée (Oualegh, Djerba); Tâjdît, Mosquée (Fâtû, Djerba)

الشيخ ابن جعفر "ق. 3 هـ." ومنهجه الفقهي في كتاب الجامع: أبواب العبادات أنموذجاً - القنوبية, عائشة بنت مبروك (مجلة الاجتهاد للدراسات القانونية والاقتصادية, 2025)
تهدف الدراسة إلى إبراز علم من أعلام الإباضية المشارقة ومنهجه في كتابه الجامع وأثره على الفقه الإباضي، وهو الشيخ أبو جابر محمد بن جعفر الدرمكي الأزكوي (حي: 280هـ)، فجاءت الدراسة للكشف عن مكانة الشيخ ودوره في الفقه الإباضي خصوصا والفقه الإسلامي عموما، فجاءت الدراسة في أربعة مباحث تناولت التعريف بالشيخ وكتابه ومنهجه في التأليف والاستدلال، واعتمدت هذه الدراسة على المنهج الوصفي، والمنهج الاستقرائي، وخلصت الدراسة إلى أن الشيخ ابن جعفر يعد من كبار علماء الإباضية في المشرق في القرن الثالث الهجري، وكتابه الجامع (9 أجزاء) من بواكير العمل الموسوعي الفقهي، حيث شهدت هذه المرحلة بدايات الكتابة في الدراسات الفقهية المقارنة، فكان ابن جعفر ينقل في كتابه أقوال أشياخه وشيوخهم وغيرهم من أمثال الإمام جابر بن زيد وأبي عبيدة ووائل وأبي صفرة ومحمد بن محبوب، ويختار ما يراه صوابا مستعملا جملة من العبارات والصيغ في ذلك كما ينقل ما ذكر عن الصحابة والتابعين، وقد يعرض المسألة مجردة عن الأدلة، وقد يدعمها بالدليل من القرآن أو السنة، كما نجده كثيرا ما يورد محاوراته ومراسلاته مع شيخه أبي عبد الله محمد بن محبوب التي يتبنى الكثير منها ويحتج بها، وقد يخالفه الرأي، كما نجده يذكر آراء معاصريه كأبي المؤثر وأبي الحواري، ومن منهجه أنه يبدأ الفصل عادة بآية أو حديث فيعلق على النص ويفرع عليه موردا أقوال العلماء في ذلك، ويكتفي أحيانا بإيراد المسألة بصيغة تقريرية ثم يبحث لها عن مختلف الصور المحتملة فيذكر حكمها أو ينقل أقوال بعض العلماء. كما يذكر في بعض المسائل الحكم الشرعي معضدا قوله بالدليل من كتاب الله أو سنة نبيه أو رأي العلماء.

سلطنة عمان: أهمية موقعها الجيواستراتيجي ومراحل تطور نظامها السياسي - حبيب, حسين علي; دخيل, محمد حسن (آداب الكوفة, 2025)
Keywords: Géographie -- Oman

الاستدلال بالقياس عند الإباضية في القرن الثاني الهجري - الهادي, سيف بن سالم (المجلة العالمية للدراسات الفقهية والأصولية, 2025)

Cezayir’in Mizâb Bölgesine Seyahat ve Cezayir İbâzîleri Üzerine Notlar - İğdi, Ahmet (e-Makalat Mezhep Araştırmaları Dergisi, 2025)
19-28 Ocak 2025 tarihleri arasında Cezayir’in Mizâb diye anılan bölgesine bir seyahat gerçekleştirdim. Bu seyahata çıkma sebebim, daha önce uzun yıllar çalıştığım İbâzî topluluklarını kendi kültür çevrelerinde görmekti. Bu ziyareti hem İbâzî mezhebinden olan hem de Gardâye Üniversitesi’nde öğretim üyesi olan arkadaşım Prof. Dr. Bekîr Bûarva’nın bağlantıları sayesinde gerçekleştirdim. Ayrıca aynı üniversiteden ve Azzâbe heyeti üyesi de olan Prof Dr. Yahya Hâc Buhûn da özellikle başkent Cezayir’deki İbâzî kurumlarını gezmemde mihmandarlık etti. Gezi boyunca İbâzî mezhebinin gelenek olarak canlı yaşandığı ve tarihsel dokusunu da koruyan şehirlerini, camilerini ve mezarlıklarını gezdiğimiz gibi İbâzî eğitim ve araştırma kurumlarını da ziyaret ettim. Gezi bana kitaplarda anlatılan İbâzî gelenek ve inanışlarının canlı olarak yaşandığı bir kenti görme olanağı verdi.
Keywords: Récits de voyage -- Mzab

المراسلات السياسية بين الدولتين العمانية والعثمانية من خلال كشف النقاب عن رسالة الإمام أحمد بن سعيد حاكم عمان إلى السلطان عبد الحميد الأول من آل عثمان (1134 ه/ 1020 م) دراسة وتحقيق - خيراني, صلاح; الطراونة, محمد سالم (المجلة الجزائرية للدراسات الإنسانية, 2025)
Keywords: Relations -- Oman -- Empire ottoman

‘Comme à Tunis’: Roundtable with Rafram Chaddad - Jonathan, Victoria (Francosphères, 2025)
‘Comme à Tunis’ was an evening curated by Victoria Jonathan around the work of Tunisian artist Rafram Chaddad, on 14 October 2024 at the Book Bar (Hôtel Grand Amour), in conjunction with Paris Art Week. Drawing on everyday life and investing public spaces, Rafram’s work evokes exile, migration, the fragility of borders, and the mutability of identities. This roundtable, co-chaired with Joseph Hirsch (mahJ), focuses on Rafram Chaddad’s book The Good Seven Years, a deeply original artistic work on the traces of Tunisia’s Jewish minority that almost disappeared in the twentieth century.
Keywords: Judaïsme -- Djerba

Preserving Omani Intangible Heritage: A Study of Folktale Authenticity and Classification - Akkawi, Aya Walid Fayyad; Rubai'ey, Fatema; Dineen, Gerard (المجلة العلمية لکلية الآداب جامعة أسيوط, 2025)
To prevent Omani folktale heritage from being lost or distorted, especially in the era of globalization and digitization, and since there is no oral documentation of Omani folktales, there is a need to investigate the authenticity of documented Omani folktales published in print and to classify them based on tale-type. This study attempts to document a comprehensive collection of Omani folktales from existing materials published in or translated into English by developing a classification system based on Hasan El-Shamy‘s established tale-type index. Further, the study aims to assess the authenticity of these folktales by investigating Omani cultural markers found in them and identifying potential distortions or adaptations.
Keywords: Littérature -- Oman

التعليل الفقهي بقاعدة "الأمور بمقاصدها" وما تفرع عنها، وتطبيقاتها الفقهية في باب المعاملات من كتاب "شرح النيل" للشيخ أطفيش(1332هـ) - الحبسي, أحمد بن ناصر بن محمد; الحبسي, سلطان بن منصور (مجلة الشهاب, 2025)
يهدف هذا البحث إلى إبراز مسلك التعليل الفقهي بإحدى القواعد الفقهية الكبرى وهي قاعدة "الأمور بمقاصدها" في باب المعاملات عند الشيخ أطفيش (1332ه)، وجاء للإجابة على الإشكالية المتمثلة في الأسئلة التالية: ما مفهوم التعليل الفقهي؟ وما المقصود بقاعدة الأمور بمقاصدها، والقواعد المتفرعة عنها؟ وهل أخذ المؤلف بالتعليل الفقهي بهذه القاعدة؟ وما التطبيقات الفقهية التي أدرجها تحت التعليل بهذه القاعدة؟ واعتمد البحث على المنهجين الاستقرائي والتحليلي، وخلص إلى عدة نتائج من أهمها أن المؤلف أخذ بالتعليل الفقهي بالقواعد الفقهية للأحكام التي ذكرها في كتابه، ومنها التعليل بقاعدة "الأمور بمقاصدها"، وعلَّل بعض الفروع الفقهية بهذه القاعدة والقواعد المتفرعة عنها. This research aims to highlight the path of jurisprudential reasoning based on one of the major jurisprudential rules, which is the rule of “matters with their purposes” in the chapter on transactions according to Sheikh Tfayesh (1332 AH), and came to answer the problem represented in the following questions: What is the concept of jurisprudential reasoning? What is meant by the rule of matters with their objectives, and the rules deriving from it? Did the author follow the jurisprudential explanation for this rule? What jurisprudential applications did he include under the justification for this rule? Keywords: reasoning, jurisprudence, matters with their purposes, Tfayesh, explanation of the Nile.
Keywords: Fiqh -- Commentaires -- 19e siècle

Hafed Abdouli, Min Trībūlīṭāniya ilā Aṭrābuls: al-mašhad al-ta‘mīrī ḫilāl al-‘aṣr al-wasīṭ al-mutaqaddam bayna al-tawāṣul wal-taḥawwulāt, [De la Tripolitaine à Tripoli : le paysage urbain au début du Moyen Âge entre continuité et changement]: Leyde, Brill, 2023 - Amara, Allaoua (Revue des mondes musulmans et de la Méditerranée, 2025)
Keywords: Recension

Eksistensi Kitab Musnad Rabi’ Bin Habib Sebagai Kitab Hadis Shahih Khawarij Alibadiyah - Nurizzati Arifah, Afro’ Anzali; Muhid; Atim Muthoharoh, Isnaini Lu’lu’; Khaira, Zsazsa Tuhfa (Journal of Hadith Studies, 2025)
Discover this 2025 paper in Journal of Hadith Studies (25501448) by Nurizzati Arifah, Afro’ Anzali; Muhid; Atim Muthoharoh, Isnaini Lu’lu’; et. al. focusing on: HADITH; LIBRARY research; SECTS; QUALITATIVE research; RESEARCH methodology
Keywords: Hadith -- Ibadisme

وقف النخيل في عمان: دراسة فقهية في الاهتمام والأغراض والتحديات والحلول من خلال الاستفتاءات والوصايا في كتب الفقه والفتوى (القرن ١٢ه-١٥ه/ ١٨م-٢١م) - البطاشي, هلال بن خلفان (مجلة كلية الدراسات الإسلامية والعربية للبنات بالزقازيق, 2025)
Keywords: Agriculture -- Oman; Waqf (fondations) -- Oman

Language Borrowing in Oman: Evidence of Balushi Influence in Spoken Omani Dialect - Dhahab, Maryam Nawaf al- (Sultan Qaboos University, 2025)
This study explores the borrowing of Balushi words into the Omani dialect, focusing on three commonly used terms: /sˤar.da/ (severe cold), /ˈpæn.ke/ (fan or propeller) and /ˈkun.bil/ (thick blanket). Through a survey of 50 participants from eight Omani governorates, the research examines the usage, pronunciation and recognition of these words among native speakers. The study suggests that while these terms may share origins with Farsi and Hindi, their phonetic features and local pronunciations point to more direct borrowing from Balushi. The research highlights the impact of multilingualism in Oman and the subtle ways in which borrowed words become embedded in local identity. Despite the limited sample size, this paper encourages further investigation into linguistic borrowing and regional variation in Oman.
Keywords: Linguistique -- Oman

Sijilmasa: The Capital of Gold and Trade Caravans During the Reign of the Banu Midrar (140 AH – 366 AH / 757 CE – 976 CE) - Ahmed, Naima Abdulmawla Salem (Bani Waleed University Journal of Humanities and Applied Sciences, 2025)
During the reign of the Banu Midrar (140–366 AH / 757–976 CE), the city of Sijilmasa witnessed significant economic development in various aspects, particularly in trade. This study focuses on the role played by the Banu Midrar in revitalizing commercial caravan routes and organizing trade networks during their rule. It also highlights their efforts to establish extensive trade relations with the Eastern Islamic world, North Africa, al-Andalus, and Sub-Saharan Africa, with gold being one of the most prominent commodities exchanged. The researcher adopted an analytical inductive approach to examine historical events and facts and to understand the motivations behind the imposition of taxes and customs on land and maritime trade by the Banu Midrar, which contributed to elevating Sijilmasa’s global commercial status during the 2nd to 4th centuries AH (8th to 10th centuries CE). Additionally, the researcher employed the descriptive method to trace and analyze historical developments, while also incorporating other scientific methodologies where necessary. This approach led to findings that underscore the pivotal role of the Banu Midrar Emirate in the flourishing of trade in Sijilmasa.
Keywords: Commerce transsaharien; Histoire -- Sidjilmassa

Archaeometallurgy in northern Oman—Diachronic copper production on a smelting site in Wadi al-Salh - Bukowski, Krzysztof; Pieńkowska, Agnieszka; Woronko, Barbara; Moska, Piotr; Kiersnowski, Hubert; Piestrzyński, Adam; Ghafri, Waleed Awabh Harib Said al- (Archaeometry, 2025)
Archaeometallurgical studies at the Salh site in northern Oman have provided new data on copper technology in the Bronze Age and Islamic periods. Archaeological results indicate that it may have functioned seasonally. Slag analyses have shown possible technological changes over the centuries. Smelting was carried out under reducing conditions, using oxidized copper ores weathering zone deposits. The scale of copper production at Salh1 was relatively small in both periods, but—due to its strategic location near important trade routes—the site could have functioned as part of a short-range as well as long-range mercantile network.
Keywords: Archéologie -- Oman

Ibāḍīsm in the Eastern Ḥanafite (-Māturīdite) Firaq Tradition -With Special Reference to Abū Muṭīʿ Makḥūl b. al-Faḍl al-Nasafī’s (d. 318/930) Kitāb al-Radd- - Gömbeyaz, Kadir (Hitit İlahiyat Dergisi, 2025)
Compiling the political-theological groups and doctrines that emerged within Islamic society has been a genre of literature that Muslim scholars have paid attention since the early periods. While some of these works, generally focusing on the ideas of these groups, attempt to gather data about them, others are not content with this and aim to demonstrate their erroneous views and the extent to which they have deviated from the right path. Therefore, heresiography has often proceeded not as a field study but on a theoretical basis and, at times, with ideological concerns. Various researchers have suggested that within the broader heresiographical literature, certain traditions of sect classification have emerged, distinguished by their approaches, classifying methods, and the types of information they use regarding the sects. One such classification tradition is the Eastern Ḥanafite (-Māturīdite) Firaq Tradition, which emerged in the Khorasan and especially Transoxiana regions, developed by authors who defined themselves in terms of theological identity as Ḥanafite and, in later centuries, as an extension of this, Māturīdite. The most striking feature of this tradition is that it places the 73-sect ḥadīth at the center of its classification, reaching this number through a mathematical formulation in which six main heretical sects, each consisting of twelve sub-groups, are combined with the one saved sect: 6x12+1=73. This study examines how the Eastern Ḥanafite (-Māturīdite) Heresiographical (Firaq) Tradition, with its distinctive characteristics, perceived Ibāḍism through the narrative found in its earliest and most comprehensive surviving example: Kitāb al-Radd ʿalā al-bidaʿ wa al-ahwāʾ al-ḍālla by Abū Muṭīʿ Makhūl b. al-Faḍl an-Nasafī’s (d. 318/930). This work has been chosen due to its fundamental role in shaping the later heresiographical works of this tradition. The study not only analyzes Abū Muṭīʿ’s depiction of Ibāḍism; but also compares it with other examples of the same tradition when necessary. Furthermore, the accuracy of the information provided about the Ibāḍīs in the work is scrutinized. Although some of the views attributed to Ibāḍism may lead to misunderstandings due to omissions or inaccuracies, they can be said to largely align with actual Ibāḍī beliefs. However, there is one particular point that seems difficult to reconcile: the statement attributed to the famous ṭābiʿī scholar Qatāda, describing the Ibāḍiyya as "Magians of this ummah." In the Islamic intellectual tradition, the school that has been compared to or associated with Magianism, based on a reference to a ḥadīth narration, is in fact the Qadarīyya and its later extension, the Muʿtazila. The similarity sought to be established between these sects and the Magians is based on the dualistic belief in God held by the Magians -one god being the source of all good and the other being the source of all evil- while the Qadarīyya and Muʿtazila, regarding human actions, see God as the creator of good and humans as the bringers of evil into existence. However, there is no possibility of establishing such a similarity between the Ibāḍiyya and Magianism through the belief in God or human actions. This is because the Ibāḍīs reject the idea that humans create their own actions and attribute both good and evil to God. What is the source of this attempted connection between the Ibāḍiyya and the Magians, which we only encounter in the Eastern Ḥanafite (-Māturīdite) Firaq Tradition? The findings of our research within the scope of this study indicate that this connection is likely based on an misreading or scribal due to the similarity in the written forms of the words Ibāḍiyya and Ibāḥiyya in the works of this tradition. A distinct characteristic of the Eastern Ḥanafite Firaq Tradition, the views of each sect are refuted, and the responses of the saved sect along with the correct view on the relevant issue are presented. At this point, Abū Muṭīʿ first presents the views of the Ibāḍiyya and then proceeds to criticize them. In conclusion, from the perspective of the Eastern Ḥanafite (-Māturīdite) Firaq Tradition, Ibāḍism is considered one of the twelve heretical subgroups of Ḥarūriyya/Nāṣibiyya (i.e., the Khārijites), which is one of the six main deviant sects among the 72 misguided ones. Based on the views attributed to it, especially the baseless analogy established with the Magians, it is understood that the authors of the tradition did not have direct knowledge of the Ibāḍīs or contact with them. Ultimately, within this tradition, sects like Ibāḍism are not seen as ideological formations to be understood, but rather as ones to be rejected.
Keywords: Hérésiographie -- Ibadisme

العلاقات التجارية الامريكية العمانية (1856-1833) - يوسف, دلال أمير (مجلة دراسات في التاريخ والآثار, 2025)
Keywords: Relations -- Oman -- Etats-Unis

الاهتمام الإباضي بالتفسير القرآني: الآراء التفسيرية للجيطالي (ت: 750ه) من خلال كتابه قناطر الخيرات، أنموذجا - الوائلي, سعيد بن سليمان (مجلة کلية الدراسات الإسلامية والعربية للبنات بالإسکندرية, 2025)
هذا البحث متعلق بمجال التفسير القرآني، يظهر اهتمام المذهب الإباضي بعلم التفسير من خلال إبراز الآراء التفسيرية لعلمائهم، فمن تلك الجهود الآراء التفسيرية المبثوثة في كتاب قناطر الخيرات لأبي طاهر الجيطالي، أحد أعلام المذهب الإباضي، فبجانب الأهمية العلمية والمكانة التاريخية والقيمة المعرفية التي يحملها الكتاب، نجد فيه اهتماما علميا في الجانب التفسيري للقرآن الكريم، بما يظهر المعنى الذي يراه مؤلف كتاب القناطر في النصّ القرآني.من الأسباب التي دفعتني إلى اختيار هذا الموضوع ارتباطه بمباحث علوم القرآن الكريم، وعلم التفسير على وجه التحديد، وما يتصل بكتاب قناطر الخيرات الذي يجد فيه الباحث اهتمامات علمية متنوعة من تزكية للنفس وارتباط بفنون العلم المختلفة.ولموضوع البحث أهميته التي يستمدها مما ينتسب إليه من علم، حيث له ارتباط وثيق بأهل العلم والعلماء، وبعلوم القرآن الكريم والتفسير للنص القرآني وما له من دلالات وإرشادات ربانية، ومن جهة أخرى له علاقة بما قدمه طائفة من علماء المسلمين ممن ينتمون إلى جبل نفوسة وما حولها، فقد تأكد ارتباطهم بعلم التفسير والاهتمام به. مشكلة الدراسة تكمن في النظرة إلى اهتمام المذهب الإباضي بالتفسير القرآني، بسبب ما يُرى من قلة المؤلفات في علم التفسير في الظاهر. فهل نجد للمذهب الإباضي اهتماما بعلم التفسير؟ وما النماذج الدالة على ذلك؟ويتفرع عن ذلك الأسئلة التالية: - ما مدى الاهتمام بالتفسير عند الجيطالي؟- ما مجالات الآراء التفسيرية لدى الجيطالي؟- كيف عرض لنا الجيطالي آراءه التفسيرية في كتابه قناطر الخيرات؟تكمن أهداف هذا البحث في النقاط التالية:
Keywords: Coran -- Commentaires -- 14e siècle; Jayṭālī, Ismāʿīl b. Mūsà (13..-1350)

العلاقات التجارية والثقافية بين المغرب والسودان الغربي خلال القرنيين الثاني والثالث الهجريين - حبيبي, إسماعيل (دورية کان التاريخية: المستقبل الرقمي للدراسات التاريخية, 2025)
Keywords: Commerce transsaharien

صالح بن يوسف قبل اليوسفيّة (1945-1955): بيوغرافيا استعاديّة - السباعي, فوزي (دورية کان التاريخية: المستقبل الرقمي للدراسات التاريخية, 2025)
Keywords: Ben Youssef, Salah 1907-1961; Biographies -- Djerba -- 20e siècle

رحلتي إلى جزيرة «جربة» حيث التاريخ والتنوع والعيش المشترك - العبري, بدر بن سالم (المسار, 2025)
Keywords: Manuscrits -- Djerba; Récits de voyage -- Djerba

الأوبئة والأمراض في عمان بين التوثيق والاغفال (13-14هـ/19-20م): دراسة تاريخية تحليلية - الهنائي, سليم بن محمد; الخاطرية, خلود بنت حمدان; الندابي, ناصر بن علي; الجهورية, أحلام بنت حمود (مجلة التاريخ المتوسطي, 2025)
Keywords: Epidémies -- Oman

أضواء على الأوضاع السياسية والاقتصادية في سلطنة مسقط وعُمان في النصف الأول من القرن 20م، وتداعيات ح ع1 - العواني, عمر علي خميس (وقائع تاريخية, 2025)
سيعنى هذا الموضوع بدراسة انعكاسات الأوضاع السياسية الاقتصادية العالمية على سلطنة مسقط وعُمان في النصف الأول من القرن العشرين، بدايةً بالتركيز على انتقال سلطة القرار السياسي والاقتصادي في سلطنة مسقط وعُمان إلى قوى عظمى كان لها دور في الأحداث السياسية والاقتصادية الداخلية، ولعل أقواها كانت السلطات البريطانية؛ ومن جملة ما سنتطرق إليه في هذا البحث أيضاً هو قضية الصراع الأوروبي في منطقة الخليج العربي وآثار ذلك على حكومة مسقط وعُمان. وكذا انعكاسات الصراع البريطاني - الأمريكي على الامتيازات النفطية في السلطنة قبيل وخلال الحرب العالمية الثانية، وسيكون تركيزنا على مرحلة مهمة من تاريخ سلطنة عُمان المعاصر، وهي المرحلة التي حكم فيها السلطان تيمور بن فيصل الذي حكم عُمان من عام 1913 وحتّى عام 1932م، ومن الإشكاليات التي تناولتها الدراسة باتباع المنهجين الوصفي والتاريخيَّ؛ هو كيف رسمت بريطانيا خطة تدمير الحياة السياسية والاقتصادية بعُمان منذ نهاية القرن 19م؟ من أجل وضعها تحت السيطرة والتبعية، وكيف ساهمت في تدهور الحالة السياسية والأمنية والاقتصادية والمالية في النصف الأول من القرن العشرين لمدّ نفوذها في الساحل العُماني؟ كما تفرعت هذين الإشكاليتين إلى تساؤلين مهمين هما: ما هو الوضع السياسي الداخلي لعُمان، ودور بريطانيا في تأجيج الصراع الداخلي بين داخلية عُمان وحكومة مسقط؟ وما هي الأوضاع الاقتصادية للسلطنة بين الحربين والتداعيات السلبية للأزمة الاقتصادية العالمية؟
Keywords: Vie politique -- Oman -- 1913-1932

Transformations of Housing in the M'Zab Valley: Contemporary Urban Challenges and Threats to Identity - Islam, Snoussi Mohamed; Dhaher, Najem (Proceedings of the international conference of contemporary affairs in architecture and urbanism-ICCAUA, 2025)
The ksour of the M’Zab Valley, located in southern Algeria, were founded in 1101 by the Mozabites. These fortified villages, in their original configuration, incorporate exemplary architectural and urban planning elements, promoting sustainable habitation that is perfectly adapted to the Saharan context while reflecting local cultural identity. In recognition of their outstanding universal value, UNESCO introduced specific preservation and protection measures as early as 1982. Architect André Ravéreau described this valley as a true “lesson in urban planning”, highlighting a remarkable balance between functionality, sustainability, and respect for the Saharan ecosystem. However, the recent urbanisation transformations in the M’Zab Valley, which are the subject of my doctoral thesis, reveal significant changes. New development projects, located outside the walls surrounding the ksour, are multiplying to meet a growing demand for housing. Although necessary, these interventions create a rupture with the urban landscape and the Saharan architectural identity. A chronological analysis of architectural samples makes it possible to trace the elements that have been abandoned, reproduced, or transformed over time, while questioning how these developments reflect Saharan identity and impact the built heritage.
Keywords: Urbanisme -- Mzab

Bioclimatic and Vernacular Approaches in Hot and Aride Climate at Urban Scale: A Comparison on M'Zab and Yazd Valleys - Yılmaz Yıldırım, Demet; Selmani, Hanane (Journal of Planning, 2025)
Keywords: Urbanisme -- Mzab

مشروع الخالص السياسي ومالمح المنقذ في الإمامة الإباضية - تغلات, زهير (أفاق معرفية, 2025)
Keywords: Imamat -- Ibadisme

جماليّة القبح والعهر في رواية التّقارير السريّة لدولة الزّعيم لمنّوبي زيّود - البوجديدي, علي (أفاق معرفية, 2025)
يتناول المقال جماليّة القبح والعهر في رواية التّقارير السريّة لدولة الزّعيم للرّوائيّ التونسيّ منّوبي زيّود. وهي رواية حديثة تعالج قضايا السّياسة والمجتمع وتستخدم معجم العُهر والقُبح، إذْ وجدنا السّارد يستعرض عالم المرأة العاهرة، وينبش في عالم السّياسيّ المشوّه، كما ينغُر في الأجساد المحرّفة تحريفا هزليّا ساخرا، مُستجليا سيمياء الألوان بين همس وفضح، ويحرِص على تصوير شخوص الرّواية بعناية مركِّزا على طابعها الوحشيّ. ولا أدلّ على أهميّة العهر والقبح ثيمة الرّواية الأبرز من انفتاحها على مقطع يكرِّس صورة الوسخ مكانا وشخوصا فمدينة العُهر أسلمت روحها لرهط من اللّصوص الجدد، تجلّى في عهر شخوصها وأمكنتها، وزمانها. بموازاة عُهر الشخصيّات وقبحها، اقترن العهر والقبح كذلك سيميائيّا بالسّواد، سوادٌ حالك يطبع غلاف الرّواية ولا تقطعه غير صحائف بالية تشهد على الماضي وتدوّن بحبر أحمر تقارير سريّة، وهو ما يفضح منذ البدء عن عالم الرّواية التّخيليّ وتماسّه مع المرجعيّ والمعيش.
Keywords: Littérature -- Djerba

Comparative Study of Intimacy Between Millennial Vernacular Islamic Habitat of M’zab and Standardized Modern Habitat - Krimo, Dahmani (Journal of Islamic Architecture, 2025)
Understanding intimacy within a habitat is crucial to deciphering its human and social dynamics. Human habitation's conceptual and poetic content inspires both the creation and philosophical thinking of societies. Heidegger connected art, space, and architecture of human habitation by responding to the aspirations of their inhabitants. In this sense, private life constitutes a boundary between private and public family life. In Islamic architecture, this sustainable concept is intergenerational, translating sensory experiences into spatial design. We aim to quantify this concept by comparing Islamic and modern architecture. By integrating ophthalmology calculations, those of J. Panero and M. Zelnik, and the interpersonal communication thresholds of Hall and Moore, we calculated the dynamics of spatial and superficial intimacy based on gender. Differences have been observed between Mozabite Islamic architecture in Algeria, recognized as a UNESCO World Heritage Site, and modern architecture. According to Shannon and Weaver, the information is coded messages and measurable quantities. The internalization or exteriorization of intimacy is essential to understand its vernacular or modern typology. The resonance of gender frequencies undoubtedly forms the basis of a relatively effective strategy for protecting privacy within human habitats. This approach facilitated the development of a sensory imprint for the opulent vernacular Islamic habitat of M'Zab.
Keywords: Architecture -- Mzab

Characterization and distribution of microplastics on the beaches of Southern Tunisia: a case study of the Island of Djerba - Guesmi, Mohamed; Ouri, Abir; Jlalia, Ibtissem; Cherni, Makrem; Ben Ammar, Hajer; Chatti, Saber; Grassl, Bruno; Souissi, Radhia; Abderrazak, Houyem (Euro-Mediterranean Journal for Environmental Integration, 2025)
Microplastics (MPs), resulting from the degradation of plastic waste, were investigated on eight beaches on the Island of Djerba, located in the Gulf of Gabes in Tunisia. The study included 96 sediment samples collected in the summer of 2021 from four beach zones (dune, upper beach, coastline, and lower tidal line). The MPs were obtained using the NaCl density separation method and quantified through microscopic observation. MPs were classified based on shape, size, and dominant color. In addition, Fourier Transform Infrared Spectroscopy in attenuated total reflectance mode (FTIR-ATR) was used to identify the polymer composition of representative MPs. The results revealed microplastic concentrations ranging from 23 particles/kg at Gallela Beach to 126.67 particles/kg at Yati 2 Beach, with the highest accumulation found in the dune zone (65%) compared to the other zones. The samples were dominated by fragmented and fibrous MPs, with blue, red, and black being the most abundant colors. Polymer analysis revealed that polyethylene (PE) was the most abundant polymer, followed by polypropylene (PP) and polystyrene (PS). This study highlights significant spatial variability in the distribution of the microplastic on Djerba beaches, influenced by tourism, fishing, and urban runoff. These findings underline the urgent need for sustainable waste management to reduce microplastic pollution of the Island of Djerba and in Zarzis.
Keywords: Crises environnementales -- Djerba

Identification of Secondary Metabolites from Origanum majorana L. (Lamiaceae) Essential Oil Cultivated in Island of Djerba; Antibiofilm, Anticoagulant and Phytotoxic Properties - Bouomrine, Sonia; Melliti, Marwa; Harzallah-Skhiri, Fethia; Jannet, Hichem Ben; Faisal, Mohammad; Alatar, Abdulrahman A.; Flamini, Guido; Edziri, Hayet (Chemistry Africa, 2025)
Origanum majorana L. is an aromatic plant from the Lamiaceae family, considered as one of the popular plants in Tunisia since it was known to have many biological potentials and frequently grown in gardens as a condiment plant. The aim of this work is to explore the chemical composition, the antimicrobial, antibiofilm, anticoagulant and insecticidal activities of the flowering aerial parts extracts and the essential oil (EO) of this plant. The essential oil was extracted by hydrodistillation and analyzed using GC/MS. Polyphenols, flavonoids and tannins were quantified from three organic extracts. The antimicrobial activities were assessed against 8 bacteria; 4 Gram negative and 4 Gram positive ones; and 4 fungal strains. The biofilm inhibition was determined in vitro by the micro dilution method against 3 bacteria. Prothrombin time (PT) and kaolin clotting time (KCT) tests were employed to investigate the anticoagulation potential for the first time. The repellent activities of the organic extracts and the fumigant activity of the EO were studied. The flowering aerial parts EO is rich in oxygenated monoterpenes (54.38%) especially in terpinen-4-ol. For the antimicrobial activities, the tested oil displayed moderate antibacterial and antifungal activity (MIC = 1.5 mg/mL), and showed a good antibiofilm activity against the tested bacteria with inhibition values greater than 51 ± 1.04% at MIC dose. Furthermore, it has anticoagulant activities with a prothrombin time of 37.3 ± 0.36 s and KCT of 48.1 ± 0.26 s at a concentration of 15 mg/mL, as well as fumigants activities against Tribolium castaneum. Polyphenols and tannins contents were found to be the highest in ethyl acetate and ethanolic extracts. The two extracts showed interesting antibacterial and antifungal activity with values of MIC ranging from 1.25 to 10 mg/mL, and from 2.5 to 20 mg/mL, respectively. Also, they present a strong antibiofilm activity at different MICs. Ethyl acetate extract has an interesting anticoagulant activity at a concentration of 0.5 mg/mL with 52.18 ± 0.49 s for KCT. Ethanolic extract is a promising anticoagulant agent (16.9 ± 0.02 s for PT and 45.72 ± 0.24 s for KCT at a concentration of 0.5 mg/mL). Only Petroleum ether extract has repellent activities (62.5 ± 8.5%) against an insect pest tested. The aerial parts of Origanum majorana could be considered as new source of anticoagulant, antibiofilm, antibacterial, antifungal and insecticide molecules for pharmaceuticals and pest purposes. However, further research must be undertaken to identify the active molecules responsible for these biological activities.
Keywords: Botanique -- Djerba

Zanzibar was a country: exile and citizenship between East Africa and the Gulf: Nathaniel Mathews, Oakland, CA, University of California Press, 2024, 358 pp., $29.95/£25.00 (paperback), ISBN: 9780520400702 - Nicholson, Timothy (Global Change, Peace & Security, 2025)
Keywords: Recension

الجانب السياسي وأثره في نشأة الخوارج وفرقها - عبد الرحمن, فتحي محمود محمد (مجلة کلية الدراسات الإسلامية والعربية للبنات بسوهاج, 2025)
الملخص: فرقة الخوارج من الفرق التي ظهرت منذ زمن بعيد ولا تزال افكارها موجود في زمننا هذا فالخوارج من أشد الفرق الإسلامية تمسكاً بمذهبها الذي تعتقده وتدعو إليه، وتحاول تطبيقه بالقوة، مستخدمة القتل والفتك بالأنفس المحرمة إذا اقتضى الحال؛ فهي فرقة كبيرة من الفرق الاعتقادية، وتمثل حركة ثورية عنيفة في تاريخ الإسلام السياسي، وقد شغلت الدولة الإسلامية فترة طويلة من الزمن؛ حيث بسطوا نفوذهم السياسي على بقاع واسعة من الدولة الإسلامية في المشرق وفي المغرب العربي، ولا يخفى أن بعض أفكار الخوارج المتعلقة بتكفير العصاة لا يزال لها أتباع يمثلون تنطع الخوارج وتشددهم في وقتنا الحاضر؛ مما يستدعي عرض ودراسة هذه الفرقة، وما أنتجت من آراء وأفكار، وبيان ما جناه أتباعها على الإسلام والمسلمين، كما أن من أسباب اختياري لهذا الموضوع هو معرفة الطبيعة السياسية والعسكرية لهذه الحركة المعارضة والتعرف على الدور السياسي الذي لعبته الحركة الخارجية خلال هذه المرحلة من التاريخ الإسلامي؛ ولهذا كان اختياري لهذا البحث الجانب السياسي وأثره في نشأة الخوارج وفرقها، وقد استخدمت في هذا البحث المنهج التحليلي القائم على تحليل محتويات النصوص واستخراج المعنى منها، وإبرازه في صـورة مبسطة، وصياغتها بصيغة موضوعية، وقد اشتمل البحث على مقدمة، وتمهيد، وثلاثة مباحث، ثم خاتمة، وفهرس للمصادر والمراجع. Abstract: The Kharijites, one of the earliest Islamic sects, continue to hold relevance in contemporary times. They are characterized by their unwavering adherence to their beliefs, their willingness to enforce them through violence, and their designation of those who deviate from their doctrine as apostates. As a significant ideological group and a revolutionary movement in Islamic political history, the Kharijites held sway over the Islamic state for an extended period. Their political influence extended across vast regions of the Islamic empire, both in the East and the Maghreb. It is undeniable that some of their ideas regarding the excommunication of sinners still resonate with modern-day extremists, embodying the Kharijites' extremism and rigidity. This necessitates a thorough examination of this sect, its doctrines, and the detrimental consequences of its actions for Islam and Muslims. My motivation for delving into this topic stems from a desire to understand the political and military nature of this oppositional movement and its role in shaping Islamic history during this crucial era. Consequently, I have chosen to focus on the political aspects and their impact on the emergence of the Kharijites and their various sects. The research methodology employed in this study is analytical, involving the analysis of textual content to extract and present its essence clearly and concisely, adhering to an objective tone. The study is structured as follows: an introduction, a preface, three chapters, a conclusion, and an index.
Keywords: Kharijisme

التدوين التاريخي ومنهجه عند إباضية المغرب ما بين القرنين (10-4ه/16-10م) - زيان, علي (مجلة الإنسان والمجال, 2025)
تعالج هذه الورقة البحثية التدوين التاريخي عند فرقة الإباضية ببلاد المغرب بعد سقوط الدولة الرستمية بتهرت وتفرق أهلها بين أقاليمه، رغم ذلك عملوا على تثبيت فكرهم وعقائدهم وتاريخهم وتدوينه، في محاولة منهم لعدم اندثاره، وكان اهتمام مفكريهم وفقهائهم الكبير بتاريخ مذهبهم وأخبار دعاتهم الأوائل، وأئم رائمة دولتهم المندثرة، وسير علمائهم، وبناء على ذلك سنحاول رصد الفكر التاريخي الإباضي عن طريق التعريف بأهم أعلامه والموضوعات التي كتبوا فيها والمصادر والموارد التي اعتمدوا عليها في مؤلفاتهم، والمناهج التي اتبعوها في ذلك. ومن النتائج المتوصل إليها أن جل مؤلفاتهم قد تميزت بالمذهبية، فقد اعتنت بتدوين تاريخ الاباضية دون غيرها، وترجمت لأعلام المجتمع الإباضي من الفقهاء والمحدثين والعلماء وانتقدت الحركات المناوئة والمخالفة لمذهبهم. وسلكوا في ذلك عدة مناهج متميزة عن سابقيهم أو المعاصرين لهم من المؤرخين المسلمين في توجهاتهم وميولاتهم وطرق نقلهم وأسلوبهم وعرضهم للمادة التاريخية في مصنفاتهم.
Keywords: Prosopographie -- Afrique du Nord

Un projet d’alliance entre Kilwa et la France contre l’expansionnisme omanais, étude d’une lettre en arabe de mfalme Sulaymān b. Ḥasan à Louis XVIII - Belhacel, Abdelhakim; Qaisi, Fu’ad al- (Afriques. Débats, méthodes et terrains d’histoire, 2025)
La série « Réunion » des Archives nationales d’outre-mer conserve plusieurs lettres en arabe issues des correspondances entre les Français et les souverains musulmans d’Afrique de l’Est. L’une d’elles, écrite en 1819, est traduite en français et éditée pour la première fois. Son étude apporte un éclairage crucial sur la nature des relations entre Swahili, Omanais et Français au début du xixe siècle. Elle fait apparaître l’importance des réseaux négriers pour la diplomatie française et leur persistance après l’abolition officielle de la traite. Elle permet également de comprendre comment le sultanat de Kilwa tente de se défaire de la mainmise omanaise. De plus, elle montre l’importance de l’emploi de la langue arabe pour les correspondances diplomatiques dans l’océan Indien. La lettre de mfalme Sulaymān b. Ḥasan à Louis XVIII vise en effet à sceller une alliance entre la France et le sultanat de Kilwa contre les Omanais installés à Zanzibar, grâce aux bons offices d’un arabisant et d’un négrier. L’étude de ce document comprend une reproduction et une analyse de la lettre et de son enveloppe, une retranscription, une traduction et une analyse permettant de comprendre le contexte (acteurs, situation politique) et de dégager ses apports quant à la connaissance des stratégies de résistance des souverains swahili face à l’expansionnisme omanais en Afrique de l’Est.
Keywords: Relations -- Zanzibar -- Qilwa; Vie politique -- Zanzibar -- 1806-1856

تأسيس الفكر الأصولي في المدرسة الإباضية في القرون الهجرية الثلاثة الأولى - السعيدي, فيصل بن علي (مجلة جرش للبحوث والدراسات, 2025)
Keywords: Ibadisme -- thèmes et motifs

موقف هود بن محكم الهواري من آيات العقيدة في تفسيره اليوم الآ خر أنموذجاً - عبدالعال, كمال عبد العال تمام (مجلة القلم للعلوم الإنسانية والتطبيقية, 2025)
Keywords: Coran -- Commentaires -- 9e siècle

Traditional Irrigation installations in the M’zab Valley - Zaaba, Omar (Herodotus' Journal of the Human and Social Sciences, 2025)
Keywords: Agriculture -- Mzab; Irrigation -- Mzab; Puits -- Mzab

طريقة التفسير بالمأثور وبالرأي في الآراء التفسيرية للشماخي من خلال كتابه الإيضاح - الوائلي, سعيد بن سليمان (مجلة شروس, 2025)
الملخص: لهذا البحث عناصر علمية مهمة مرتبطة بالعلوم الشرعية، التي من أهمها علم التفسير القرآني، وعلم الفقه بما يشتمل عليه من فروع، من خلال كتاب فقهي يتعرض فيه صاحبه إلى ذكر الآيات القرآنية وبيان المعاني المتعلقة بها، وهو في ذلك يعتمد على طريقة المفسرين بالمأثور وبالرأي، ثم يظهر المعنى الذي يراه في النصّ القرآني. من الأسباب التي دفعتني إلى اختيار هذا الموضوع ارتباطه بعلم التفسير الذي له الشرف والرفعة، وما يتصل بالجانب الفقهي في كتاب الإيضاح الذي يزخر بالمعاني التفسيرية، لتتحدد رؤية مؤلفه في الوسط العلمي بين أهل العلم والمعرفة. إن للموضوع أهميته التي يستمدها مما ينتسب إليه من علم، فمن جهة له اتصاله الوثيق بدرجات العلم والعلماء، ومن جهة أخرى له ارتباط بالقرآن الكريم وعلومه، وبعلم التفسير للنص القرآني وما له من دلالات وإرشادات ربانية، ومن جهة ثالثة له ارتباط بعلم الفقه وفروعه المتعددة التي طرقها صاحب الإيضاح في كتابه. وله ارتباط بما قدمه طائفة من علماء المسلمين ممن ينتمون إلى جبل نفوسة وما حولها، فقد تأكد ارتباطهم بعلم التفسير والاهتمام به. مشكلة الدراسة تكمن في البحث عن الاهتمام بالتفسير القرآني لدى المذهب الإباضي، في المؤلفات الجامعة لأبواب العلوم الشرعية من التوحيد والفقه وغيرها، فهل نجد لذلك أثرا في المؤلفات الإباضية؟ ويتفرع عن ذلك الأسئلة التالية: ما مدى الاهتمام بالتفسير عند علماء المذهب الإباضي؟ هل يوجد في كتاب الإيضاح ربط بين علم الفقه وعلم التفسير؟ ما المنهج الذي اتبعه صاحب كتاب الإيضاح في آرائه التفسيرية؟ وهل اعتمد في الآراء التفسيرية على طريقة التفسير بالأثر أم بالرأي أم جمع بينهما؟ تكمن أهداف هذا البحث في النقاط التالية: إبراز الاهتمامات التفسيرية لدى فقهاء المذهب الإباضي. بيان الترابط بين علم التفسير وعلم الفقه في منظومة تكاملية. إظهار المنهج الذي يتبعه مؤلف كتاب الإيضاح من طرق التفسير في آرائه التفسيرية. إبراز أثر المزج بين طرائق التفسير فيما ينتجه علماء التفسير خدمة للنص القرآني. قد اعتمدت في هذا البحث على المنهج الاستقرائي والمنهج التحليلي من بين المناهج البحثية. عرضت مادة البحث في تمهيد ومبحثين مع المقدمة والخاتمة: يتضمن التمهيد تعريفا بالشماخي ومكانته العلمية، جاء في المبحث الأول بيان لطريقة التفسير بالمأثور عند الشماخي، ونماذج للآراء التفسيرية بهذه الطريقة من كتاب الإيضاح، والمبحث الثاني جاء فيه بيان لطريقة التفسير بالرأي عند الشماخي، ونماذج من آرائه التفسيرية بها، ثم الخاتمة وفيها أبرز النتائج التي توصل إليها البحث. والحمد لله رب العالمين أولا وأخيرا،
Keywords: Fiqh -- Commentaires

En quête d'autonomie: Un couple de rachetés dans la mission catholique de Bagamoyo, Tanzanie (1890-1920) - Nivière, Adèle (Revue d'histoire contemporaine de l'Afrique, 2025)
Bagamoyo, ville de la côte swahilie en Tanzanie actuelle, a été un point névralgique de la traite des esclaves en Afrique de l’Est du xixe siècle au début du xxe siècle. Dans ce contexte, les missionnaires catholiques ont racheté de nombreux esclaves pour les convertir. Une fois mariés, ces anciens esclaves étaient installés dans des villages chrétiens. Cet article retrace la trajectoire d’un de ces couples, à l’échelle individuelle, à travers l’éclairage des registres paroissiaux. Ces archives se révèlent utiles pour retracer les parcours d’émancipation, en particulier du point de vue de la famille, domaine central de la politique missionnaire. Le jeune couple navigue dès lors, en fonction d’opportunités genrées, entre l’insertion dans une communauté affective et religieuse chrétienne, et les réseaux économiques d’appartenance alternatifs offerts dans les villes de la côte swahilie, en dehors du cadre de la mission.
Keywords: Esclavage -- Zanzibar

عقوبة النفي وتطبيقاتها في المجتمع المزابي خلال القرن 15م إلى القرن 19م دراسة مقارنة بين الفقه الإسلامي وقانون العقوبات الجزائري - ازغار, يحيى (مجلة الاجتهاد للدراسات القانونية والاقتصادية, 2025)
Keywords: Droit coutumier -- Mzab

The Status of the Musnad of Rabi‘ bin Ḥabīb as an Authoritative Ḥadīth Source in Ibāḍī Scholarship - Arifah, Afro’ Anzali Nurizzati; Muhid; Muthoharoh, Isnaini Lu’lu’ Atim; Khaira, Zsazsa Tuhfa (Journal of Hadith Studies, 2025)
The Musnad Rabi' bin Habib book contains the hadiths of the Prophet SAW which were narrated by Imam Rabi' bin Habib as the third Ibadi imam from the khawarij group of the al-Ibadiyah sect. The existence of this book has become the center of attention for several scholars regarding the period of codification and the quality of the hadith in it. Apart from that, this book was also declared an authentic hadith book by al-Ibadiyah himself because the hadiths in it were in accordance with the ideology they adhered to. This research aims to look further at how this hadith book can be declared as an authentic hadith book for al-Ibadiyah as well as some criticisms from hadith scholars. The research method used in this research is qualitative with a library research type of research and uses a socio-historical approach. This socio-historical approach is used to see the history of this hadith book so that it can be called an authentic hadith book for al-Ibadiyah himself. The results of this research provide evidence of the extent to which the book Musnad Rabi' bin Habib is an authentic hadith book of Khawarij al-Ibadiyah which has become a reference and has received a lot of criticism from several hadith scholars.
Keywords: Hadith -- Ibadisme

Time of magan (2022-23): The ras al jinz project, excavation & survey - Azzarà, Valentina M.; De Rorre, Alexandre P. (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The project is focused on exploring the Neolithic and Early Bronze Age (EBA) occupations of Ras Al Jinz RJ-3. This site remained un touched until recent excavation efforts by Time of Magan, revealing that during the Umm an-Nar period, RJ-3 likely constituted a part of a larger settlement in conjunction with RJ-2, situated across the bay. Findings from five seasons of excavation suggest not only the existence of craft-centred zones during this era, but also evidence of earlier settlements associated with daily life. The project’s goal is to gather new information from these settlements, thereby highlighting the way of life of southeastern Arabian communities. The study of village life, social interactions, activity organisation, and economic diversification at the community level, will provide new insights into the factors that led to the EBA complexification, and will help determining the influence of local and foreign contributions. Fur thermore, the excavation of RJ-3 concludes a comprehensive series of investigations into the EBA occupations of the bay, illuminating a pivotal complex where both settlement evidence and funerary remains have been meticulously examined. New explorations in the bay will also contribute to the museumification of Ras Al Jinz and support its nomination for inclusion in the UNESCO Heritage List.
Keywords: Archéologie -- Oman

Omani-polish archaeological mission 2022: Excavations at QA20 and QB2 in the qumayrah micro-region - Bieliński, Piotr; Pieńkowska, Agnieszka; Szymczak, Agnieszka; Iskra, Mateusz (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
During the 6th season of investigations, the Omani-Polish expedition researched previously unexcavated sites in the micro-region of Qumayrah in the Al Hajar Mountains: QA 20, located near Ayn Bani Saydah, and QB 2, near the village of Bilt. The exploration at QB 2 uncovered a substantial Umm an-Nar settlement, offering insight into its layout and architecture, despite the challenges of removing layers of stone rubble. Additionally, the preliminary documentation of a round stone structure, likely of Umm an-Nar origin, was undertaken at QB 6. QA 20, an Iron Age II hilltop site, revealed an unexpectedly advanced organisation of space, resembling urban planning more than a rural settlement, challenging previous assumptions.
Keywords: Archéologie -- Oman

Project VirtuHalban (2023): Italian anthropological mission for the heritage of arabia - Bortolini, Eugenio; Benazzi, Stefano (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Project VirtuHalban investigates an Early Bronze Age funerary site at Halban, on an elevated coastal terrace where the Al Batinah coastal plain meets the Hajar Al Gharbi mountain ridge. These well-preserved monumental tombs, some reaching heights of over four metres, are significant markers of their era. Research suggests that the Halban tombs may span two distinct periods: the Hafit period (c. 3100-2600 BCE) and the Umm an-Nar period (c. 2600-2100 BCE), indicating a transition in tomb design during the Bronze Age. The project also investigates building techniques and materials employed in tomb construction, potentially having cultural or chronological significance. Excavation of tomb HAL021 during the 2023 season yielded valuable insights into its contents, including small beads and human remains, providing potential clues about the people buried in the tomb and their cultural practices. To enhance documentation, the researchers used 3D/virtual recording techniques, allowing for precise spatial mapping and the creation of 3D models and panoramas.
Keywords: Archéologie -- Oman

Tectonostratigraphy of the Ediacaran Fara Formation of the Central Oman Mountains (Jabal Akhdar, Sultanate of Oman): implications for the Late Neoproterozoic evolution of the Eastern Arabian Plate - Callegari, Ivan; Scharf, Andreas; Pinto, Andre F.; Mattern, Frank; Mazumder, Rajat; Datta, Debasmita; Rarivoarison, Heninjara (Precambrian Research, 2025)
In the western Jabal Akhdar Dome of northeastern Oman and within the Neoproterozoic Huqf Supergroup, well-exposed sedimentary formations span the Cryogenian to Ediacaran periods. These rocks bear the marks of the distant Cadomian Orogeny. Among these formations, the youngest corresponds to the diverse Ediacaran Fara Formation, partly time-equivalent to the Ara Group in the subsurface of Oman. Our study extensively examined the Fara Formation’s lithologies, stratigraphy, and syndepositional deformation features to shed light on the Late Ediacaran geological evolution of eastern Arabia. Through meticulous analysis, several key findings and confirmations of previous research emerged from our investigation: (1) the Fara Formation can be categorized into three distinct members (in ascending vertical succession FA1, FA2 and FA3); (2) while FA1 and FA2 members display signs of Cadomian D1 deformation, FA3 Member does not show any evidence of D1 deformation; (3) the first description of the fossil Palaeopascichnus assigns an Ediacaran age to the entire Fara Formation; (4) the volcaniclastic rocks within the Fara Formation are geochemically similar to Hormuz’s volcanics from the same period; and (5) carbonates and siliciclastic rocks of FA1 and FA2 formed within a probably NW/SE-striking back-arc basin associated with Cadomian subduction, while FA3′s siliciclastic rocks unconformably overlie the latter members.
Keywords: Géologie -- Oman

Archaeological mission at bat/al arid (MBA mission): 2023 season (4th season) wilāyā of ibri (dhahirah governorate) - Castel, Corinne (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The project aims at enriching the debate on the nature of the settlement sites, the emergence of socio-economic complexity and the human-environment relationships in the Southern foothills region of Oman in the Early Bronze age. It is based on an extensive survey, a geoarchaeological and hydrological study in the region comprised between Al Arid and Bat (UNESCO site), and excavations at the recently discovered site of Al Arid (15 km NW of Bat). The approach is holistic and interdisciplinary and relies on specialists from the CNRS and universities, post-doctoral researchers and students. The team is composed of archaeologists, geoarchaeologists, hydrologists, biological anthropologists, geophysicist, archaeobotanist, specialists of pottery (formal typologies, physico-chemical and petrographic analyses of pastes), Geographic Information Systems and photogrammetry. After four seasons of work, we know that Al Arid was inhabited during two main phases: in the Early Bronze age and the Late Islamic period. In the Bronze age, the site appears as a regionally important centre. The discoveries are varied and sometimes exceptional: 7 towers concentrated on 25 ha, a material, local and exogen, including a superb copper alloy axe; from the beginning of the Bronze Age it seems: a copper metallurgical workshop, a canal for diverting the course of the wadi and 99 Hafit-type tombs among them two have been excavated ; dated to the Umm an-Nar period: a settlement sector (including a house that has been completely excavated), 9 tombs. These discoveries allow us to consider that communities lived there, on a recurrent, if not permanent basis, very early in history, relying on irrigation, a mastery of copper technology and exchanges with the coastal region and Mesopotamia. The mission is also heavily involved in the protection and enhancement of the region’s heritage, working alongside the Ministry of Heritage and Tourism on the Visitor Centre project of Bat.
Keywords: Archéologie -- Oman

Bologna university project in the sultanate of oman (2023): Fieldwork activities at al khutm and ras al hadd - Cattani, Maurizo; Barchiesi, Francesca; Cavazzuti, Claudio; Cocca, Enzo (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Bologna University has a long tradition of research activities in the Sultanate of Oman, with investigation in the coastal area of Sharqiyah and more recently in the project of Al Khutm tower in the area of Bat (Al Dhahirah Governorate). The fieldwork of the campaign 2022-2023 was carried out at Al Khutm investigating the outer area of the tower characterized by a monumental stone wall. The archaeological complex appears now more valuable with a unique outline of defensive and entangled structures. Several finds, including pottery, softstone and metal, are defining the starting of the construction at the end of 3rd mill. BCE. At Ras Al Hadd the Italian team is currently involved in the excavation of the early 3rd mill. BCE cemetery around the settlement of HD-6. Several clusters of cairns as part of two main cemeteries named HD-7 and HD-10 were identified in previous research. Among dozens of burial structures, the current investigation concerned the group 12 of HD-7 cemetery and three cairns were excavated. The preliminary results show the regional character of cairns with specific size, architectural features and ritual customs.
Keywords: Archéologie -- Oman

French mission “arabian seashores”: The desert project “exploring the omani rub’ al khali” (december 2022) - Charpentier, Vincent; Maiorano, Maria Pia (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The French mission “Arabian Seashores” has been exploring the Omani coast of the Arabian Sea since 2010. The team has prospected, surveyed various sites, and conducted excavations at Khuwaymah, Masirah Island, Hallaniyat Archipelago, Sharbithat, Hasik as well as other sites along the coast. Additionally, they have explored the Jebel Qara and several rock art sites. The mission’s research focuses on the chronology of the Final Paleolithic to the Early Bronze Age, spanning the period between 10,000 and 2000 BCE. Specifically, their attention is on the transition from the Paleolithic to the Neolithic era, marking the shift from predatory societies to the first productive communities. The mission has made significant discoveries, including the Final Paleolithic cave of Natif and the Neolithic sites of Ad-Dahariz (Salalah), Hasik, and Sharbithat. Simultaneously, a project in the Rub’ Al Khali desert was carried out in collaboration with a team of geologists and paleontologists. During the latest mission in December 2022, particular emphasis was placed on research in this area, confirming the extraordinary potential of these sites. The campaign played a critical role in enhancing our understanding of cultural transfer, settling patterns, and technological innovation in Southern Arabia during the Neolithic period. Overall, the project has expanded our current knowledge of Neolithic cultures in desert locations by conducting an integrated study of the paleoenvironment and a techno-quantitative examination of the lithic industries. This work lays the foundation for future research in this field.
Keywords: Archéologie -- Oman

Archaeological expedition to al khashbah (2023): Rock art survey - Döpper, Stephanie (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
In 2023, a new project on rock art in Eastern Arabia, with special focus on the Al Sharqiyah North Governorate started. It aims at recording the spatial and chronological distribution of rock art as well as its integration into the natural and anthropogenic landscape. In the first field season from February to April 2023, over 4,000 rock art images have been recorded at the sites of Al Tasawir, Lizq, Al Khashbah and Al Rakhi. This encompassed digital sketches of the rock art panels, photography of the individual rock art images, taking of UTM coordinates, and vectorising the photographs on a computer later on. In addition, 3D models of all recorded sites were generated by structure-from-motion (SfM). As a citizen science component of the project, a smartphone application (Rock Art Oman) was developed that allows everyone to support the project by documenting rock art in an easy manner. This does not only provide more data for research but also help to foster the awareness of people in Oman for their rock art heritage.
Keywords: Archéologie -- Oman

Omani-italian archaeological expedition at al tikha (2023) - Douglas, Khaled; Pizzimenti, Sara (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The Omani-Italian Archaeological Expedition at Al Tikha, a joint project between the Sultan Qaboos University and the University of Pisa started in 2022 with the aim to investigate the archaeological site of Al Tikha, strategically located in the Batinah plain, near modern city of Al Rustaq. The 2023 excavation season focused on seven distinct areas: settlements (Mound A, Mound B, Building S1, Building S2), a metallurgical site (Mound C), and the necropolis (T1, T2).
Keywords: Archéologie -- Oman

Wadi al jizzi archaeological project 2023 - Düring, Bleda S. (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
This paper presents the main results of the 2023 excavations at Site 73 / 66 in the Liwa hinterlands (northern Oman) undertaken by the WAJAP team. Excavations focused on domestic buildings dating to the Umm an-Nar and Wadi Suq period. Here, the buildings and the deposits found within them will be discussed.
Keywords: Archéologie -- Oman

Archaeological landscape and environmental dynamics of duqm and nejd (ARDUQ): Season 2 (2022-2023) - Garba, Roman; Danielisová, Alžběta F.; Rose, Jeffrey I. (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
In March 2023, an international team of archaeologists, anthropologists and geologists led by the Institute of Archaeology of the Czech Academy of Sciences in Prague successfully completed the second season of the ARDUQ (Archaeological landscape and environmental dynamics of Duqm and Nejd) expedition. Researchers from ten countries took part in fieldwork in two regions of the Sultanate. The first team, based in Duqm (south-central Oman), carried out fieldwork at Nafūn, excavating a Neolithic collective burial and documenting extensive rock art sites, both unique in south-east Arabia. Small test trenches for lithic studies were also carried out. ARDUQ’s investigations reveal a rich archaeological landscape at Duqm with long-term occupation. The second team worked in Dhofar (southern Oman). The team discovered seven Lower Palaeolithic sites in the Rub’ Al Khālī desert, with a high concentration of handaxes. Test trenches on the Nejd plateau revealed stratified Middle Palaeolithic artefacts of Nubian Complex, and samples were taken for optical stimulated luminescence dating. A systematic study of the flint raw material was also initiated. Research at Dhofar will shed new light on the early hominin and anatomically modern human dispersal Out of Africa, a topic of global importance and interest.
Keywords: Archéologie -- Oman

A diamond in the raw in oman (season 2022): Al ṣalaylī archaeological project - Gaudiello, Michela (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
After about 5-year of survey in Al Ṣalaylī valley, conducted by the Heidelberg University team, in November 2022 have started the proper archaeological excavation at the site. The documented archaeological evidence which characterized the site of Al Ṣalaylī, span from the Iron Age to the Late Islamic periods. Despite the high number of hut tombs, may be dated to the (Late?) Iron Age period, the 2022 season of archaeological excavation focused on that area of the site previously labelled “Persian Village”. The excavation confirmed that part of the site was inhabited and exploited during the Islamic period. Due the different typology of structures put in evidence in the partially excavated Trench 1, the area has been renamed as “Settlement / Workshop”. The first season of archaeological excavation was made possible thanks to the Beatrice de Cardi award funded by the Society of Antiquaries of London.
Keywords: Archéologie -- Oman

Italian archaeological research at daba al bayah (2022): Exploration and analysis of burials at the bottom of the LCG-2 tomb - Genchi, Francesco (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The stratigraphic investigations on tomb LCG-2 led to the identification of the phase of use of the tomb floor, which, on the basis of radiocarbon dating and archaeological material, seems to refer to a final phase of Iron Age III. The research of our last exploratory season focused on the continuation of the investigation of this homogeneous phase identified at the base of the corridor. The base is characterized by a clay path running through the centre of the corridor, bordered by elongated pits containing burials and objects and informing us of how the bottom of the structure was used. This contribution focuses on the description of the last burials exposed at the bottom.
Keywords: Archéologie -- Oman

Italian archaeological mission of the university of naples l’orientale in dhofar, oman (2022-2023): Archaeological research at al baleed - Giunta, Roberta; D’Andrea, Andrea (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The Italian archaeological mission of L’Orientale in the Dhofar region was established several years ago and has carried out some short surveys and two excavation campaigns (December 2021-January 2022 and December 2022-January 2023). The main objective of the mission is to continue research at the archaeological site of Al Baleed (ancient Ẓafār) –located in the Salalah area, which has been the subject of numerous archaeological investigation since the middle of the last century. The site covers more than 1.5 km × 800 m, but a large part still remains unexplored, and questions concerning its foundation, stratigraphic sequences and the materials that have been brought to light still require in-depth investigation. In order to gain a deeper knowledge of the occupation of the area in the medieval Islamic period, it is considered equally necessary to undertake research and study of the numerous burial spaces in the Salalah area. Within this context, the mission began a survey aimed at documenting the large cemeteries located in the western part of the site of Al Baleed (outside the boundary wall) and at Al Robat, two areas which, on preliminary investigation, appear to preserve the oldest funerary evidence.
Keywords: Archéologie -- Oman

Archaeological water histories of oman (ArWHO) project (2022-23): Iron age settlements and trade in yanqul wilayat - Harrower, Michael J.; Paulsen, Paige (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The ArWHO project’s 2023 season focused on the Iron Age and early Islamic Periods, specifically concentrating on mapping settlement architecture and exploring trade in softstone and copper resources in Yanqul Wilayat. The ArWHO team mapped architecture at four Iron Age sites, discovered an ancient softstone (chlorite) quarry, and tested an autonomous Ground Penetrating Radar system. Additionally, the project engaged local residents by organising a Yanqul Community Archaeology Day to share findings and promote awareness of archaeology. Our work clarifies the histories of ancient societies, their environment, architecture, and trade activities contributing to deeper understanding of the ancient past.
Keywords: Archéologie -- Oman

Khor kharfot research project (2022 & 2023): Wadi sayq, dhofar, sultanate of oman - Hauck, F. Richard (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Beginning in the spring of 2014, the Archeological Research Institute (ARI) has been involved in archaeological investigations in the Khor Kharfot Archaeological Reserve of Dhofar, Oman. A three-year excavation contract was signed with Sultan Qaboos’s advisory council in 2015. In 2022 the excavation permit was granted a five-year renewal with the Omani Ministry of Heritage and Tourism. This article summarizes the efforts of Campaigns 6 and 7 during 2022 and 2023 to expand an appreciation of Wadi Sayq’s ancient environment and its early Paleolithic through Islamic period occupations and extensive architecture. This summary of Campaigns 6 and 7 excavations contains ARI’s recent discoveries at five separate loci: site II-4 (Neolithic and Iron Age occupation site), site IV-1 (Neolithic Kharfot Mound Site), site IV-3 (Neolithic-Iron Age-Islamic Period Alcove Site), site IV-4 (Neolithic Upper Platform), and site IV-5 (Neolithic Walkway).
Keywords: Archéologie -- Oman

Sultan qaboos university project in oman (2022): Discovery of an early bronze age settlement in al ghoryeen, mudhaybi, sultanate of oman - Jahwari, Nasser Said al-; Douglas, Khaled; Hesein, Mohamad (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The Department of Archaeology at Sultan Qaboos University (SQU), in collaboration with the Ministry of Heritage and Tourism (MHT), has conducted the 3rd season (December 2022) of intensive excavations at the site of Al Ghoryeen in Wadi Andam region on the southern fringes of the eastern Hajar Mountains in the Northern Al Sharqiyah Governorate of Oman. It was excavated under the direction of Professor Nasser S. Al-Jahwari and Dr Khaled Douglas. Participants included colleagues and MA students from the Department of Archaeology at SQU (Dr Mohamad Hesein, Dr Nasser Al-Hinaei, Yaqoob Al-Rahbi, Yaqoob Al-Bahri, Al-Reem Al-Alawi, Suad Al-Harasi, Wajd Al-Zakwani, Buthainah Al-Ghofaili and Huda Al-Daihani) and the German Archaeological Instiute in Berlin (represented by Dr Kristina Pfeifer). The results of the excavation discovered the first and largest settlement in Oman dating back to the Early Bronze Age of Hafit period (ca. 3400-2700 BC).
Keywords: Archéologie -- Oman

French archaeological mission to central oman (2023): Explorations in bisya - Jean, Mathilde; Sauvage, Martin (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The French Archaeological Mission in Central Oman (FAMCO) studies the diachronic settlement of Bisya, one of the Oman peninsula’s main archaeological zones, in the Hajar mountains foothills. This region, which benefits from a location at the confluence of several wadis and local mineral resources, has been populated since the Paleolithic. It experienced a particularly prosperous development in the Early Bronze Age and the Iron Age. The first aim of the mission is to identify the development of human communities through survey and excavation. The Palaeolithic program investigates the first settlements of the Arabian Peninsula, determining the presence or absence of Neanderthal populations and their relationship to the arrival of modern Homo sapiens between the Lower and Middle Palaeolithic. The central part of the mission focuses on the Early Bronze Age to understand the beginnings of the oasis agrosystem, the domestication of the date palm, the first irrigation systems, the development of monumental domestic and funerary architecture, and the appearance of local crafts (pottery, copper metallurgy). Our research aims to provide new evidence on the role of Oman (Land of Magan in the Mesopotamian texts) within the Middle East during the Bronze Age, particularly its relations with Lower Mesopotamia (Sumerian country), Iran (the region of Fars and Makran) and the Indus Valley.
Keywords: Archéologie -- Oman

ISTIDAMA: The long-term cultural sustainability project (2022-23): Surveys and excavations in tanūf, ad-dākhilīyah governorate - Kondo, Yasuhisa (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The Long-Term Cultural Sustainability (ISTIDAMA) Project aims to identify the eco-cultural factors of sustainable lifeways and historical landscapes of the canyons and foothills of the Hajar Mountains. To this end, the project team conducted three field activities: (1) general surveys in the Tanūf district of Ad-Dākhilīyah Governorate, (2) detailed documentation of the cemeteries in the survey area, and (3) excavations at the cave site of Mughārat Al Kahf in Wadi Tanūf. Regarding the general survey, the team documented seven archaeological sites in Wadi Tanūf and six sites in As-Suwaihiriyah in the floodplain of Wadi Al Abyad at 5 km east of Tanūf. Among these, the team documented the cemetery of WTN07, 13, and 14 in detail. These cemeteries were occupied from the Wadi Suq period (ca. 2000 to 1600 BCE) and Early Iron Age (ca. 1300–650 BCE). In the cave site, the team opened a new trench next to the last season’s one to verify stratigraphy. The team also took coprolite, date stone, charcoal, and soil sample for ancient DNA, stable isotope, and radiocarbon dating analyses.
Keywords: Archéologie -- Oman

DHOMIAP project (2022-23): New archaeological discoveries in dhofar - Lischi, Silvia (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The archaeological campaign at Khor Rori made a significant contribution to the understanding of the history and culture of the region. It focused on three main objectives: to increase knowledge of the KR-N1 necropolis, to determine the chronology and function of previously discovered structures, and to understand the land use of the Dhofar Coastal Culture and the Ancient South Arabians. To achieve these objectives, exploratory investigations were carried out in three different structures to determine their chronology, cultural affiliation, and possible use. At the same time, the study of the KR-N1 necropolis continued, with particular emphasis on dolmenic cysts and multiple cist tombs. This excavation provided valuable insights into the chronology, depositional features and mortuary practices of the Dhofar Coastal Culture. In addition, we summarise here the preliminary results of the archaeological campaign at Wadi Andhūr, part of the HELFA programme under the DHOMIAP project. The campaign aimed to explore the archaeologically rich area of Wadi Andhūr. Notable discoveries include confirmation of the South Arabian origin of the site DMa0610 and an inscribed stone of South Arabian origin. Further research is needed to answer questions about the site’s chronology, use and links with other settlements.
Keywords: Archéologie -- Oman

Ichtyophagoi, their culture and economy: Survey and excavation in wadi bani khalid (WBK1, aqr zaida al athri) and tiwi - Loreto, Romolo (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Project’s activities in the Sultanate of Oman, Ash-Sharqiyah North region, are directed towards the study of the Iron Age in northern Oman, in order to investigate those historical cultures known as fish-eating communities (Ichtyophagoi) from Greco-Roman sources and locally defined as Early to Late Iron Age cultural facies. From 2014 to 2018 the project focused on the study of the seasonal coastal economy of northern Oman in the Iron Age, in particular the phases of the 1st millennium BCE, between Qurayat and Ras Al Hadd, including Bamah and Tiwi as main coastal sites. Since 2018, the joint project has extended the area of research to urban oases further inland, along the Al Hajar mountain range, to define the settlement strategies between the Iron Age and the advent of Islam. These seasonal villages were in fact part of a complex socio-economic network involving the urban and agricultural oases in the interior, located along the Al Hajar mountain range, possessing their own hunting/fishing, farming and livestock economies, acted as bridges for trade between the coasts and the more inland regions, between Oman and the Emirates for at least the entire first half of the 1st millennium BCE and from the 1st century BCE to the 4th century CE.
Keywords: Archéologie -- Oman

DExPO project (2022-23): Dolphin exploitation in prehistoric oman - Maini, Elena (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Prehistoric communities along the coasts of southeastern Arabia relied heavily on marine resources. However, dolphin remains in the zooarchaeological record remain poorly understood due to fragmentation, taphonomic changes, limited osteological collections, and the lack of a specific methodology for determination. In response to these challenges, the DExPO project aimed to develop a protocol for the analysis of osteological data from odontocetes and cetaceans from Late Neolithic and Early Bronze Age sites in central Oman. Agreements with the Ministry of Heritage and Tourism along and support from the Natural History Museum of Oman facilitated the project. Initial implementation took place in a pilot project (2019-2020) on cetaceans in the NHM collection, and has been extended to analyse archaeological remains from key sites in Ash-Sharqiyah Governorate. Ongoing objectives include developing a methodology for identifying and documenting archaeological dolphin remains and applying these methods to large osteological collections. This is central to the study of dolphin hunting and exploitation strategies, combining zooarchaeological, material culture and environmental data, using ethnographic parallels and experimental approaches. Through the DExPO project, the enigmatic relationship between prehistoric communities and marine mammals is gradually being unravelled, providing insights into their ancient coexistence along the coasts of the Arabian Sea.
Keywords: Archéologie -- Oman

First research activities at the prehistoric mountain site hayl ajah at the inner flank of al jabal al kawr - Mateiciucová, Inna; Wilding, Maximilian (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
As the first undertaking of its kind, Project SIPO has embarked in 2018 on the environmental-archaeological research of a lithic site in Oman in a true mountain ambient – Hayl Ajah (a large sediment-filled depression at 1019 m a.s.l. on an intermontane karst plateau between Al Jabal Al Kawr and Al Jabal Al Ghul; Figs 1 and 2). Because porous karstic limestone – other than more compact rocks – allows the infiltration of precipitation water into the matrix of the rock itself, our project aims to find out, whether during prehistoric periods a degree of water storage inside limestone rock-layers and aeolian surface sediments could have made good for the reduced precipitation in the northern part of Oman compared to the country’s south. Judging from the archaeological finds, the site Hayl Ajah and similar smaller sediment places in the surroundings mountains have been accessed by people during different prehistoric periods (probably since the Middle Palaeolithic, definitely during the Neolithic and Umm an-Nar period). At the present stage we encounter various kinds of small, dispersed water and sediment features in our research area that could have served mobile foragingpastoral groups while roaming the bleak mountain landscape. Indicative of this is the remarkably wide spectrum of mostly non-local raw materials used for the stone artefacts of Hayl Ajah. For some of the lithics encountered at the mountain site, yet no real analogy to lithic traditions in other parts of the Arabian Peninsula can be found. Other stone artefacts, according to first OSL/C14 dates, belong to a time period when aridization was under way (Late Neolithic). From this evidence we infer tentatively that mountainous places in Al Jabal Al Hajar have had significance for prehistoric humans during past dry periods - perhaps as the “roof section” of an environmentally diversified, yet integrated refugium in the Kawr-Akhdar Area encompassing the more open alluvial places at the mountain front (cf. Uerpmann, Uerpmann & Jasim 2000).
Keywords: Archéologie -- Oman

La trobe archaeological research in oman: The archaeology of out of africa dispersal events in oman (2019-2022) - Meredith-Williams, Matthew; Fitzpatrick, Dianne (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The debate on the timing and nature of “Out of Africa” dispersals of multiple waves of the genus Homo has been based on a limited number of securely dated sites; the majority of the Palaeolithic archaeological record for Arabia is represented by undated surface sites. This project aims to contribute to the body of knowledge and debate through targeted field survey for stratified Palaeolithic sites that can be well dated. A multidisciplinary team of geologists, geomorphologists, hydrologists, dating experts and archaeologists has been assembled to specifically target this question. Our first three survey seasons in 2019, 2020 and 2022 gave invaluable insights into the landscape setting of Oman which have fed directly into the later seasons. Preliminary results include a number of surface sites with material typologically linked to the Lower, Middle and Upper Palaeolithic of Oman, and a small number of stratified sites have been identified and are currently undergoing analysis.
Keywords: Archéologie -- Oman

Archaeological exploration of fulayj near saham in the north batinah governate (2016-23) - Priestman, Seth; Jahwari, Nasser Said al-; MacDonald, Eve; Kennet, Derek (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The Fulayj Fort Project focuses on the unique archaeological remains at the site of Fulayj: a small, regularly planned, heavily defended, stone-built fortification constructed sometime between the early 5th to mid-6th century AD during the late pre-Islamic period and its subsequently reoccupation during the first decades following the Islamic conquest of Oman in the 7th century (Figs. 1-2). The fourth season of excavation took place over a six-week period from the 10th of January to the 20th of February 2023. It involved the work of an international team with a maximum of ten participants, including specialists from the UK, Oman, Canada, Greece and the Republic of Georgia. We were pleased to host one trainee from the Ministry of Heritage and Tourism regional office of the North Batinah Governate (Fig. 3). Excavation focused on the eastern side of the fort near to the fort entranceway (Fig. 4) with work in the north-east corner extending our understanding of a series of mudbrick rooms associated with the secondary occupation of the fort in the early Islamic period. Further excavations were opened in the south-east corner, and on the fort exterior across the south-east corner tower.
Keywords: Archéologie -- Oman

Archaeological exploration of suhar port in the north batinah governate (2023) - Priestman, Seth; Jahwari, Nasser Said al-; MacDonald, Eve; Kennet, Derek (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Suhar was one of the leading ports in the Indian Ocean during the Abbasid period. With Basra and Siraf, it formed a centre of maritime power in the Gulf and Arabia. The historian and traveller Istakhri, who wrote the Kitab Al-Masalik wa Al-Mamalik, and who lived in the 10th century, tells us that Suhar was the biggest and richest town in Oman. He tells us that it is not possible to find a city more rich in buildings and foreign wares than Suhar, and that many merchants live there who trade in ships with other countries. It is known that merchants came to Suhar from China, India and many other places. It is certain that Suhar is the most important location in Oman for the history of the first centuries of Islam. Archaeological research has already been carried out in Suhar, in the 1970s and 1980s, but there is still much more to learn about this important place. In January 2023 a British and Omani archaeological team led by Seth Priestman visited the town to investigate the remaining archaeological evidence (Fig. 1). A short sur-vey of the town revealed important information about its history. New locations came to light and important new finds of imported Chinese ceramic were made. The British and Omani team is hoping to continue work at Suhar so that the full potential of this important site can be developed.
Keywords: Archéologie -- Oman

Archaeological exploration of seeb (al hail north) in the muscat governate (2022-23) - Priestman, Seth; MacDonald, Eve; Gajewska, Maria (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
"Seeb is the site of an extensive coastal settlement located in the northern suburbs of Muscat. Previous investigations by Romolo Loreto in 2013 indicate the presence of areas of deep stratigraphy, intact occupation deposits and architectural remains covering most phases of the Islamic period. More recently, documentation by the local community has highlighted the exceptional quality of the finds assemblage, with objects drawn from across the Indian Ocean world, often closely comparable to materials from other key urban centres in the region such as Suhar, Samarra or Siraf. The existence of a large urban centre on the southern Batinah remains to be better integrated into our wider historic reconstruction of the medieval topography of Oman. To address this, a three-week field-walking survey, followed by a week of finds processing, was carried out in January-February 2023. It involved mapping and surface collection to augment our understanding of the size, nature, and diachronic development of the medieval settlement. The work was conceived in partnership with the local community, taking the factor of existing interest as the motivating driver in the plan and design of future research. Public workshops, social media and continuing conversations with residents and other stakeholders form important channels in the pursuit of the project."
Keywords: Archéologie -- Oman

Sapienza university of rome archaeological mission in the arabian peninsula and the gulf area (MASPAG): Archaeological explorations in wadi al ma’awel 2022-23 - Ramazzotti, Marco (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Sapienza Archaeological Mission in the Arabian Peninsula and the Gulf Area (MASPAG) surveys in the Omani southern Batinah, southwest of Muscat, near the Muslimat oasis, has recently revealed a new hitherto unknown multi-millennial archaeological landscape crossed by the Tropic of Cancer. In this vast area, two enormous cemeteries with hundreds of collective tombs have been identified. The oldest graves typologically and morphologically date from the end of the 4th millennium, but both the cemeteries appear to be associated with long-lasting settlements continuously inhabited up to the Islamic period. The two cemeteries next to a settlement that was fortified in the Iron Age offer the possibility of investigating the social complexity of those mobile groups interposed between south-eastern Arabia and the Persian Gulf on a broad spectrum. Powerful coalitions capable of governing large portions of the piedmont territory interposed between the rocky Hajar mountains and the spectacular western coasts of the Arabian Sea, a nomadic and half-nomadic territorial state in the south-eastern frontier of the ancient Near East which Mesopotamian texts identify as the Land of Magan.
Keywords: Archéologie -- Oman

Archaeological expedition to al khashbah (2023): UmWeltWandel, paleoenvironmental studies - Schmidt, Conrad; Beuzen-Waller, Tara; Schmitt, Katharina; Reinhardt, Antonia; Proctor, Lucas (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The final field season of paleoenvironmental studies for the UmWeltWandel project lasted from 7 January–17 April 2023. It resulted in the collection of further samples of sediment, rock, charcoal, snail, plant, pollen, and water for laboratory analysis in Germany. More than 70 sedimentological sections were investigated in the vicinity of Al Khashbah to study soil and landscape formation processes. Once completed, these studies will provide important insights into climate and vegetation of the Neolithic and Bronze Age in Central Oman.
Keywords: Archéologie -- Oman

Archaeological expedition to al khashbah (2023): Ibra south - Schmidt, Conrad; Kluge, Jonas; Biezeveld, Irini (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
A small, newly discovered Umm an-Nar settlement close to the southern outskirts of the modern city of Ibra was investigated by a team from the University of Frankfurt, Germany between 1 March 2023 and 11 April 2023. The investigation included a detailed surface survey with find collection, as well as small-scale excavations at two of the buildings. The results of the first campaign suggest a well-planned settlement structure with specialized areas for the production or refinement of copper and copper objects. Of particular importance was the discovery of multiple plano-convex copper ingots during the excavations of one of the domestic buildings.
Keywords: Archéologie -- Oman

Archaeological expedition to al khashbah (2023): Al khashbah KHS-a - Schmidt, Conrad; Maiorano, Maria Pia; Proctor, Lucas (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Several locations north of the village of Al Khashbah have yielded Neolithic remains, most likely due to the area’s accessible chert outcrops and elevated fluvial terrace systems overlooking wadi floodplains. KHS-A, the main Neolithic site in the area, is distinguished by extensive flint scatters, isolated stone constructions, and fireplaces. In 2022, the team excavated a preliminary test trench (KHS-A.1) that yielded a high number of lithics and charcoal samples. Radiocarbon dating placed the age of the complex within the Late Neolithic Period. In 2023, further excavations at KHS-A.13 were undertaken with the goal of confirming the age dating of the site and expanding our understanding of the extent and occupational sequence of the KHS-A complex. The trench consisted of a 3 × 4 m exposure revealing multiple fireplaces, ash pits, and post holes. The investigation of the Neolithic occupations at Al Khashbah seeks to open new routes and further perspectives in the study of Early and Middle Holocene in the broad area between the mountains and the Rub Al Khali desert.
Keywords: Archéologie -- Oman

Archaeological investigations on the necropolis of khor jarama: Campaign 2021-2022 - Sévin Allouet, Christophe (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Archaeological campaigns led during these last five years on the necropolis of Khor Jarama, located in the Ja’alan area, has brought to light what is probably a new prehistoric culture unknown in Oman. Indeed, the excavation of seven tombs located not far from the Jarama lagoon has enabled the discovery of the first funerary monuments known to date in Oman. These latter have been dated from the middle of the 4th millennium BCE for the oldest ones, that is to say several centuries before the monumental tombs of Hafit period. These tombs are characterized by new architectures as well as by new funerary practices observed in Oman. This discovery fills a void of data observed until now in Oman and located between 3600 and 3200 BCE, that is to say the period of transition between the end of the Neolithic and the beginning of the Hafit period. This discovery highly changes the vision that we had about the first prehistoric societies in Oman: there is probably here, very early at the end of the Neolithic, structured groups, probably hierarchized, and led by members buried in monumental tombs. A new campaign of survey in the Ja’alan area has allowed the discovery of eight others necropolis showing the same architectural characteristics than tombs of Jarama, and thus belonging probably to this period. Current investigations on these necropolis could come to confirm the identification of a new prehistoric period in Oman.
Keywords: Archéologie -- Oman

Bat archaeological project (2022-2023): Beyond the bat oasis - Swerida, Jennifer; Dollarhide, Eli; Jensen, Reilly; Bryant, Robert (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The Bat Archaeological Project conducted its winter field season from December 26, 2022 until March 5, 2023. Our research focused on different areas of the Bat area’s Bronze Age archaeological landscape, including Rakhat Al Madrh, the Khutm Settlement, and the proposed location of the new Bat Visitors Center. At Rakhat Al Madrh, the team excavated three Umm an-Nar period houses. With assistance from a team of geomorphologists and geologists from the Sorbonne University, we also discovered that the houses were located around an ancient marsh/wetland where Umm an-Nar people likely experimented with early agriculture and pastured livestock. This ancient settlement is unlike any other known Early Bronze Age village or town in Arabia because of this environment. At Al Khutm, the team discovered and excavated Umm an-Nar houses and tombs and digitally mapped a very large fortress at the site dating to the Iron Age II. At the proposed location for the new Bat Visitors Center, we excavated and surveyed several mounds, which appear to be tombs that continue from the necropolis across the wadi. With the generous permission of the Ministry of Heritage and Tourism, laboratory analyses on geological, C-14, botanical, and ceramic samples collected this season are currently underway.
Keywords: Archéologie -- Oman

Terraced landscapes of the jabal akhdar (2022-23): Fieldwork at shuraijah and wadi bani habib - Turner, Sam; Zerboni, Andrea; Kinnaird, Tim; Kindi, Mohammed al-; Sevara, Christopher; Brandolini, Filippo; Pezzotta, Andrea (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Agricultural terraces are prominent features in landscapes across the world. Terraces enable the cultivation of steep land for crops including cereals, fruit, vegetables, flowers and trees, and can be irrigated where careful water management is required. They allow the redistribution of sediment to create soils with improved root penetration and water retention. Terraces are highly variable, their regional development reflecting a combination of natural factors (differing geologies, geomorphology, hydrological conditions) and landscape histories (manuring, field management, crop selection, water availability). The histories of terraced landscapes remain poorly understood, including in Oman. Little is known about when they were constructed, and how they were used and developed across different periods and environments. A key reason for this lack of knowledge is that terraces have proven exceptionally difficult to date using conventional or scientific archaeological methods. This research project uses a new method developed by the research team to date terraces in Oman for the first time and use geoarchaeological methods to investigate how they were used in the past. In March 2023, targeted fieldwork in two villages of Jabal Akhdar (Ash Shuraijah and Wadi Bani Habib) allowed collection of sediment samples for dating and geoarchaeological analysis.
Keywords: Archéologie -- Oman

Joint heidelberg university/ministry of heritage and tourism project (2023): Archaeological rescue operation at al khod, ḥūr ad-dabʿ, muscat - Yule, Paul A. (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
In September 2018 the population of the capital area reached 1.4 million. Places such as Al Khod need room for growth. The development of this area during the past 20 years includes the building of the Nizwa road, highway 15, to its north-east Lulu Al Bandar super market and flanking to its west a large housing settlement. There, pre-Islamic hut tombs are scattered over the three low mountains (600m x 300m area). The Ministry of Defence plan to develop the mountains (Fig. 2) as a recreational facility – the ‘Heritage Hill’ project. This report sketches the mapping and excavation (12.01. to 26.01.2023) and documents 140 burial structures, the excavated finds, the clearance of stone from the tomb cluster on the southern mountain, figures of the 3D and drawings of the tomb images. This site, with its hut tombs and niche graves is important to solve the problem of the dating and nomenclature of prehistoric funerary architecture. The author searches for an alternative to the nomenclature ‘cairn’ which describes not the original architecture, but rather an undifferentiated, dishevelled state of preservation.
Keywords: Archéologie -- Oman

The salut and bisya archaeological mission (2022): The rock art landscape and its threatening - Zerboni, Andrea; Degli Esposti, Michele; Pezzotta, Andrea; Marinoni, Alessia; Gallinaro, Marina (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The geoarchaeological investigation around the Bisya and Salut Archaeological Park disclosed the complexity of local archaeological landscape dating to the last millennia of the Holocene and the main steps in developing sophisticated systems for land exploitation. Recent fieldwork focused on the importance of rock art in the region, which needs to be systematically surveyed and documented. Rock art sites feature various representations dating from the second millennium BCE onwards and the research carried out in 2022 aimed to assess its archaeological potential, as well as identify any threats to its preservation. The investigation confirms that local rock art is a valuable asset for Oman’s archaeology and potential tourism. It suggests the development of geo-cultural tourism routes that combine archaeological sites and rock art with the natural landscapes. Nonetheless, the preservation of rock art and the issues threatening it need careful consideration and assessment for future planning.
Keywords: Archéologie -- Oman

الألبسة في طرابلس وبرقة وفزان خلال القرون 5-11م/1-5هـ (مقاربة تاريخية حول التأثيرات المحلية والخارجية) - وريث, أسامة عبد الحميد (مجلة كلية الآداب, 2025)
تُركز هذه الدراسة على رصد طبيعة وأنماط الملابس في ليبيا خلال القرون الألبسة في طرابلس وبرقة وفزان خلال القرون 5-11م/1-5هـ، وهو موضوع أهتم من خلاله بتوثيق التطور التاريخي لمراحل وأشكال الملابس المحلية، كالعباءات الرجالية والأردية النسائية والسراويل والطاقيات والصنادل. ومن الجيد رصد نوعية الملابس التي ارتداها سكان البلاد الليبية، إذ يُساعد هذا المنهج التسلسلي على تحديد التحولات التي طرأت على الملابس الليبية مع مرور الزمن. وتسعى الدراسة البحثية إلى التحقق من ماهية قطع الملابس المعنية بناءً على شهادات المصادر النصية أو الأدلة الأثرية، مع التمييز ما بين الملابس المنتجة محلياً وتلك المتأثرة منها بالثقافات الخارجية. خصوصاً وأن الملابس الطرابلسية الفاخرة بدأت بعد الإسلام تكتسب شهرة، وبعضها يأتي من جبل نفوسه، كما برزت منسوجات برقة الصوفية عالية الجودة، المنسوجة من صوف سلالة الخِراف البرقاوية الممتازة. This study focuses on documenting the nature and patterns of clothing in Libya between the 5th and 11th centuries CE (5th century AH). The research aims to trace the historical development of local garments, such as men’s cloaks, women’s robes, trousers, caps, and sandals. Examining the types of clothing worn by Libyans during this period is valuable, as this sequential approach helps identify transformations in Libyan attire over time. The study seeks to determine the characteristics of these garments based on textual sources and archaeological evidence, distinguishing between locally produced clothing and those influenced by external cultures. Notably, luxurious Tripolitanian garments gained prominence after the advent of Islam, some of which originated in the Nafusa Mountains. Additionally, high-quality woolen textiles from Barqa, woven from the fine wool of Barqawi sheep, became widely recognized.
Keywords: Artisanat -- Tripoli

Hégémonie, esclavage et modélisation des discours de domination sous les premiers empires au Proche-Orient médiéval - Trabelsi, Salah (Esclavages & Post-esclavages. Slaveries & Post-Slaveries, 2025)
Les victoires remportées par les Arabes sur les deux grands Empires perse et byzantin se sont soldées par l’annexion d’immenses territoires. Ces conquêtes soudaines et fulgurantes ont bouleversé les équilibres sociaux et institutionnels des vieilles cités de la péninsule Arabique. Un des effets inhérents à la conquête est la montée en puissance d’une oligarchie militaire arabe qui, aidée par ses affidés parmi les notables des pays vaincus, confisqua à son profit les biens et les terres, ceci entraînant une brusque recrudescence des violences et des exactions. Dans ce contexte, les populations colonisées furent souvent réduites à l’état de bêtes brutes, dénuées de sensibilité humaine. En plus du mépris et des catégorisations raciales, elles furent frappées d’exclusion en vertu d’une politique d’oppression et de spoliations massives et systématiques.Ces transformations profondes apparurent dès la deuxième moitié du viie siècle. Une de leurs conséquences décisives est la naissance d’un puissant empire édifié par les califes omeyyades. Descendant des notables affiliés au clan mecquois des ʿAbd S̲h̲ams, ces dynastes régnèrent à Damas entre 661 et 750 apr. J.-C. Après leur chute, ce fut au tour de leurs rivaux, les Abbassides, d’imposer leur domination depuis Bagdad sur des peuples et des territoires répartis sur des côtes aussi diverses que celles de la mer d’Arabie, du golfe Persique, de la mer Rouge, de la Méditerranée et des deux océans Atlantique et Indien.Cet article entend fournir une analyse historique et critique des rapports sociaux, économiques et culturels au Proche-Orient médiéval, à une époque marquée par la naissance et l’apogée des deux premiers empires coloniaux arabes. L’un de ses principaux enjeux est de sortir d’une histoire édifiante pour retrouver une approche méthodique, permettant de comprendre les mouvements profonds d’une si longue histoire. Il s’agit d’une démarche qui privilégie une relecture serrée des sources de première main et fait attention aux sens précis des mots et à la valeur informative des témoignages. Ces renseignements proviennent des documents de chancellerie, des dīwān ou bureaux des secrétaires royaux, des livres des impôts (Kharādj), des traités médicaux, des sources géographiques et littéraires, des annales historiques, etc. Ces corpus dont nous disposons sont sans doute assez réduits, incomplets et souvent laudatifs. Ils tendent généralement à édulcorer les réalités qu’ils décrivent. Il arrive néanmoins d’y trouver des indications significatives permettant de reconstituer la trame du réel. Ces données sont sans doute loin d’être sans défauts. Elles nous aident cependant à mieux cerner les faits pour les replacer dans l’infinie variété du réel tout en élargissant les champs d’investigation au sujet des discours sur l’altérité, de l’évolution des mentalités, de l’entrée en jeu des préjugés de couleur, des hiérarchies sociales et des identités biologiques et culturelles.
Keywords: Ibn Kaydad

Treatises on the Islamic firaq (Sects) and the Origin of Islamic kalām: Early Kufa-Baghdad Literature - Salimi, Abdulrahman al- (Studia Islamica, 2025)
Abstract This study examines two late 2nd/8th century books that have been edited and published recently: Abū Muḥammad ʿAbd Allāh b. Yazīd al-Fazārī (d. c.185/800)’s Kitāb al-Rudūd (The Book of Responses) and Ḍirār b. ʿAmr al-Ġaṭāfānī’s (d. c.200/810) Kitāb al-Taḥrīš (The Book of Provocation). Both texts shed light on the emergence of ʿilm al-kalām (scholastic theology) in early Islam and its relationship to books and treatises on the Islamic firaq (sects) – a relationship which until now has not been sufficiently examined. In comparing these two texts, we focus on the specific topics they share, the methodologies they use, and the technical terms they employ. We conclude that the emergence of ʿilm al-kalām, as well as the Islamic “contemplative disciplines” in general, occurred not primarily, as is often surmised, as a result of external Greek philosophical influence but rather as the result of a politico-theological debate that took place within Muslim communities. We also reconsider the nature of intellectual life during the early Abbasid period.
Keywords: Fazārī, ʿAbd Allāh ibn Yazīd al-; Foi -- Traité -- 8e siècle; Ġaṭāfānī, Ḍirār b. ʿAmr al-

Miranda Morris, Ethnographic Texts in the Baṭḥari Language of Oman - Rubin, Aaron D. (Journal of Semitic Studies, 2025)
Keywords: Linguistique -- Oman; Recension

Résistance et Dévotion. Anciens sanctuaires ibadites de Djerba - Chekhab-Abudaya, Mounia (Bulletin critique des Annales islamologiques, 2025)
Résistance et Dévotion : Anciens sanctuaires ibadites de Djerba, publié par Virginie Prevost, est le fruit d’un long travail commencé en 1996 et enrichi, depuis 2009, des clichés du photographe Axel Derriks. Cet ouvrage se présente comme une étude historique et architecturale minutieuse portant sur quarante-huit mosquées de l’île de Djerba, avec pour dessein de « conserver la mémoire des anciens lieux de culte de Djerba » (p. ix). Tout au long du volume, V. Prevost souligne de manière pertine...
Keywords: Architecture -- Djerba; Recension

Min Trībūlītānyā ilā Aṭrābulus : al-mashhad al-taʻmīrī khilāl al-ʻaṣr al-wasīṭ al-mutaqaddam bayn al-tawāṣul wa-l-taḥawwalāt من تريبوليتانيا إلى أطرابلس المشهد التعميري خلال العصر الوسيط المتقدّم بين التواصل والتحوّلات - Prevost, Virginie (Bulletin critique des Annales islamologiques, 2025)
Voici la première monographie publiée par le chercheur tunisien Hafed Abdouli, tirée en partie de sa thèse de doctorat consacrée à la Tripolitaine médiévale, défendue à Tunis en 2011 sous la direction de Faouzi Mahfoudh. L’ouvrage, préfacé par Ahmed M’Charek, constitue le premier volume d’une nouvelle collection des éditions Brill, Libya Islamica, et s’inscrit dans un intéressant programme de recherches dirigé par Aurélien Montel et Sébastien Garnier, Libmed, qui propose, sous la forme d’un s...
Keywords: Recension

Cultivating the Past, Living the Modern: The Politics of Time in the Sultanate of Oman: Amal Sachedina - Chatty, Dawn (Journal of Arabian Studies, 2025)
Keywords: Recension

Privacy and Gendered Domestic Spaces in the 21st Century: Mapping Sociocultural Continuity in the Community led-housing Project of Ksar Tafilelt, Algeria - Messabih, Hadjer; Wulff, Federico (ARCHive-SR, 2025)
As a sociocultural product, the home is shaped by specific sociocultural norms and values. Economic development and modernisation have significantly affected the architecture of many Muslim homes, resulting in a disconnection from Islamic culture. This paper explores two sociocultural factors in Muslim housing: privacy and gender segregation. The analysis highlights how the principles of traditional Islamic architecture are still woven into contemporary designs, using Ksar Tafilelt in Algeria as a case study. The aim of this paper is to demonstrate that the Mozabite house in Ksar Tafilelt continues to uphold the social customs and religious beliefs of its residents despite the influences of modernisation. Through fieldwork and comparative analysis, both the traditional house in the original Mozabite settlement and the contemporary house in Ksar Tafilelt are examined in terms of user zones rather than functional zones. This approach investigates how these homes uphold traditional Mozabite architectural patterns while accommodating contemporary comfort needs. The study methodology also includes a combination of questionnaires and interviews conducted with a sample of 70 residents from Ksar Tafilelt. The findings reveal factors that have enabled the Mozabite community to maintain its Islamic identity. They also emphasise a notably conservative, family-oriented culture, which is reflected in the organisation of household spaces. This research study highlights the significance of involving the community in housing projects and comprehending the sociocultural principles of the local population throughout the construction process.
Keywords: Architecture -- Mzab

العمل التطوعي في مؤسسة العشيرة دراسة استطلاعية - إباض, بهون علي; مختار, يمينة (مجلة آفاق علمیة, 2025)
ملخص باللغة العربية: يسعى الباحثان من خلال هذه الدراسة إلى اكتشاف ظاهرة العمل التطوعي في مؤسسة العشيرة داخل مجتمع بني مزاب، حيث تم اعتماد المنهج الوصفي كونه الملائم لهذا النوع من الدراسات والتي تعد الأولى من نوعها حسب اطلاع الباحثين، وذلك بغرض جمع أكبر قدر من المعلومات الوصفية وقد وزع الباحثان استمارة الكترونية على عينة قصدية بطريقة كرة الثلج، حيث بلغ مجموعها 278 استمارة، وقد ركز الباحثان على أهم المهارات المكتسبة للعمل التطوعي وكذا معرفة المعيقات ومنه الخلوص إلى بلورة اقتراحات عملية تساعد على فعالية العمل التطوع داخل مؤسسة العشيرة تحديداً، وقد توصلت الدراسة إلى مجموعة نتائج أهمها؛ ضعف مشاركة المرأة في مؤسسة العشيرة، والدافع الرئيس من الإقبال على العمل التطوعي هو ابتغاء الأجر العظيم؛ مما يشجع على استمرارية العطاء رغم وجود بعض المعيقات المتعلقة بنقص التكوين ونقص السيولة المالية. Abstract: The researchers aimed at exploring the voluntary work phenomenon in Al-Ashira institution in M’zab valley. As this study is unprecedented, the descriptive method was used, so a huge data were collected with an electronic questionnaire administrated to 278 individuals sampled through snowballing style. We focused on dimensions related to voluntary work acquired skills, and obstacles encountered by them. The findings showed low participation of females in Al-Ashira institution, and the primary motive to participate in voluntary work is to obtain a great reward from Allah, which wields power to Al-Ashira members to be persistent though obstacles pertaining to low formation, and low funds.
Keywords: Vie sociale -- Mzab

The Position of Ilm al-Rijal in the Ibadi Sect - Shamkhi, Mina; Masoudian, Aref (Studies on Understanding Hadith, 2025)
The issue of hadith purification and the preservation of the Prophetic tradition in the Ibadi sect has led to the development of the science of Rijāl as one of the fundamental pillars of hadith studies in this sect. Given the widespread fabrication of hadiths throughout various historical periods, examining the principles and criteria of this discipline is essential for assessing narrations. This study aims to explain and analyze the foundations of Ibadi Rijāl studies and compare them with those of other sects, namely Shia and Sunni, using a descriptive-analytical method. In its initial stages, by reviewing the history of Rijāl science and its sources, including the Musnad Rabi‘ ibn Ḥabīb and the Mudawwanah of Abū Ghānim al-Khurāsānī, the research demonstrates how the Ibadis, unlike other schools that primarily rely on Sunni or Shia sources, have managed to establish an independent identity in hadith scholarship. This article explores the various dimensions of Ibadi Rijāl studies and explains its influence on the sect's religious identity. By examining criteria such as integrity, precision, Islam, maturity, intellect, moral uprightness, consistency of practice with narration, verification of the primary narrator, avoidance of tadlīs (concealment of defects in narration), and endorsement of narrations by scholars, the study highlights the distinctive features of the Ibadi Rijāl system. Additionally, the necessity of referring to Sunni sources for evaluating hadiths, particularly due to the lack of independent Ibadi works on jarḥ wa ta‘dīl (criticism and authentication of narrators), underscores key differences between this sect and others.
Keywords: Hadith -- Ibadisme

“Berbers,” “Khārijites” and “Knowledge Bearers”: How the Ibāḍīs Shaped a Regional Counter-Memory in North Africa - Aillet, Cyrille (Arabica, 2025)
Les soulèvements qui, vers le milieu du viiie siècle, détachèrent une part importante du Maghreb de la tutelle orientale, représentèrent un défi significatif pour le jeune Empire abbasside. Que s’était-il passé ? Dans leur tentative d’explication de la situation en Occident, la plupart des sources mirent en avant l’opposition entre les conquérants et les « Berbères » autochtones, dépeints comme un peuple non civilisé, insoumis et rallié au courant des rebelles « Khārijites ». Dans les régions où l’ibadisme s’était répandu, une contre-mémoire ne tarda toutefois pas à émerger. Les Ibāḍites inventèrent leur propre récit du passé, en célébrant l’Occident comme un nouveau berceau religieux et les Berbères comme un nouveau peuple élu, dont la conversion à l’islam était vue comme un choix volontaire. Cet article compare le récit le plus courant sur l’Afrique du Nord avec la version ibāḍite tout en essayant d’évaluer comment ces deux faisceaux narratifs interagissaient.
Keywords: Kharijisme

الإمام أبو سعيد الكدمي ودوره في نشأة المدرسة النزوانية وتطورها: (Imam Abū Saʿīd al-Kudāmī and his Role in the Emergence and Development of the Nizwa School of Thought) - الكندي, أحمد بن يحيى بن أحمد; الصوافي, سعيد بن راشد; المنصوري, المبروك الشيباني; الكندي, ماجد بن محمد; الريامي, علي بن سعيد بن سالم (التجديد - مجلة فكرية محكمة, 2025)
هدفت هذه الدراسة إلى إبراز دور الإمام أبي سعيد الكدمي في نشأة المدرسة النزوانية، وزعامته العلمية والفكرية لهذه المدرسة، والتعريف بالمدرسة النزوانية وأهم تطوّراتها التاريخيّة ودورها في تكوين الطبقة الفكريّة والسّياسيّة المتخصصة في عصرها. وسعت الدراسة إلى إبراز قيمة هذه المدرسة الفكرية المتميّزة، وقد اعتمدت الدراسة على مناهج كالاستقرائي في استقراء مختلف جوانب نشأة المدرسة النزوانية وأهم تطوّراتها التاريخيّة، والوصفي التحليلي لبيان دور المدرسة النزوانية وإسهاماتها في الفكر الإسلامي. وخلصت الدراسة إلى نتائج منها ارتباط ظهور المدرسة النزوانية بمنهج توسط في تعامله مع المختلفين في قضية عزل الإمام الصلت بن مالك الخروصي (272هـ/ 885م)، وقد تبنت المدرسة النزوانية آراء معتدلة في قضية العزل وفي أحكام الولاية والبراءة مع المختلفين فيها .الكلمات المفتاحية: المدارس الفكرية العمانية، أبو سعيد الكدمي، المدرسة النزوانية.

أبو غانم بشر بن غانم الخراساني (ت: 205هـ) ومنهجة في "المدونة": دراسة تحليلية - الهادي, سيف بن سالم (التجديد - مجلة فكرية محكمة, 2025)
قدم البحث شخصية علمية من خراسان، اشتغلت على الخلاف العالي، وآمنت بالتعددية الفكرية، وانتقلت كما انتقل غيرها من علماء خرسان إلى حواضر العالم الإسلامي، في العراق والجزيرة العربية؛ من أجل الإسهام في الإنتاج العلمي. كان أبو غانم الخراساني حريصًا على تدوين فقه المدرسة الإباضية، والمقارنة بين آراء تلاميذ أبي عبيدة مسلم بن أبي كريمة على مستوى الخلاف داخل المدرسة وخارجها، فقدم كتابًا رائعًا أسماه: "المدونة"، وهو أول سِفْرٌ إباضيٌّ في الخلاف العالي، سُمِّي لاحقا بالمدونة الصغرى، التي هي في مقابل المدونة الكبرى، التي تعرضت للإضافة من قبل علماء الإباضية اللاحقين. يُعَدُّ البحث عن مثل هذه الشخصيات المغمورة لدى المدراس الأخرى مهم جدًّا، إذ يمنح الباحثين فرصة للاطلاع على النتاج العلمي المبكر في المدراس الإسلامية، كما يعالج الكثير من الأحكام المبنية على الاستقراءات الناقصة عند الحديث عن المدراس المخالفة، ولقلة الكتابة عن أبي غانم؛ كان هذا البحث إسهامًا ضروريًّا في المجلات المحكمة؛ نظرًا لقربها المباشر من الباحثين. تضمَّن البحثُ الحديثَ عن شخصية أبي غانم، وقدراته العلمية، وتميزه الأخلاقي، وفيه أيضًا حديثٌ عن المذهب الإباضي؛ نشأته، ومعالمه الفقهية، والسياسية، وعلاقته بمذاهب أهل السنة، وفيه أثبت الباحث تميُّز المذهب بالاجتهاد المطلق، وبراءته من الانتساب للخوارج؛ فقهًا وسياسةً. الكلمات المفتاحية: أبوغانم، أبو عبيد، الإباضية، المدونة، الفقه المقارن.
Keywords: Fiqh -- Commentaires

Les (échelles de) proximité(s) d’un snack cacher du souk de Djerba - Morvan, Yoann (Géoproximités, 2025)
Keywords: Judaïsme -- Djerba

علاقة عُمان بباشوية مصر في عهد السيد سعيد بن سلطان 1804-1832م - القطيطي, منال بنت حمد (المجلة العربية للآداب والدراسات الإنسانية, 2025)
Keywords: Relations -- Oman -- Egypte; Vie politique -- Oman -- 1804-1856

A Tale of Two Cultures: Comparative study of “Iɣed n Tinnurt” from Infusen and “Aschenputtel” from Germany - Buzakhar, Mazigh (Tamazgha Studies Journal, 2025)
Keywords: Littérature -- Djebel Nefousa

Engineering Thoughts Embedded in Ancient Groundwater Techniques: The Case of Falaj in Oman - Mohtashami, Ali; Ghafri, Abdullah Saif al-; Labbaf Khaneiki, Majid (Iranian Journal of Science and Technology, Transactions of Civil Engineering, 2025)
This study aims to examine the engineering design of the falaj system using a wide variety of published documents on its construction and maintenance. A falaj is a hand-dug tunnel that transfers groundwater from aquifers to lower-lying lands. Falaj masters, despite the fact that they are usually illiterate, employ embedded mathematics to calculate the height difference between two points, excavate tunnels, measure tunnel gradient and depth, and locate groundwater infiltration area. Their traditional knowledge is awash with a great deal of mathematical methods, which has turned falaj into a feat of engineering. These methods are primarily based on principles such as proportion, right triangles, similarity of triangles, the intercept theorem, unit conversion, fractions, algebraic equations, and the four basic operations. This study concludes that the technical complexity of falaj system in terms of engineering, is the result of some simple yet effective mathematical calculations that form the core of falaj indigenous knowledge and aflaj masters perceive such equations intuitionally.
Keywords: Irrigation -- Oman

Al-ʿAwtabī’s Kitāb al-Ansāb: Challenges in Attribution and Composition - Nābūda, Ḥasan Muḥammad al- (Der Islam, 2025)
The Kitāb al-Ansāb (The Book of Genealogies) provides detailed accounts of the lineages and familial connections of Omani tribes in southeast Arabia, which is essential for understanding the social and political structure of the region during the premodern period. This book became an indispensable resource for historians seeking to write a comprehensive history of premodern Oman, as it was frequently quoted by later Omani historians and formed the foundation of premodern Omani cultural and religious practices. Compiled during the 4th/11th century, the identity of its writer has attracted much speculation. While widely attributed to an individual from the ʿAwtabī family, this attribution does not withstand scrutiny. This paper critically examines the author of the Kitāb al-Ansāb , his style and method, sectarian and factional affiliations, and attempts to place the text in its historical context. It argues that the author was most likely a nonsectarian moderate from the cosmopolitan city of Ṣuḥār, a coastal city in northern Oman, and completed the text in the year 345/956 or earlier. The confused and fragmentary condition of the text today is likely the result of subsequent copyists, with the oldest known manuscript dated 1086/1672. The paper concludes with a discussion of the extant manuscripts and a call for a critical edition.
Keywords: Sources -- Oman

Jewish Communities in French North Africa: Comparing Strategies and Outcomes - Petrucci, Filippo; Soi, Isabella (The Maghreb Review, 2025)
The article describes Jewish communities’ stances in relation to Zionist movements in France and in territories administered by France that were primarily populated by Muslims. It considers the actions of North Africa Jews in the Zionist movement, particularly during the Second World War, and how the war influenced Zionism. The Jewish communities in Algeria, Morocco, and Tunisia had different statuses influenced by and mirrored in the various colonial administrations, local authorities, and populations. Besides, those differences related to their degree of involvement with Zionism, which was anything but homogeneous and ranged from strong support to a lack of interest. Based on material collected from various archives (mainly Yad Vashem and the Central Zionist Archives), the article uses a selection of testimonies that describe the diversity of North African Jewish communities and their different levels of engagement with Zionist activities. In this way, the stories of these actors and witnesses will directly reveal the heterogeneous worlds of Judaism and Zionism in North Africa. The article also confirms the diversity of the French Empire despite the shared concept of assimilation and the impact of the colonial administration, that was organized in different ways depending on the local situation and on social relations in North African societies.
Keywords: Judaïsme -- Djerba

Urbanization and its Impact on Land Use and Land Cover in Al Buraimi City, Oman Using Remote Sensing and GIS - Ansari, Tauseef Ahmad Ahmad; Singh, Chandan Kumar; Albawwab, Wael (Journal of Landscape Ecology, 2025)
Rapid urbanization poses significant challenges that can transform the physical and socio-economic environment of a city. Oman, a coastal country, has experienced a rapid increase in urbanization over the past decades. As statistical data show, the population increased significantly from 1955 to 2023, ranging from 2.5 % to 88 %. Similarly, the population in Al Buraimi Governorate has doubled since 1993, with an estimated population of 121,802 (NCSI, 2021) Al Buraimi City facing significant challenges. The city’s rapid growth in population burdening its infrastructure, traffic, municipal, education and public health capacity. This paper investigates the transformation of Land Use (LU) / Land Cover (LC) change from 2003 to 2023 in relation to population growth, employing both spatial and non-spatial methods to analyze the urban sprawl. The study focuses on the four main objectives: 1. To identify distinct types of sprawls (e.g., continuous, leapfrog, ribbon) and their spatial distribution proximity areas. 2. To examine the factors driving urban sprawl, including population growth, industrial development, socio-economic and educational opportunities. 3. To assess LU/LC changes over the study period using geospatial methods. 4. To forecast urban sprawl pattern using statistical models, providing insights into potential future developments. Given the limited understanding of urban sprawl in the study area, this research aims to address the complex challenges of urbanization and recommends sustainable resource development strategies. The results show that between 2003 to 2023, built-up areas increase from 13.14 % to 14.88 %, roads and other areas from 9.92 % to 11.23 % and vegetation cover decline from 3.93 % to 3.37%. Population, road and built-up area densities show significant increase. The population density rose from 27.72 % to 44.12 %, road density surged from 13.86 % to 47.04 %, built-up area density grew from 25.68 % to 41.92 %. Depending on the forecast results of urban sprawl, the low sprawl (45 %-55 %) with higher density and less probability, medium sprawl (55 %-65 %) with moderate expansion probability, high sprawl (65 %-75 %) with increased probability of expansion and very high sprawl (> 75 %) with lower density, high probability of expansion. The areas with a high population, road or built-up area density are less likely to sprawl in the city of Al Burami. Additionally, three sprawl patterns, continuous, leapfrog and ribbon pattern in the study area were identified, helping in further solutions to urbanization.
Keywords: Urbanisme -- Oman

الشيخ سليمان اللمكي... دوره الريادي في الحياة السياسية والاجتماعية في عمان وشرق أفريقيا - الحضرمي, أحمد بن سعيد; الحضرمي, مسعود بن سعيد (مجلة الحكمة للدراسات الاعلامية و الاتصالية, 2025)
Keywords: Journalisme -- Oman

النمو الحضري بمدينة مدنين (الجنوب الشرقي التونسي) - ضيف الله, الطاهر (Revue des Études Multidisciplinaires en Sciences Économiques et Sociales, 2025)
تشهد مدينة مدنين بالجنوب الشرقي التونسي منذ ترقيتها الى مركز ولاية سنة 1956 تحولات مهمة، تمثلت  في نمو ديمغرافي سريع، وتوسع مجالي، وتدعم في انشطتها الاقتصادية خاصة على مستوع قطاعي الصناعة و الخدمات العمومية، وتدعم نشاط التجارة الموازية منذ سنة 1988 مما ساهم في توسيع نفوذها وتنويع علاقاتها. يتناول هذا العمل دارسة مكونات الدينامية الحضرية بمدينة مدنين وعواملها بتحليل مراحل النمو الديمغرافي، ومكانتها ضمن التراتب الحضري الاقليمي، ومراحل توسعها المجالي، وتدعم أنشطتها الاقتصادية. الكلمات المفاتيح: مدنين - نمو حضري- دينامية حضرية - التسلسل الهرمي - الجنوب الشرقي التونسي
Keywords: Djerba -- Gouvernorat

1560 Cerbe Deni̇z Savaşi - Köse, Sevilay (The Journal of Social Sciences, 2025)
Djerba Island, which had been a refuge for famous pirates since the second half of the 16th century, had an important position for the Mediterranean. Especially when Turgut Pasha, the Beylerbeyi of Tripolitania, took Djerba Island under his control, the Christian world's interest in the island increased. The Crusader troops formed to capture Djerba managed to capture the island and built a castle on the island despite the disagreement between the commanders, bad weather conditions, epidemics and deserters. Upon this news, the Ottoman navy under the command of Piyale Pasha moved towards the island of Djerba. The Ottoman fleet, which was outnumbered, defeated the Crusader fleet off the coast of Djerba. While some of the Crusaders fled, some of them took refuge in the castle of Djerba. The Crusaders were besieged by sea and land for two months. The Ottoman navy forced the Crusaders to surrender by attacking the wells in the castle. In return for the surrender of the Crusaders, their lives were spared and the island of Djerba was annexed to Tripolitania under the Ottoman Empire. This study focuses on the conquest of Djerba by the Ottoman navy, which was an important centre of refuge for Turkish pirates and the domination of the Central Mediterranean.
Keywords: Djerba -- Empire ottoman; Invasions chrétiennes -- Djerba -- 1560

مخطوط في أصول الفقه لابن سراقة العامري (ت410هـ): دراسة تحليلية - فخار, جابر بن سليمان (مجلة الشهاب, 2025)
Keywords: Malshūṭī, Tibghūrīn b. ʿĪsā al-

A First Glance at Pre-Islamic Pigments in Shells From Salūt (Sultanate of Oman) - Degli Esposti, Michele; Lotti, Paolo; Crippa, Gaia; Diego Gatta, G.; Zerboni, Andrea (Arabian Archaeology and Epigraphy, 2025)
Marine shells containing greenish or blackish pigments are frequently found at pre-Islamic archaeological sites in Southeast Arabia and are generally interpreted as ancient eye makeup, representing a long-standing tradition that continues to the present day. While these ‘cosmetic’ shells are primarily found in funerary contexts, their presence in residential areas suggests broader use within the community. Although relatively abundant, these shells have undergone limited chemical and mineralogical analysis, hindering a deeper understanding of their composition and production. This study presents the first archaeometric results from six marine shells excavated at Bronze and Iron Age sites in the Salūt and Bisya oasis (Sultanate of Oman). Chemical analyses reveal copper- and manganese-bearing minerals as the primary components of the greenish and blackish pigments, respectively. The presence of these minerals near the Salūt oasis suggests local pigment sources. This study represents the first step in a broader analytical programme aimed at the characterisation of samples from other archaeological sites of Southeast Arabia spanning over a wider chronological time frame.
Keywords: Archéologie -- Oman

نفوسة والنفوسيون في طبقات المشائخ بالمغرب للدرجيني - المقدمي, نادية عيسى خليفة (مجلة شمال إفريقيا للنشر العلمي, 2025)
Keywords: Prosopographie -- Djebel Nefousa

معركة النهروان (38هـ/ 658م): دراسة تحليلية للمقدمات والمآلات والتداعيات في ضوء تعدُّدية الروايات التاريخية - الريامي, علي بن سعيد; اليعربي, يونس بن مطر (مجلة الدراسات الإنسانية والأدبية, 2025)
هدفت هذه الدراسة إلى تحليل المقدمات التاريخية لمعركة النهروان 38هـ/ 658م، وتداعياتها على البنية السياسية والفكرية للمجتمع الإسلامي المبكر؛ مع تقديم قراءة جديدة تعتمد إلى مصادر متنوعة، بما فيها المصادر الإباضية التي أُهمِلَت في دراسات سابقة. تكمُن أهمية هذه الدراسة في الكشف عن جذور النزاعات السياسية والفكرية التي شَهِدَها الإسلام المبكر، وانعكاساتها على تشكيل المفاهيم المتعلقة بالشرعية السياسية وطاعة الحاكم، فضلًا عن فهمِ تداعياتها على الواقع العربي والإسلامي المعاصر، كونِها تُسَلِّطُ الضوء على واحدة من أكثر المراحل تعقيدًا وحسَّاسيَّةً في التاريخ الإسلامي. فمن خلال دراسة معركة النَّهروان؛ يمكن فهمُ الجذور الأولى للنزاعات السياسية والفكرية التي ظهرت في الإسلام المبكر، ومدى تأثيرها في ظهور ما عُرِفَ "الفِرَق الإسلامية" اعتمدت هذه الدراسة المنهجَ التاريخي التحليلي، من خلال تتبُّع الروايات التاريخية ومقارنتها نقديًّا؛ مع التركيز على تجاوز التَّحيُّز الأيديولوجي ودمج وجهات نظر المصادر المختلفة. ومن أبرز ما توصلت إليه هذه الدراسة من نتائج أنَّ معركة النَّهروان مثَّلت تحوًّلًا جوهريًّا في علاقة السُّلطة بالمعارضة، وأسهمت في ترسيخ الانقسامات الفكرية والسياسية، وأكدت ضرورة الاعتماد إلى مصادر متعددة لتقديم رُؤية شاملة للأحداث.الكلمات المفتاحية: النَّهروان؛ صِفِّين؛ السُّنَّة؛ الشِّيعة؛ الإباضية.
Keywords: Fitnah

Muscat in Rural Tanzania: Omani Arabs, Identity, and Citizenship in Post-Slavery Tanzania, 1920s–1960s - Nyanto, Salvatory S.; Becker, Felicitas M. (African Historical Review, 2025)
Studies on post-slavery in East Africa often concentrate on the aftermath of slavery for the formerly enslaved. By contrast, former owners’ experiences after abolition and during emancipation are rarely explored. This article examines the trajectories of Omani Arabs in western Tanzania during and after the end of slavery, ca. 1910 to the late twentieth century. Having settled and built slavelabour plantations along the central caravan route in the nineteenth century, they relocated to rural areas between the 1920s and 1930s following the legal abolition of slavery and great economic depression. To tell their story in postslavery Tanzania, we drew examples from primary sources deposited in the archives of Tanzania and the United Kingdom, and oral interviews collected from the many villages in rural western Tanzania where the Omanis’ descendants now live. We show that the history of the Omani Arabs and their identity in twentieth-century western Tanzania was shaped by economic dispossession and uncertainty about citizenship, but also by evolving cultural identities and sustained social networking.
Keywords: Relations -- Oman -- Zanzibar

A Tolerated Terror: Rahmah bin Jabir and the Age of Revolutions in the Gulf, 1760-1830 - Roberts, Nicholas P. (Itinerario, 2025)
Rahmah bin Jabir (c. 1760-1826) is one of the most frequently mentioned persons in British sources from the Gulf in the first decades of the nineteenth century. He is also found throughout important Arabic-language chronicles. Despite his prominence in the sources, however, scholars have paid him relatively little attention, in either English or in Arabic. Though often cast as a pirate, this article argues that Rahmah bin Jabir was a political entrepreneur critical to shaping the international order of the Gulf in the first half of the nineteenth century. Reading against the grain of the colonial archive and synthesizing British sources with Arab chronicles, this article brings to life a textured political imaginary of the Gulf in the global age of revolutions, using Rahmah to weave overlapping political agendas between different emerging states, including the Omanis, the Saudi-Wahhabis, the Bahrainis, the Qataris, and the British. I suggest that Rahmah stands as one figure through whom historians can continue piecing together an age of revolutions in the Gulf that is more than Europe’s emergence into modernity, one that highlights a complex and vibrant history of negotiation, endurance, and resiliency.
Keywords: Biographies

المسائل النحوية والصرفية في كتاب الإبانة في اللغة العربية لسلمة بن مسلم العوتبي - زيدان, انتصار محمد; قدوري, سوسن غانم (مجلة بحوث اللغة, 2025)
من اللغات التي تتميّز بنظام تركيبيٍّ نحويٍّ، وصرفيٍّ، وصوتيٍّ -فريدٍ- هي اللغة العربية، فإنها أجزل لغات العالم لفظاً، وأمكنِها مقدرةً على استيعاب المفردات، ولكلماتها وألفاظها دلالاتٌ مختلفات، ومعلومٌ أنّ اللغة فنٌّ لا يولد مع الإنسان إلا بعد المخالطة، والدراسة، وطول النظر، والعكوف على مصادرها - بحثاً وتقصّياً- للوقوف على بدائعها وأسرارها، وممن لَمَعَ نجمه، وبَانَ أُفقُه -امتداداً على طول الزمن- عالمٌ عاش في القرن الخامس الهجري عرف بـ "العوتبيّ" و"الصحاري"، إذ ترك لنا كتاباً في أربعة أجزاء أسماه: "الإبانة"، في بيان كثير من معاني اللغة، ومضمّناً إياه كثيراً من مسائل النحو والصرف والبلاغة والمعاني، جاء هذا البحث متناولاً بيانَ مكانة هذا العالم الكبير الذي غفلت عنه الدراسات، ثم بعضاً من أهم المسائل النحوية والصرفية الواردة في كتابه "الإبانة"، واستخراج هذا الكنز المتناثر بين طيّاته، وتناولها بالشرح والتفصيل ليستفيد منها الباحثون، على الرغم من ان هذا الكتاب مُعجَميٌّ؛ إلا أنّ هذه المسائل قد أخذت نصيبها منه عنده في الكتاب، جاء البحث في مبحثين: الأول تعريف بالعوتبيِّ وشيء من ترجمته، ثم تعريفاً بكتابه "الإبانة"، مع بيان محتواه وموضوعه، وأبرز ملامح منهجه فيه ، وجاء المبحث الثاني: باحثاً بعضاً من أهم المسائل النحوية والصرفية الواردة فيه، فأصحبت المسائل: أربعة نحويّات، وثلاثةٍ صرفيات، ثم خاتمة، مع أبرز النتائج.
Keywords: Linguistique -- Oman

الأمثال الشَّحْرِيَّة: ذاكرة الثقافة الشفوية في ظفار، عُمان = Shaḥrī Proverbs: the Memory of Oral Culture in Dhofar, Oman - الشحري, محمد مستهيل (Athīrat: Journal of Ancient Arabia, 2025)
ملخص البحث ‫يمكن القول بأن الأمثال الشحرية تشكّل جزءًا أساسيًا من الذاكرة الثقافية التواصلية ومن الخزان الثقافي الخاص في هذه الديار عبر التاريخ والتي تعكس بلا شك علاقة الإنسان بالأرض واستمراريته في أرض ظفار. يتناول البحث عددًا من الأمثال المنطوقة التي تعبر عن ثقافة مجتمعية تعتمد على الذاكرة في التواصل واكتساب المعرفة وتداول الثقافة. تكشف الأمثال عن المصادر الأولية في الثقافة الشعبية ومدى ارتباطها بالمعتقد الديني أو العرف الاجتماعي. وتتناول جزءا من ثقافة المجتمع تجاه المرأة فتقدر المرأة وتثمن دورها الاجتماعي، وتوضح الأمثال الشحرية عن نمط اقتصادي رعوي يشارك فيه الرجال والنساء معًا.‬
Keywords: Linguistique -- Oman

Al-Nejd, a Fortified Samad Late Iron Age Settlement in Sharqiyya North Governorate, Sultanate of Oman: an Attempted Reconstruction - Yule, Paul A.; Ayash, Nasser Bovoleti (Athīrat: Journal of Ancient Arabia, 2025)
Abstract First reported in 2014, a fortified site atop a small mountain adjacent to the village of al-Nejd shows another facet of the settlements of the little-known Samad Late Iron Age (SLIA). Until recently, few settlements of the Early Iron Age and late pre-Islamic period are recorded and published in the land between the Oman Peninsula (U.A.E.) and Oman’s southern province, Dhofar. While analyzing graves with skeletons and finds of the latter period yields information about their owners, settlements lag far behind. With this background, al-Nejd offers new insight into the settlement, in addition to the first coin to be found in Oman. The authors attempt graphic documentation to contextualize the architecture and answer two questions. First, is there a typical kind of SLIA fortification separate from other periods? Second, how closely is the SLIA related to its neighbors and the preceding period in terms of material culture and architecture?
Keywords: Archéologie -- Oman

New Rock Art Discoveries in Aṣ Ṣafiyya (Wadi Nafūn, Duqm), Sultanate of Oman - Fossati, Angelo E.; Garba, Roman (Athīrat: Journal of Ancient Arabia, 2025)
Abstract The Nafūn rock art complex, located in al-Wusṭā Governorate in south-central Oman, was discovered in 2020 and has emerged as one of the most extensive rock art sites in southeast Arabia. The site features 59 flat limestone rock surfaces with over 200 South Arabian inscriptions and over 500 engraved figures. These figures include maritime animal depictions such as sea turtles, sperm whales, squid, jellyfish, ray fish, and mola mola, along with more common depictions of camels (sometimes ridden) and horsemen hunting oryx or wild canids. The rock art tradition in the Nafūn area is estimated to reach from the 5th millennium BCE to the 2nd millennium CE, offering a unique window into a way of life that endured for over 6,000 years.
Keywords: Archéologie -- Oman

The Making of a Ruler: Haitham bin Tariq on the Omani Throne - Kechichian, Joseph Albert (Middle East Policy, 2025)
Oman's leadership transition from Qaboos bin Sa‘id to Haitham bin Tariq validated Al Sa‘id authority in more ways than one. While the 15th Al Sa‘id sultan has only been in power for slightly more than four years, his initial governance preferences indicate that he will manage with poise. Haitham has developed a new doctrine that emphasizes wealth creation, acceleration of education levels, ensuring norms of social security, improving civil rights, and promoting closer ties with the sultanate's neighbors. In key speeches, he has promised to address core challenges and, over the course of four years, has ushered in laws that translate his pledges into actions. This preliminary assessment of Haitham evaluates his early decisions, appraises his declared priorities, and identifies his major preferences. It further highlights some of the internal as well as foreign challenges that confront Omanis. Given his measured and contemplative personality, Haitham has adopted pragmatic policies to preserve and defend Omani interests—not only to continue on his predecessor's path but to further validate long-term Al Sa‘id aspirations.
Keywords: Vie politique -- Oman -- 2020-....

Bronze Age to Early Iron Age Water Harvesting and Management in the Ancient Oasis of Salūt (Bisya, Sultanate of Oman) - Degli Esposti, Michele; Cremaschi, Mauro; Zerboni, Andrea (Open Quaternary, 2025)
During the 3rd millennium BC, a series of oases located along the western foothills of the al-Hajar Mountains saw the establishment of intensive human occupation, associated with the construction of large buildings (the so-called “towers”) and residential structures. These settlements were supported by the onset of agriculture and their development was often associated with and made possible by the introduction of substantial water management systems, including simple wells and complex, large ditches. The oasis of Salūt, near Bisya in the central Sultanate of Oman, is one such Early Bronze Age (EBA) centre. There, extensive investigation of ancient hydraulic structures provided an opportunity to study contexts preserving significant information on ancient climate change and water availability, from the late 3rd to the second half of the 1st millennium BC. A geoarchaeological investigation targeted the huge ditch surrounding the EBA stone tower of Salūt-ST1. Its complete layout was revealed and large portions were fully excavated, allowing the documentation of its infillings and the geological substratum. At the same time, wells excavated at the bottom of the ditch witness the attempt to cope with the lowering water table at the turn of the 3rd millennium BC. Exploration of Iron Age (IA) wells, paired with the geoarchaeological study of sediments from the plain, further extended the chronological scope of the research, while a survey of the area identified ancient and more recent underground and open-air channels, including the exceptional radiometric dating for the introduction of the aflaj (the local term – plural – for the underground water tunnels) network serving the oasis in the late Holocene. This contribution presents the first synthesis including fresh data on how water was harvested and managed in the area of Salūt over almost two millennia, with a diachronic approach that finds little parallels in the region.
Keywords: Archéologie -- Oman

Homeland Is Where the Soul Resides: Travel Prayer, Passports, and Nation in the Western Indian Ocean - Limbert, Mandana E. (Comparative Studies in Society and History, 2025)
This article examines conflicting notions of political home or homeland (waṭan) in the early twentieth-century Western Indian Ocean. In a period of colonial consolidation and shifts in trans-oceanic mobility, determining political belonging took on urgency for both British officials and Omani intellectuals and migrants. This article examines how, in contrast to both anti-colonial nationalists and British colonial officials, homeland in Omani religious scholarship was neither bounded territorially nor articulated through origins or subjecthood. Yet, it was spatial, affective, and hierarchically determined. And, it was manifest, embodied, and performed in the daily requirements of prayer. Spatial but not territorial, necessary but personally, hierarchically, and affectively decided, this pious notion of homeland has for the most part been replaced by the nation-state form. Yet, legacies of attachment to waṭan outside the bounded territorial model occasionally surface, operating as a simultaneous, but not synonymous, expression of political and personal belonging.
Keywords: Emigration -- Oman

A critical analysis of the impact of early marriage on girls based on published autobiographies and a contemporary scholarly text – Īḍāḥ al-bayān fī nikāḥ al-ṣibyān - Mayberry, John F. (Medico-Legal Journal, 2025)
Background This work emerged from a need to better understand the “lived experience” of early marriage for girls and how it should impact on contemporary attitudes in the Muslim community and encourage it to support the international movement with the aim of a minimum common age of 18 years for marriage of young people. Objective To identify from contemporary published literature, including autobiographies and religious texts dealing specifically with early marriage, the effects of early marriage on individuals and to set this as a background to the extensive literature on its medical, psychological and social impact. Participants and setting: The setting is the published words of two women and a man who were involved in early marriages and a commentary on the topic by an Ibadi theologian. Methods The documents were identified through searching a range of databases using various search engines. Texts were then analysed for key terms describing the impact of early marriage and these were then grouped into themes. Findings The extracts raise questions linked to the issue of consent and the role of adult coercion, including physical force and threat of harm. In practice girls are given in marriage by their guardians against their wishes and international conventions on the rights and care of children, as well as that outlined in Qur’an 4 v6. Conclusion Modern Muslim states face a real challenge in implementing 18 as the minimum age for marriage, especially in how to manage opposition to appropriate new legislation from some traditionalist groups.
Keywords: Fiqh -- mariage

Reasoning By Analogy According to the Ibāḍis In The Second Century AH = لاستدلال بالقياس عند الإباضية في القرن الثاني الهجري - الهادي, سيف بن سالم (International Journal of Fiqh and Usul al-Fiqh Studies, 2025)
This research presents a preliminary study on qiyas (analogy) in the Ibadi School, focusing on the second century A. H. in which Abū ʿUbaydah Muslim bin Abī Karīmah and his students were present. It has shown that the school paid early attention to analogy. Abū ʿUbaydah, al-Rabīʿ, and Ibn ʿAbd al- ʿAzīz used it to varying degrees, and the latter one comes in the forefront of those who used it abundantly. Abū ʿUbaydah initially expressed reservations, due to the absence of standardized values, and the fear of adopting whims as a hidden premise for analogy, especially if the matter was related to dimāʾ (killing life) and furūj (private parts). However, the applied practices of what later became known to the uṣūlī scholars as the qiyas al-ʿillah wa al-dalālah (analogy of cause and indication) were evident in Abū ʿUbaydah’s masāʾil (issues) and inspired in his later students. Ibn ʿAbd al-ʿAzīz considered Abū ʿUbaydah as skilled and precise in his applications of analogy. This research traces these applications through the Mudawwanah (writings) of Abū Ghānim Al-Khurāsānī (d. 200 A. H.).
Keywords: Fiqh -- Irak -- 8e siècle

El retrato colectivo de los Banu Birzal - De Felipe, Helena (Anaquel de Estudios Árabes, 2025)
The aim of this paper is to reconstruct the collective portrait of the Banū Birzāl, a Berber nukkārite group that was exiled from the Maghrib to al-Andalus during the caliphate of al-Ḥakam II. The objective of this reconstruction is to highlight the effects that the changes in geographical, socio-political and religious contexts provoked in their collective biographical portrait, which, in certain periods, is transferred from the collectivity to certain individualities. The collective displacement of Banū Birzāl and the details of their historical trajectory allow us to draw some conclusions about their textual representation as a group, changes in both their leadership and their beliefs and, finally, about their mobility in the Mediterranean area.
Keywords: Banu Birzal -- Histoire; Nukkarisme -- Andalousie

Study of the antioxidant activity of some traditional date vinegar from the indigenous knowledge of the M’Zab valley populations (north-eastern Algerian Sahara) - Benhammadi, Zohra; Ould El Hadj, Mohammed Didi; Bouziane, Ghania; Eddoud, Amar; Kemassi, Abdellah; Chakou, Fatma Zohra; Khalifa, Sara; Benkhelifa, Nadjet (African Journal of Biological Sciences, 2025)
This study focuses on the physicochemical characterization and biological activities of some traditional date vinegars from the indigenous knowledge populations of the M’Zab valley (north-eastern Algerian Sahara). These are four types of vinegar made from different varieties of dates, including TemdjohoretTafezwine-Ghars (TTG), Ghars-Tafezwine-Azerza (GAT), H’Chef Deglet Noor (D1), and Ghars-Tafezwine-Azerza-Deglet Noor (ND). The analysis results show that the date vinegar samples studied are characterized by an acidic pH (3.15±0.02-3.62±0.00), high dry matter contents (3.98±0.17-8.47±0.06%), insoluble solids rate (8.1±0.06-15.05±0.03), in electrical conductivity (3.36±0.01-6.11±0.01ms/cm), and total acidity contents ranging from 14.17±2.40 for GAT to 39.8±0.92 g/l for TTG. The residual alcohol rates are 1±0.00% for the TTG sample to 4.9±0.00% for GAT. However, total sugar contents (0.88±0.1%7.36±0.57%) are more or less high in samples of traditional date vinegar, which gives a sweetness to some date vinegar samples. The protein contents (0.43±0.007-0.79±0.002) of the various date vinegar samples are low. Statistical analyses show that each type of traditional date vinegar has a distinct profile, influenced by the chemical characteristics of the cultivars used. The antioxidant activities of traditional date vinegar samples show their high antioxidant capacity for all types of radicals. Each sample of vinegar has significant antioxidant activities, although their activities are always lower than those of ascorbic acid (vitamin C) or Trolox. For each type of traditional date vinegar sample, it should be noted that the radical inhibition rates (FRAP, DPPH, and ABTS) are dosedependent. The sample with the highest antioxidant power remains GharsTafezwine-Azerza (GAT), with IC50 = 0.0538 mg product/ml distilled water for the DPPH test and IC50 = 0.0125 mg product/ml distilled water for the ABTS test. For a high reduction capacity by the FRAP test, it is 484.16±8.66 µM/ml equivalant Trolox.
Keywords: Botanique -- Mzab

The Sultan of Muscat in Vermont: Reimagining the Middle East in World History - Roberts, Nicholas P. (Middle East Critique, 2025)
While historians have never written about it, in May 1846 the Sultan of Muscat arrived in Weathersfield, Vermont for his first voyage to the United States. This article uses the Sultan’s arrival in Vermont as a platform for augmenting a growing chorus of historians challenging the geographic and disciplinary boundaries that continue to define Middle East Studies. Using archival sources from the US, UK, Zanzibar, and a range of secondary sources, this article addresses a complex centuries-long process of Omani expansion and expropriation that culminated in Zanzibar in the nineteenth century and the height of the Omani Empire as an active participant in shaping the modern world economy. The writing of world history and of Middle East history generally continues to commence from the presupposition of an inevitably ascendant Western-created and led modern world. This article challenges the latter assumption.
Keywords: Relations -- Oman -- Etats-Unis

The Search for Petroleum in The Sultanate of Oman – The First 120 Years - Heward, Alan P.; Morton, Michael Quentin; Kindi, Mohammed al- (Geological Society Special Publications, 2025)
This is a story of failure and success, of disappointment and elation. World wars, a market glutted with cheap oil and geologists unable to access areas of interest hampered the search. Early expeditions provided the first maps of the mountains and Dhofar, and glimpses of the geology of the interior, but no evidence of oil.
Keywords: Géologie -- Oman; Pétrole -- Oman

العلاقة الثقافية بين علماء عمان وعلماء جبل نفوسة ما بين القرنين (2هـ / 8م – 8هـ / 14م) - الندابي, ناصر بن علي; الكاسبي, يوسف بن سعيد بن ناجم (مجلة العمارة والفنون والعلوم الإنسانية, 2025)
الملخص: عنوان هذا البحث هو العلاقة الثقافية بين عمان وجبل نفوسة ما بين القرنين ( 2هـ / 8م – 8هـ / 14م)، فهو يتناول جانبا من جوانب العلاقة الثقافية العلمية ونموذجا من أواصر التواصل بين علماء عُمان وعلماء جبل نفوسه ( بدولة ليبيا حاليا)، وقد سلط الضوء على طبيعة هذه العلاقة وسبر أغوار عمقها وقدمها. ويهدف البحث إلى الكشف عن أسباب ودوافع التواصل بين علماء البلدين في داخل القطرين وخارجهما، وبيان أسس وثمار التبادل الثقافي بينهما ودور الحج في تعميق علاقتهما. وقد اعتمد الباحثان في هذا البحث على المنهج التحليلي، والقراءة الدقيقة المتأنية للروايات التاريخية، مستخدما السرد التاريخي متى اقتضى الأمر لتوضيح كنه تلك العلاقة وتفاصيلها. وقد توصل البحث إلى أن المذهب الإباضي هو أساس وسبب هذه العلاقة وهو المسؤول الأول والأخير عن استمرارها عبر القرون على الرغم من البعد الجغرافي بين المنطقتين، كما أن أكثر اللقاءات العلمية التي وقعت بين علماء القطرين كان أغلبها في العراص المقدسة بمكة المكرمة، ويعود ذلك إلى الظروف التي كانت مهيأة لتلك اللقاءات، من خلال تحديد أماكن محددة يلتقي فيها علماء المغرب والمشرق الإباضية في المشاعر المقدسة، وخرج هذا البحث بالكثير من الأدلة التي أبرزت عمق العلاقة بين العلماء، وأظهرت كذلك أن الدين الإسلامي الذي هو أساس هذه العلاقة كان السبب الأول والأخير في جمع مشرق العالم الإسلامي مع مغربه عبر هذه الفئة التي عرفت ترجمة هذا التوجه وإبرازها على الساحة الإنسانية، كما يمكن جعل هذه العلاقة سببا في تدعيم العلاقات اليوم، وهي فرصة لتبصير جيل اليوم والغد بضرورة هذه العلاقة وتدعيمها والسعي إلى استمرارها. الكلمات المفتاحية: الرحلات العلمية، التبادل الثقافي، دوافع التواصل، المذهب الإباضي، عمان، جبل نفوسة.
Keywords: Relations -- Djebel Nefousa -- Oman